Protruding pillar-array evaporators with crude-oil-sequestering thermal reservoirs for salt-free solar desalination via dynamic ion scavenging and thermal pumping - Eun Jin Kim; Seung Hee Han; Woong-Ki Hong; Won San Choi (Desalination, 2026)

Simultaneous LC-MS/MS screening of 222 drugs of abuse in eight solid food matrices using a unified QuEChERS-Based approach - Eunbin Ryu; Jae Ui Park; Jin Ah Lee; Sangeun Lee; Wonhee Koo; Yoon Hee Lee; Jungmin Shin; Jihyun Lee; Jaewoo Song; Hangji Ok; Mi Jeong Oh; Jae-Sung Pyo; et al. (Regulatory Toxicology and Pharmacology, 2026)

A mechanistic evaluation of sodium channel modulators in hiPSC-derived cardiomyocytes using fluorescence-based sodium flux imaging - Su-Bin Kim; Jaehun Lee; Jieun An; Ara Cho; Kun Hee Lee; Eunho Kim; Hwan Choi; Jina Ryu; Ki-Suk Kim; Choongseong Han; Dong-Hun Woo (Biotechnology Letters, 2026)

Performance validation of the KeraSkin™ reconstructed human epidermis (RhE) model according to OECD document no. 219 and exploratory optimization of its predictive capacity for in vitro skin corrosion testing - JunHo Park; Hayan Jeong; Seohwi Yoon; Yongbin Lee; Jung Eun Park; Su-Hyon Lee; Seolyeong Kim; Eunjin Byeon; Jungkwan Seo; Suejin Kim; Bong-Gun Ju; Sang Hee Lee; et al. (Toxicology in Vitro, 2026)

Stable photocatalytic CO2-to-CH4 conversion enabled by a 3D hydrophobic Ti3C2Tx MXene architecture under continuous flow - Hyunju Jung; Eunji Kim; Chi Won Ahn; Hee Han; Issam Gereige; Aqil Jamal; Yonghee Lee; Hee-Tae Jung (Chemical Engineering Journal, 2026)

A pseudo-bilayer organic photoanode for solar water oxidation - Gyu Won Chae; Seong Rae Kang; Jin Su Park; Euimin Lee; Jisu Yoo; Hyuna Kim; Jongbeom Kim; Hoon Kim; Donghyun Lee; Eunsong Jeon; Wonjun Kim; Changduk Yang; et al. (Chemical Engineering Journal, 2026)

Identification of constituents of Lamium amplexicaule applying UPLC‒QTOF MS analysis combined with feature-based molecular networking - Euna Choi; Jisu Park; Chang Hyun Jin; Min-Jeong Hong; Sun Hee Hong; Bo-Ram Kim; Bomi Nam; Ah-Reum Han; MinKyun Na (Biochemical Systematics and Ecology, 2026)

Evaluation of subchronic toxicity, genotoxicity, and blood kinetics of 1,2-benzisothiazolin-3-one following oral administration - So-Young An; Soyeon Jeon; ChulBeom Park; Seol-Hee Moon; Seung-Hwa Kim; Hyo-Jin Ahn; Hyun Kim; Jong-Sam Park; Beom Seok Han; Wan-Seob Cho (Regulatory Toxicology and Pharmacology, 2026)

Interfacial electron-transfer engineering in electrostatically assembled ɑ-Fe2O3/MXene for sulfamethoxazole degradation and antibiotic-resistance risk mitigation - Sejun Park; Yuri Park; Soyeon Kim; Idriss Mohdeb; Uijeong Han; Hongmok Jo; Si-Kyung Cho; Doo-Hee Lee; Yuhoon Hwang (Journal of Hazardous Materials, 2026)

Application of Fourier transform near-infrared (FT-NIR) spectroscopy and machine learning for non-destructive viability assessment of 20-year stored Pinus densiflora seeds - Da-Eun Gu; Ja-Jung Ku; Sim-Hee Han (New Forests, 2026)

Morphological and physiological differences between diploid and autotetraploid in citrus - Sang Su Han; Kyung Uk Yi; Eun Ui Oh; Eo Jin Kim; Ye Hee Jeong; Kwan Jung Song (Horticulture, Environment, and Biotechnology, 2026)

Retraction notice to “Biochar-induced metal immobilization and soil biogeochemical process: An integrated mechanistic approach” [Sci. Total Environ. 698 (2020) 134112] - Ali El-Naggar; Mi-Hee Lee; Jin Hur; Young Han Lee; Avanthi Deshani Igalavithana; Sabry M. Shaheen; Changkook Ryu; Jörg Rinklebe; Daniel C.W. Tsang; Yong Sik Ok (Science of The Total Environment, 2026)

Corrigendum to “Relationship of parental phthalate exposure with fetal growth and placental development at birth” [Reprod. Toxicol. 137 (2025) 109025] - Hye Jin Chang; Yoon Hee Cho; Yeong Sook Yoon; Younglim Kho; Je Yeon Lee; Dong Won Hwang; Jung Yeol Han; Jisun Lee; Young Ah Kim (Reproductive Toxicology, 2026)

Influence of storing muscle tissue in the cold on in vitro myogenic cell line development from the black sea bream (Acanthopagrus schlegelii) - Eun Soo Jeong; Dan Hee Han; Seung Pyo Gong (Fish Physiology and Biochemistry, 2026)

Cutting and loading scenario and radiological dose assessment for spent steam generator decommissioning - Hyun Jin Yu; Do Won Hyeon; Yong Hee Han; Sang Ryeol Yoon; Jong Soon Song; Min Ho Lee (Annals of Nuclear Energy, 2026)

Integrating high-fidelity hiPSC-cardiomyocytes with AI-driven modeling for enhanced proarrhythmic risk assessment - Su-Bin Kim; Jaehun Lee; Jieun An; Ara Cho; Kun Hee Lee; Hwan Choi; Choongseong Han; Muhammad Adnan Pramudito; Ki Moo Lim; Dong-Hun Woo (Archives of Toxicology, 2026)
Cardiotoxicity remains the leading driver of drug attrition; however, its prediction remains suboptimal when conventional hERG assays and animal models are used. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) offer a human-relevant alternative that aligns with the CiPA initiative and ICH E14/S7B guidelines. This study validated an integrated platform that combines high-purity hiPSC-CMs with Artificial Intelligence (AI) to enhance the accuracy of predicting drug-induced proarrhythmic risk. Phenotypic characterization of the hiPSC-CMs demonstrated high cardiac differentiation efficiency (cTnT + > 95%) and a predominant ventricular-like identity (MLC-2 V + , 78–84%), ensuring biological relevance for ventricular arrhythmia assessment. Electrophysiological data from 28 CiPA reference compounds were collected via Multielectrode Array (MEA) to train multiple machine learning models. The Artificial Neural Network outperformed the other architectures, achieving a superior ROC-AUC of 0.982. The utility of the platform was evaluated using 12 anticancer agents. Although most drugs showed dose-dependent reductions in impedance-based viability, four compounds (Idarubicin, Erlotinib, Sunitinib, Cyclophosphamide) did not exhibit overt structural cytotoxicity. However, MEA analysis revealed significant functional perturbations, including FPDcF prolongation, in sunitinib- and erlotinib-treated samples after long-term treatment. The AI model subsequently classified these two agents as high-to-intermediate risk for Torsades de Pointes (TdP), thereby quantifying their time-dependent proarrhythmic liabilities. These findings show the platform’s ability to detect hidden functional cardiotoxicity, often missed by standard viability assays. The AI-hiPSC-CM system offers a high-throughput, early-stage safety screening tool that bridges in vitro data and clinical outcomes with a standardized risk assessment framework.

Corrigendum to “Heavy metal-induced proteomic profiles associated with disease risk in environmentally vulnerable populations” [J Hazard Mater 511 (2026) 142267] - Min Heo; Sora Mun; Nam-Eun Kim; Hyeongyu Shin; Ah Ra Do; Jeeyoung Kim; Jung-Yeon Kwon; Sujin Seo; Hyein Han; Yong Min Cho; Young-Seoub Hong; Hee-Gyoo Kang; et al. (Journal of Hazardous Materials, 2026)

Heatwave-driven amplification of ozone formation offsets emission control benefits in VOC-limited megacities - Han-Jun Ji; Hyo-Jung Lee; Jong-Min Kim; Sang-Seok Oh; Min-Seong Kim; Cheol-Hee Kim (Journal of Environmental Management, 2026)

Smart thrust bearing with integrated discharge-based energy harvesting and deep-learning fault detection - Jimin Kong; Dongwon Seo; Seokjin Kim; Giyoung Son; Kyeonghwan Kim; Jang-Woo Han; Hee Jae Hwang; Jihoon Chung (Chemical Engineering Journal, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

Evaluation of two novel superoxide dismutases (SODs) from the freshwater diatom Fragilaria saxoplanctonica and their specific responses to metals and pesticides - Hee-Jin Kang; Han-Sol Kim; Taehee Kim; Jang-Seu Ki (Ecotoxicology, 2026)

Emerging metabolic hormone therapeutics for metabolic dysfunction-associated steatohepatitis: incretin-based drugs, fibroblast growth factor analogs, and liver-targeting strategies - Sukwoo Han; Jaehee Shin; Jae Cheon Kim; Dong Hee Na (Journal of Pharmaceutical Investigation, 2026)
Background As the prevalence of metabolic dysfunction-associated steatohepatitis (MASH) continues to rise, drug development has accelerated, with growing interest in therapeutic strategies that harness metabolic hormones. Metabolic hormone-based approaches, particularly those originally developed for obesity and diabetes, have shown potential to mitigate MASH. Notably, the glucagon-like peptide-1 receptor (GLP-1R) agonist semaglutide received accelerated approval for MASH in 2025. In addition, GLP-1R-based multi-agonists and candidates leveraging the metabolic actions of fibroblast growth factor (FGF) 21 are in active clinical development for liver disease. Area covered This review provides an overview of metabolic hormone-based therapies, including incretin-based drugs and FGF analogs, that are currently under clinical development for MASH. It also discusses liver-targeting strategies to achieve selective hepatic delivery, which may vary according to the expression of liver-specific receptors and fibrosis degree. Expert opinion Within the MASH therapeutic landscape, incretin-based therapies are evolving from GLP-1R mono-agonist to multi-agonist approaches that aim to combine weight loss-mediated benefits with mechanisms that directly modulate hepatic lipid handling and inflammation. Moreover, the therapeutic actions of metabolic hormones in MASH, together with the expression profiles of their corresponding receptors, play a critical role in determining targeting strategies. Stage-specific and liver-selective delivery strategies will likely distinguish next-generation candidates. This review summarizes the pharmacological mechanisms and delivery strategies of each agent class and further explores these receptors as potential targets to inform the development of precision therapeutic approaches.

Ethanol extract of the freshwater green alga Prasiola japonica attenuates hair loss and promotes hair growth in a testosterone-induced hair loss model - Yun Soo Cho; Sang Hee Park; Han Soo Kang; Dong Seon Kim; Ji Hye Yoon; Sieun Yoon; Natasha Christabella Sutopo; Ha Jin Noh; Dong Sam Kim; Jae Youl Cho (Algae, 2026)
Prasiola japonica is a freshwater green alga distributed in Northeast Asia. This study investigated the effects of 70% ethanol extract of P. japonica (Pj-EE) under testosterone-induced hair loss conditions using C57BL/6 mice and human dermal papilla (HDP) cells. Topical application of Pj-EE promoted hair regrowth, increased hair length, and enhanced follicular density and activity in vivo. Pj-EE treatment also partially restored hair type distribution by reducing the proportion of zigzag hairs and increasing guard and awl hairs. Although these effects were less pronounced than those observed with minoxidil, consistent improvements were detected across multiple parameters. Mechanistic studies showed that Pj-EE inhibited 5α-reductase activity and reduced dihydrotestosterone (DHT) production in HDP cells, accompanied by downregulation of androgen receptor expression. Additionally, Pj-EE decreased proapoptotic Bax levels while increasing proliferation-associated markers (Ki67 and proliferating cell nuclear antigen) and the anti-apoptotic protein Bcl-2 in a dose-dependent manner. Functionally, Pj-EE enhanced HDP cell proliferation and migration and attenuated testosterone-induced apoptotic responses, indicating improved follicular cell viability under androgen-stimulated conditions. High-performance liquid chromatography analysis based on comparison with an authentic phytol standard identified phytol as a representative constituent of Pj-EE, and its high abundance was associated with 5α-reductase inhibitory activity. Collectively, these findings suggest that Pj-EE may attenuate androgen-responsive hair loss conditions by modulating 5α-reductase/DHT signaling and supporting follicular cell proliferation and survival in a testosterone-induced model.

Heavy metal-induced proteomic profiles associated with disease risk in environmentally vulnerable populations - Min Heo; Sora Mun; Nam-Eun Kim; Hyeongyu Shin; Ah Ra Do; Jeeyoung Kim; Jung-Yeon Kwon; Sujin Seo; Hyein Han; Yong Min Cho; Young-Seoub Hong; Hee-Gyoo Kang; et al. (Journal of Hazardous Materials, 2026)

Iron availability modulates ferric reduction oxidase (FRO) gene expression in the toxic dinoflagellate Alexandrium pacificum - Quynh Thi Nhu Bui; Han-Sol Kim; Sofia Abassi; Hee-Jin Kang; Jang-Seu Ki (European Journal of Protistology, 2026)

Synergistic oxygen intermediate spillover in Pt3Co-PtCo dual-phase intermetallics for enhanced oxygen reduction kinetics - Uhyeok Son; Jong Yoon Lee; Hye Jeong Joe; Gi Won Lee; Seunggyun Han; Seon-yeong Lee; Jeong Hee Lee; Jae-Hyun Park; Sung Jong Yoo; Kug-Seung Lee; Seok Ki Kim; Joseph T. Hupp; et al. (Chemical Engineering Journal, 2026)

Hydrogen production in plasma gasification of pulp-derived organic waste: Numerical analysis using MHD–CFD simulations - Chang-Hyeon Kim; Seong-Pyo Kang; I-Jeong Jeon; Eun-Su Yoon; Han Jun Lee; Jae-Hak Lim; Won-Jun Jang; Tae-Hee Kim; Jae-Oh Shim (Bioresource Technology, 2026)

Doubling frequency of summer cold surges in recent decades and their impact on East Asian extreme precipitation - Kwang-Hee Han; Jee-Hoon Jeong; Sung-Ho Woo; Ho-Young Ku; Hayeon Noh; Baek-Min Kim (Atmospheric Research, 2026)

Association of long-term ambient air pollution exposure with LDL cholesterol level by visceral adiposity in Korean adults - Sujeong Han; Seo Eun Hwang; Jae Moon Yun; Soontae Kim; Yoon-Hee Kang; Hyun-Jin Kim; Jin-Ho Park (Atmospheric Pollution Research, 2026)

Genetic diversity and genome-wide association study of horticultural traits in pumpkins (Cucurbita moschata) originating from East Asia - Eun Su Lee; Yoon Jeong Jang; Ye-Rin Lee; Oakjin Lee; Hee-Bum Yang; Hye-Eun Lee; Koeun Han; Do-Sun Kim (Horticulture, Environment, and Biotechnology, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Ground response analysis and liquefaction assessment of subsea soils at an offshore platform site - Hyejin Lee; Byungmin Kim; Jieun Kim; Taek Hee Han; Jun Kil Park; Youngjin Choi; Hyung-Ik Cho; Jae-Hyun Kim; Jeongmin Goo (Bulletin of Earthquake Engineering, 2026)
The development of underwater infrastructure is increasingly important due to the rising demand for offshore resource utilization and marine spatial expansion. This study evaluates the seismic behavior of subsea soil at a proposed offshore platform site, focusing on liquefaction potential and cyclic softening. Site-specific geotechnical investigations, including Standard penetration tests (SPT), cone penetration tests (CPT), and shear wave velocity ( V S ) measurements, were conducted to characterize the soil profile. Nonlinear site response analysis revealed significant amplification of seismic waves in the 0.2–2.0 s period range, due to soft clay layers. Liquefaction potential was evaluated using cyclic resistance ratio (CRR) and cyclic stress ratio (CSR) methods, following KDS 17 10 00 and effective stress-based dynamic analysis. Results indicated that the upper soil layers consist of high-plasticity clay, have a low likelihood of liquefaction. Cyclic softening analysis showed that softening may occur at shallow depths under 50-year return period earthquakes, and more broadly under 500-year events. The factor of safety varied depending on the undrained shear strength ( S u ) estimation method. While the site satisfies international seismic design standards for liquefaction, potential cyclic softening suggests that further design considerations are needed. This study offers a practical framework for evaluating seismic stability of submarine soils.

Editor's Note to “Inhibiting bacterial biofilm formation by stimulating c-di-GMP regulation using citrus peel extract from Jeju Island” [Sci. Total Environ., 872, (2023), 162180] - Han-Shin Kim; So-Young Ham; Hwa-Soo Ryoo; Hee-Deung Park; Jeong-Hoon Park (Science of The Total Environment, 2026)

Nickel-incorporated core–shell porous organic polymer for green conversion of levulinic acid to γ-valerolactone - Yujin Choi; Hyug Hee Han; Chaewon Shin; Jung-Hyeok Park; Joo Yeon Han; Chang-Ha Lee; Seenu Ravi; Youn-Sang Bae (Chemical Engineering Journal, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

Evaluation of Metal(loid) Immobilization and Lettuce (Lactuca Sativa L.) Growth in Soil Treated with Biochar and Modified Biochar with Iron Phosphate - Han Na Kim; Seung Jun Lee; Su Kyeong Shin; Jeong Yeon Kim; Ye Eun Lee; Jin Hee Park (Water, Air, & Soil Pollution, 2026)

Cell membrane-camouflaged nanoparticles: selection strategy in incurable disease treatment - Hyunjun Moon; Jeongeun Kim; Gyuri Bae; Woong Choi; Suk Han Jung; Soobok Lee; Kangseok Lim; Jin Hee Na; Jeong Uk Choi; Jong-Ho Kim; Sangmin Lee (Journal of Pharmaceutical Investigation, 2026)

Multi-Scale Temporal Uncertainty-Aware Hierarchical Adaptive Ensemble for Intelligent Ship Emission Monitoring and Prediction - Duc-Anh Pham; Kyeong-Ju Kong; Jung-Min Kim; Hee-Sung Yoon; Seung-Hun Han (Journal of Marine Science and Engineering, 2026)
This paper presents a novel Multi-Scale Temporal Uncertainty-aware Hierarchical Adaptive Ensemble (MSTU-HAE) algorithm for intelligent ship emission monitoring and prediction in maritime environmental compliance applications. The maritime shipping industry contributes approximately 3% of global CO2 emissions and significant amounts of nitrogen oxides and sulfur oxides, necessitating advanced predictive monitoring systems. The proposed MSTU-HAE algorithm integrates three key innovations: multi-scale temporal feature extraction using causal convolutions at short-term (5 samples), medium-term (20 samples), and long-term (60 samples) windows; gas-specific attention mechanisms that automatically weight temporal scales based on individual emission gas characteristics; and three-level hierarchical uncertainty quantification encompassing individual model uncertainty, ensemble disagreement, and regulatory compliance risk assessment. Experimental validation was conducted using emission data collected from a fishing vessel over 3 operational days (1732 original samples), augmented to 17,320 samples via controlled replication with noise injection to support model training. Rigorous temporal data splitting with 70%/15%/15% train/validation/test partitioning ensures no data leakage. Comparative analysis against six baseline methods (XGBoost, LSBoost, AdaBoost, Ridge Regression, Random Forest, and K-Nearest Neighbors) demonstrates that MSTU-HAE achieves superior average performance, with R2 = 0.9670 and NSE = 0.9670 across all emission gases. This research contributes a robust, interpretable, and scalable prediction framework that advances the state of the art in maritime environmental monitoring through novel algorithmic innovations in temporal feature learning and uncertainty quantification.

Comparison between genomic alterations in mouse, pig, and human through whole-genome sequencing - Geon Hue Bae; Seong Gyu Kwon; Jeong-Woo Choi; Joo Hee Hong; CheolMin Jeon; Areum Cho; JaeEun Shin; Mee Sook Jun; Man-Hoon Han; Seock Hwan Choi; Ji Won Oh (Journal of Genetics, 2026)

Atmospheric deposition as a pathway for microplastic transport to the marine environment: Temporal variation and environmental factors - Youna Cho; Andrew Loh; Won Joon Shim; Gi Myung Han; Sung Yong Ha; Sang Hee Hong (Marine Pollution Bulletin, 2026)

Repurposing spent battery waste into plasmonic photothermal membrane for efficient solar-driven evaporation and freshwater production - Muhammad Zakria Tariq; Animesh Roy; Byungki Kim; Youn-Hee Han; Sang-Youn Kim; Bong-Kee Lee; Sung Jea Park (Journal of Environmental Management, 2026)

Integrative culture-based and 16S rRNA microbiome analysis combined with on-site temperature evaluation to enhance safety management of salt-fermented octopus and clams - Ki Won Lee; Young Hoon Lee; Yun O; Hea Yeon Han; Ga-Hee Ban; Min Suk Rhee; Sun Ae Kim; Tae Jin Cho (Food Control, 2026)

Boosting CO2 capture in UTSA-16 via alkali ion exchange - Hyug Hee Han; Seungho Yu; Yujin Choi; Kyu-Min Ryoum; Jong Hak Kim; Richard Blom; Carlos A. Grande; Masoud Mofarahi; Ki Chul Kim; Youn-Sang Bae (Chemical Engineering Journal, 2026)

Probiotic-Derived Strain-Specific Metabolites Ameliorate Metabolic Dysfunction–Associated Steatotic Liver Disease through Modulation of the Gut-Liver Axis - Sang Jun Yoon; Jieun Choi; Sung-Min Won; Jeong Seok Yu; Hee Young Kim; Hyun Chae Joung; In Gyu Park; Jung A Eom; Sang Hak Han; Do Yup Lee; Ki Tae Suk (Probiotics and Antimicrobial Proteins, 2026)

Discovering anti-obesity blue food compounds via combined deep learning and in silico approaches - Seo Hyun Shin; Eunseok Oh; Chanyoon Park; Seung Man Oh; Hee Jeong Hwang; Jeong Yun You; Hyeri Ryu; Gihyun Hur; Ji Woo Kim; Jung Han Yoon Park; Eun Roh; Heonjoong Kang; et al. (Molecular Diversity, 2026)
Blue foods, such as fish and aquatic sources, are rich in bioactive compounds with potential health benefits, including anti-obesity effects. AMPK, a key regulator of energy homeostasis and adipogenesis, plays a vital role in combating obesity by inhibiting adipocyte differentiation. This study aimed to identify natural AMPK activators from underexplored blue foods using a deep learning-based compound-protein interaction (CPI) prediction model that incorporates both local and global features of proteins and compounds. Local and global molecular characteristics were systematically represented using sequence-based encodings, molecular fingerprints, and protein descriptors to enhance the model’s ability to capture diverse biochemical relationships. The deep learning framework integrated these multimodal features through neural network modules to predict potential compound–protein interactions. In silico molecular docking was performed to refine the predicted interactions, leading to the identification of 94 top-scoring compounds with strong binding affinity toward AMPK. In vitro validation of five commercially available compounds confirmed anti-obesity activity. Notably, cyclo(Pro-Val) from Ulva pertusa , activated AMPK and modulated key adipogenic markers, suggesting its potential as a natural AMPK activator for obesity prevention and the feasibility of AI-driven screening for marine bioactives.

Longitudinal association of chronic periodontitis with all-cause dementia, Alzheimer disease, vascular dementia, and mild cognitive impairment: a distributed network analysis - Gyubeom Hwang; So Hee Lee; Sang-Won Han; YoungSoon Yang; Soyoung Lee; Yeshin Kim; Yerim Kim; Rae Woong Park (GeroScience, 2026)

A Next-Generation Recombinant Botulinum Toxin With Enhanced Activity and Longer Duration of Action - Mi Seon Shin; Laon Kim; Jae Yoon Byun; Hee Won Min; Su Hyeok Kim; Ui Beom Park; Deu John M Cruz; Seongsung Kwak; Kook-Han Kim (Toxicon, 2026)

Whole-genome shotgun metagenomics reveals environmental perturbations in the gut microbiome and resistome of wild raccoon dogs rescued at a wildlife center - Junbum Lee; Sungjoo Hong; Jeongheon Choi; Hyokeun Song; Jang-Hee Han; Young Deok Suh; Seong Chan Yeon; Seongbeom Cho (Science of The Total Environment, 2026)

Cross-cultural analysis of consumer perceptions of adzuki beans: A topic modeling approach using Korean and Japanese Q&A discourse data - Seo-Young Kim; Hee Jeong Hwang; Daeun Kim; Ra Yoo; Jung Han Yoon Park; Hee Yang; Ki Won Lee (Food Quality and Preference, 2026)

Inflammatory responses and cilia reorganization induced by daily exposure to diesel exhaust particles in primary human nasal epithelium - Dohyun Han; Jihyun Choi; Moo Kyun Park; Nahyun Kim; Doo Hee Han (Environmental Research, 2026)

Artificial intelligence‑based quantitative analysis of hepatic fibrosis in carbon tetrachloride-induced mouse model of metabolic dysfunction-associated steatohepatitis - Jin-Hee Lee; Myung-Hwa Yang; Gyeongjin Han; Won Hoon Jung; Myung Ae Bae; Ji-Seok Han; Tae-Sung Koo; Jae-Woo Cho (Toxicological Research, 2026)

Rapid ecotoxicity and genotoxicity assessment using Macropodus ocellatus cells - Minseon Kim; Ji Ho Park; Byeonghyeon So; Hojun Lee; Jee Hee Yoon; Yoo Jin Lee; Duyeol Kim; Hyung Wook Kwon; Jihae Park; Taejun Han; Sekyung Oh; Yun Haeng Lee; et al. (Toxicological Research, 2026)

Biological upcycling of conditionally biodegradable plastics: enzymatic depolymerization to microbial valorization and consolidated bioprocessing frameworks - Yunhee Jeong; Sol Min Han; Jieun Wu; KwangYoung Park; Yunjeong Song; Yung-Hun Yang; Kyung-Jin Kim; Jungoh Ahn; Kyungmoon Park; See-Hyoung Park; Si Jae Park; Eun Ju Yun; et al. (Systems Microbiology and Biomanufacturing, 2026)

Reexamining Korea’s successful forest restoration through the revised PDCA framework - Hyun Park; Hee Han; Dayoung Kim; Sara Kim (Environmental Management, 2026)

A feasibility study of a non-aromatic oil as an alternative fuel for its application to jet aviation and rocket-engine fuels - Hee Sun Han; Cheon Hyeon Cho; Yejin Kang; Chae Hoon Sohn (Fuel, 2026)

Distribution and composition of floating litter in coastal and offshore waters surrounding South Korea - Yu Lee Jang; Sang Hee Hong; Soeun Eo; Gi Myung Han; Sung Yong Ha; Hyungbeen Lee; Inwoo Han; Won Joon Shim (Environmental Pollution, 2026)

3D channeled porous carbon hosts with cobalt nanoparticle-induced zincophilicity for stable zinc anodes - Hyunsoo Lee; Donghyeon Nam; Chaehyeon Moon; Jinseok Park; Michael J. Lee; Keun Hee Kim; Hyeonsoo Han; Donghyeok Roh; Kyungmo Kim; Jaeyoung Choi; Seung Woo Lee; Byung-Hyun Kim; et al. (Chemical Engineering Journal, 2026)

Diesel exhaust particles attenuate skeletal muscle cell proliferation and induce skeletal muscle atrophy through activation of AMP-activated protein kinase - Yeong Hoon Kang; Hyun Joung Lim; Eunsook Park; Jihye Bang; Hee-Soo Han; Youngyoul Kim; Min Ju Kang; Kyung-Ok Uhm; Hyeon Soo Kim (Molecular & Cellular Toxicology, 2026)

Mediation Effect of Oxidative Stress in the Associations between Cadmium Exposure and Renal Tubular Damage of Residents in Metal-Polluted Regions in Korea - Dahee Han; Kyung-Hwa Choi; Jang-Hee Lee; Young-Seoub Hong; Woo Jin Kim; Yong Min Cho (Exposure and Health, 2026)

Vivianite for simultaneous stabilization of arsenic, antimony, and lead in complex contaminated systems - Han Na Kim; Girish Choppala; Ravi Naidu; Jin Hee Park (Environmental Geochemistry and Health, 2026)

BAARTR: Boundary-Aware Adaptive Regression for Kinematically Consistent Vessel Trajectory Reconstruction from Sparse AIS - Hee-jong Choi; Joo-sung Kim; Dae-han Lee (Journal of Marine Science and Engineering, 2026)
The Automatic Identification System (AIS) frequently suffers from data loss and irregular report intervals in real maritime environments, compromising the reliability of downstream navigation, monitoring, and trajectory reconstruction tasks. To address these challenges, we propose BAARTR (Boundary-Aware Adaptive Regression for Kinematically Consistent Vessel Trajectory Reconstruction), a novel kinematically consistent interpolation framework. Operating solely on time, latitude, and longitude inputs, BAARTR explicitly enforces boundary velocities derived from raw AIS data. The framework adaptively selects a velocity-estimation strategy based on the AIS reporting gap: central differencing is applied for short intervals, while a hierarchical cubic velocity regression with a quadratic acceleration constraint is employed for long or irregular gaps to iteratively refine endpoint slopes. These boundary slopes are subsequently incorporated into a clamped quartic interpolation at a 1 s resolution, effectively suppressing overshoots and ensuring velocity continuity across segments. We evaluated BAARTR against Linear, Spline, Hermite, Bezier, Piecewise cubic hermite interpolating polynomial (PCHIP) and Modified akima (Makima) methods using real-world AIS data collected from the Mokpo Port channel, Republic of Korea (2023–2024), across three representative vessels. The experimental results demonstrate that BAARTR achieves superior reconstruction accuracy while maintaining strictly linear time complexity (O(N)). BAARTR consistently achieved the lowest median Root Mean Square Error (RMSE) and the narrowest Interquartile Ranges (IQR), producing visibly smoother and more kinematically plausible paths-especially in high-curvature turns where standard geometric interpolations tend to oscillate. Furthermore, sensitivity analysis shows stable performance with a modest training window (n ≈ 16) and minimal regression iterations (m = 2–3). By reducing reliance on large training datasets, BAARTR offers a lightweight, extensible foundation for post-processing in Maritime Autonomous Surface Ship (MASS) and Vessel Traffic Service (VTS), as well as for accident reconstruction and multi-sensor fusion.

Biofouling mitigation in cathodic electrochemical filtration via combined sublethal oxidative stress and electrostatic repulsion - Jeong Hoon Lee; Han-Shin Kim; Eun-Tae Yun; So-Young Ham; Peng-Fei Sun; Hwa-Soo Ryoo; Hee-Deung Park (Water Research, 2026)

Molecular biomarkers associated with environmental naphthalene exposure in the respiratory system - Hye-Jeong Han; Amartuvshin Baasankhuu; Bogun Kim; Angela Astrid Sekar Prameswari; Karina Kalani; Paolo Panza; Sangwoo Lee; Woo-Keun Kim; In-Geol Choi; Cheol-Hee Kim; Hyun-Taek Kim (Science of The Total Environment, 2026)

Molecular spacer engineering of carbazole–phosphonic acid SAMs: Probing interfacial energetics in low-light organic optoelectronic devices - Hee Chun Kim; Ji Hyeon Lee; Tae Hyuk Kim; Min Jong Lee; Eun Soo Shim; Seunghwan Bae; Hyungju Ahn; Han Jung Park; Nak-Seung Patrick Hyun; Jea Woong Jo; Jae Won Shim (Chemical Engineering Journal, 2026)

Bisphenol AF induces mouse spermatogonia apoptosis via reactive oxygen species-mediated Beclin-1 cleavage - Hyo Jin Gu; Gil Un Han; Seul Gi Kim; Sung-Hwan Moon; Seung Hee Shin; Buom-Yong Ryu (Toxicological Research, 2026)

Suppression of Inflammatory Responses Through GD3 Synthase (GD3S) Silencing Mediated by TLR4 Signaling: In Vitro and In Silico Analysis - Jun-Young Park; Abekura Fukushi; Hee-Do Kim; Han-His Kuo; Yu-Chan Chang; Daeui Park; Cheorl-Ho Kim (Molecular Neurobiology, 2026)

miR-495-3p Attenuates Neuronal Apoptosis Through The Activation of Wnt/MAPK Pathways in Ischemic Stroke - Eunjae Jang; Hee Yu; Jiyun Choi; Jin Yoo; Hyong-Ho Cho; Byeong C. Kim; Han-Seong Jeong; Sujeong Jang (Molecular Neurobiology, 2026)

Necessity of considering sex factors in the clinical application of transdermal formulations - Seung-Hyun Jeong; Se-Jin Ko; Hyeon-Hee Eom; Eon-Ji Han; Ji-Hun Jang; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2026)

Copper modulates cell fate through the PLK1–FOXO3a–β-catenin signaling pathway by differentially regulating cuproptosis and EMT - Hyo-Jun Lee; Ju-Hee Park; Do-Yeon Kim; Dae-Young Kim; Min-Jae Yi; Wu-Seong Choi; Han-Heom Na; Sehyun Chae; Young Taek Oh; Keun-Cheol Kim (Apoptosis, 2026)

6-PPD induces mitochondrial dysfunction and reduces healthspan and lifespan through SKN-1 in Caenorhabditis elegans - Moonjung Hyun; Laxmi Rathor; Hye-Jin Kim; Ho-Jeong Lee; Taylor McElroy; Moongi Ji; Min-Seok Choi; Steven Beck; Julia Bailey; Hun Hwan Kim; Yi Sheng; Jeong-Doo Heo; et al. (Journal of Hazardous Materials, 2025)

Lung neoplasm development in a mouse model exposed to fine particulate matter in Korea - Hyunseung Oh; Yoon Jeong Nam; Jin Young Choi; Hyejin Lee; Hong Lee; Yu-Seon Lee; Yoon Hee Park; Su A. Park; Hayan Park; Jaeyoung Kim; Sang Hoon Jeong; Ju-Han Lee (Molecular & Cellular Toxicology, 2025)

Optimal chemokine receptors for enhancing immune cell trafficking in adoptive cell therapy - DoYeon Han; Byung-Kwan Jeong; Jong Moo Hong; Jeong-Han Seo; GunHee Lee; Kwanghee Kim; Chorong Hong; Hyeonjin Lee; Su Min Cha; Jong Hyeok Kim; Taehyun Park; Gyungyub Gong; et al. (Immunologic Research, 2025)

Reducing electrical conductivity of nutrient solution to prevent rhizosphere salt accumulation and its impact on cherry tomato growth and fruit characteristics in hydroponics - Jeong Yeon Kim; Su Kyeong Shin; Jong Won Park; Han Na Kim; Govind D. Vyavahare; Jin Hee Park (Horticulture, Environment, and Biotechnology, 2025)

Microbial and Metabolic Dynamics during Fermentation of Vinegar with Rye Bread - Jae Hyeon Ahn; Gyoungmin Baek; Jae-Cheol Lee; Kira Moon; Han-Seung Noh; Aslan Hwanhwi Lee; Byung Hee Chun (Current Microbiology, 2025)

Generation of NOD SCID mice with near-complete deletions of Il2rg and Prkdc for human cancer and HSC engraftment - You-Min Kim; Hee Ju Na; Do Hee Kwon; Jae Hoon Lee; Bo Min Park; Subin Lee; Tae Wook Nam; Mi Yeon Park; Sun Ha Park; Sung Joo Kim; Bongkum Choi; Han-Woong Lee (Transgenic Research, 2025)
Immunodeficient mouse models are invaluable tools for preclinical research, particularly for cancer therapies and studies of the human immune system. Notably, strains with combined Prkdc (scid) and Il2rg (null) mutations—such as NOG and NSG mice— are widely used due to their profound immunodeficiency, allowing efficient engraftment of various human cells. However, these models were generated by disrupting the Il2rg gene through replacement with a neomycin resistance (Neo) cassette in embryonic stem cells. Incomplete excision of this cassette can inadvertently alter the expression of neighboring genes, thereby introducing potential confounding variables. In addition, they may still express mutant mRNAs that escape nonsense-mediated decay (NMD) and/or produce truncated proteins with residual activity, potentially compromising the interpretation of experimental outcomes. To address this, we developed the N2G mouse strain (NOD-2-Genes KO) where almost all genomic loci of both Prkdc and Il2rg genes are deleted via CRISPR/Cas9 genome editing. N2G mice exhibited tumor growth comparable to NOG mice following the transplantation with several human cancer cell lines. Moreover, human CD34 + cord blood (CB) cells engrafted into N2G mice showed robust reconstitution of human immune cells, especially T cells in peripheral blood, spleen and bone marrow, compared to NSG mice. These results suggest that N2G mice, lacking residual mutant mRNA and the exogenous Neo resistant gene, offer an advanced model for preclinical studies.

Probability of freedom from foot-and-mouth disease virus serotype Asia 1 in Southeast Asia, China and Mongolia - Masako Wada; Jun-Hee Han; Bolortuya Purevsuren; Karma Rinzin; Ashish Sutar; Ronello Abila; Supatsak Subharat (Preventive Veterinary Medicine, 2025)

Quantifying excess mortality attributable to tropical cyclones in South Korea: Insights from a generalized synthetic control approach - Changwoo Han; Soontae Kim; Yoon-Hee Kang; Tarik Benmarhnia (Environmental Research, 2025)

Piloti-inspired evaporators with sacrificial skins and light-guiding fibers for efficient and salt-resistant solar desalination - Dong Geon Lee; Seung Hee Han; Eun Jin Kim; Won San Choi (Chemical Engineering Journal, 2025)

The transport, removal, and formation of aerosols by a precipitating extratropical cyclone passing the Korean Peninsula - Yu-Jin Jo; Han-Gyul Jin; Hyo-Jung Lee; Cheol-Hee Kim (Atmospheric Research, 2025)

Association Between ABCG2 Polymorphism and Statin-Induced Adverse Events: A Meta-Analysis - Da Hoon Lee; Hae Ji Shin; Beom Yoon; Han Wool Kim; Hyeon Woo Jo; Hee Jung Kim; Woorim Kim (Cardiovascular Toxicology, 2025)

Montmorillonite modified with Fe3O4 and tannic acid for inhibition of S. aureus and MRSA biofilm formation - Seung-Cheol Jee; Dong-hee Han; Min Kim; Kyung-Bin Bu; Jung-Suk Sung; Avinash A. Kadam (Applied Clay Science, 2025)

Relationship of parental phthalate exposure with fetal growth and placental development at birth - Hye Jin Chang; Yoon Hee Cho; Yeong Sook Yoon; Younglim Kho; Je Yeon Lee; Dong Won Hwang; Jung Yeol Han; Jisun Lee; Young Ah Kim (Reproductive Toxicology, 2025)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Prodigiosin regulates cancer metabolism through interaction with GLUT1 - Hyun-A Yang; Tae-Hee Han; Keeok Haam; Kyung-Soo Lee; Jinsu Kim; Tae-Su Han; Moo-Seung Lee; Hyun Seung Ban (Natural Product Research, 2025)

Triflumizole induces excessive reactive oxygen species, inhibits the GPR30/PI3K/AKT pathway, and triggers apoptosis and autophagy in GC-1 spermatogonia cells - Seul Gi Kim; Dong-Jin Yoon; Daniel Chavez Varias; Gi Jeong Ahn; Gil Un Han; Sung-Hwan Moon; Hee-Seok Lee; Seung Hee Shin; Buom-Yong Ryu (Pesticide Biochemistry and Physiology, 2025)

Growth enhancement of harmful dinoflagellate Prorocentrum cordatum by bacterial community shifts driven by dissolved organic matter derived from raphidophyte Heterosigma akashiwo - Royoung Park; Joo-Hwan Kim; Jin Ho Kim; Sae-Hee Kim; Hyeon Ho Shin; Myung-Soo Han; Bum Soo Park (Harmful Algae, 2025)

Platycodin D reverses tumor necrosis factor-α-induced endothelial dysfunction by increasing nitric oxide through G protein-coupled estrogen receptor-mediated eNOS activity - Ju Yeon Chae; Gi Ho Lee; Seung Yeon Lee; Gil-Saeng Jeong; Hwi-yeol Yun; Eun Hee Han; Anh Thi Ngoc Bui; Hye Gwang Jeong (Chemico-Biological Interactions, 2025)

Evaluation of genomic breeding values and accuracy for carcass traits in Korean Hanwoo cows using whole-genome SNP chip panels - Ji-Hee Jang; Han-Deul Lee; Jong-Joo Kim; Md Azizul Haque (Mammalian Genome, 2025)

Evaluating the Trophic Structure of an Artificial Macroalgal Bed of Eisenia bicyclis Using C and N Stable Isotopes - Dong-Young Lee; Dongyoung Kim; Chan-Kil Chun; Youngkweon Lee; Kyu-Sam Han; Hyun Kyum Kim; Tae Hee Park; Hyun Je Park (Journal of Marine Science and Engineering, 2025)
In this study, we applied a new technique for vegetatively transplanting kelp Eisenia bicyclis to restore macroalgal habitats. We aimed to assess the restoration success of the E. bicyclis bed by comparing the carbon and nitrogen stable isotope ratios of macrobenthic consumers and their isotopic niches in artificial and control (barren ground) habitats. Except for the deposit feeding group, no significant differences were observed in isotopic values of the other feeding groups (suspension feeders, herbivores, omnivores, and carnivores) between the two sites. In contrast, our results showed wider isotopic niche indices for all feeding groups at the transplantation site compared to those at the control site, suggesting increased trophic diversity in the artificial habitat. Overall, these results indicate that the macroalgal bed created using the new method can play an ecological role in restoring functional properties of food web structures via trophic support of degraded coastal ecosystems.

Beneficial effects of probiotics on dysbiosis of gut microbiota induced by antibiotic treatment in healthy dogs - Sung-Jae Kim; Hee-Chun Chung; Soo-Yeon Park; Jae-Myun Lee; Jeong-Hee Han (Research in Veterinary Science, 2025)

Improved thermal stability of NbCoSn half-Heusler compounds via Sb doping-induced complementary point defect evolution - Kyuseon Jang; Poulumi Dey; Biswanath Dutta; Hail Park; Ji-Hee Son; Jeong-In Jang; Mohammed Kamran Bhat; Hanhwi Jang; Hyungsub Kim; Jungwoo Choi; Siyuan Zhang; Ruben Bueno Villoro; et al. (Chemical Engineering Journal, 2025)

Integrated membrane contactor system using NaOH solution for biogas purification and polyhydroxyalkanoate synthesis via cyanobacteria - Abduljelil W. Sabir; Dong Yun Han; Se Wan Kim; Simon MoonGeun Jung; Ga-Hyeon Kim; Karl Forchhammer; Jong-Hee Kwon; Pyung Soo Lee (Chemical Engineering Journal, 2025)

Impact of HOMER2 frameshift extension variant on auditory function and development - Eunjung Han; Ju Ang Kim; Saemi Park; Jin Hee Han; Min Young Kim; Yehree Kim; Ngoc-Trinh Tran; Bong Jik Kim; June Choi; Byung Yoon Choi (Journal of Molecular Medicine, 2025)
The HOMER2 gene, crucial for synaptic signaling and calcium homeostasis in the auditory system, is linked to sensorineural hearing loss (SNHL), with its variants contributing to severe SNHL in older adults, often necessitating cochlear implants in their 60 s or 70 s. In this study, we identified a novel frameshift extension variant, c.1033delC (p.Arg345Glu fs *64; p.R345E fs *64), which introduces a significantly longer protein extension than previously reported extension variants, in a patient in their sixties presenting with progressive profound SNHL. To investigate the pathogenic potential of this variant, we employed molecular modeling and zebrafish models, comparing wild-type HOMER2, a hypothetical p.R345* variant involving alteration of the most C-terminal 10 amino acids, and the patient-derived p.R345E fs *64 variant. AlphaFold2 predicts that the p.R345E fs * 64 variant causes significant structural changes in the HOMER2 EVH1 domain, disrupting interactions with Cdc42 and contributing to SNHL. Zebrafish models show that this variant, which combines truncation and extension features, impairs neuromast hair cell function and exacerbates auditory phenotypes, while also increasing cardiac anomalies. In comparison, the p.R345* variant showed an obvious milder impact. Our findings suggest that the pathogenic effect of the p.R345E fs *64 variant is more driven by the extension beyond the stop codon. Here we report that a novel frameshift extension variant of HOMER2 , which arises as a causative gene in elderly patients with profound SNHL, highlighting the need for genetic diagnosis in this population. Our findings reveal a solid pathogenic gain-of-function effect related to the long extension to the C-terminal of HOMER2 , and a possible link to cardiac anomalies.

Long-term exposure to air pollution and incident Alzheimer’s disease among older adults: evidence from a large-scale retrospective cohort in Korea - Hyung Doo Kim; Jongmin Oh; Jisun Myung; Changwoo Han; Hyun Joo Bae; Soontae Kim; Yun-Chul Hong; Youn-Hee Lim; Dong-Wook Lee (Environmental Science and Pollution Research, 2025)

Synergistic effects of oral milk ceramide-collagen peptides mixtures in preventing UV-induced inflammation and photoaging through TGF-β and NF-κB/MAPK signaling pathways in UV-exposed hairless mice - Sung Hee Han; Hyung Joo Suh; Sang Jun Lee; Yeok Boo Chang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Legacy and emerging persistent organic pollutants in sea turtles from Korean waters: Levels, profiles, and interspecies differences - Yelim Moon; Won Joon Shim; Sung Yong Ha; Gi Myung Han; Mi Jang; Il-Hun Kim; Hae-Rim Lee; Sang Hee Hong (Environmental Research, 2025)

Ecological Impacts of Sunflowers on Soil Microbial Communities: Insights from Full-Length 16S rRNA Sequencing - Seong-Jun Chun; Yingshun Cui; Jihoon Kim; Jun-Woo Lee; Sung Min Han; Kyong-Hee Nam (Current Microbiology, 2025)

Comparative toxicity of eleven bisphenol analogs in the nematode Caenorhabditis elegans - Sang Eun Ha; Myon Hee Lee; Sung Min Han; Sung-hwan Kim; Moonjung Hyun; Jeong Doo Heo (Toxicology Letters, 2025)

Impact of heat and ozone stress on rice growth and productivity: interactive and mitigating effects - Hyeon-Seok Lee; So-Hye Jo; Ju-Hee Kim; Seo-Yeong Yang; Jae-Kyeong Baek; Yeong-Seo Song; Nam-Jin Chung; Han-Yong Kim; Ji-young Shon (Science of The Total Environment, 2025)

Trophic niche shifts in Japanese anchovy, Engraulis japonica, during ontogenetic migration in a temperate continental shelf system - Changseong Kim; Jaebin Jang; Jaesik Yang; Jang Han Choi; Hee Yoon Kang; Seong Yong Moon; Ho Young Soh; Heeyong Kim; Chang‑Keun Kang (Progress in Oceanography, 2025)

Synthesis of Autotaxin-Inhibiting Lipid Nanoparticles to Regulate Autophagy and Inflammatory Responses in Activated Macrophages - So Won Jeon; Jun Kwon; Hee Gyeong Ko; Jong Sang Yoon; Yun A Kim; Ju-Ro Lee; Min-Ho Kang; Han Young Kim (Tissue Engineering and Regenerative Medicine, 2025)

Effects of dietary vitamin C supplementation on growth performance, antioxidant status, and growth hormone and insulin-like growth factor 1 levels in juvenile walleye pollock (Gadus chalcogrammus) - Ki Wook Lee; So-Sun Kim; Hae Kyun Yoo; Gyeong Sik Han; Hwa Yong Oh; Kwang Tae Son; Hee Sung Kim (Animal Feed Science and Technology, 2025)

Magnetic field-assisted bioleaching of cathode materials from spent Li-ion batteries using Acidithiobacillus ferrooxidans - Jun-Ho Hong; Jeon Kim; Ejin Han; Seon-Mo Yang; Hee-Soo Kim; Jihwan Kim; Chong Seung Yoon (Chemosphere, 2025)

Integrating bioaccessibility into human health risk assessment: Stabilization approach of smelter-contaminated soil with natural organic amendments - Minhee Kim; Jong-Sung Kim; Hee-Myong Ro; Junho Han (Journal of Environmental Management, 2025)

Feasibility of gold leaching from waste printed circuit boards with an airlift bioreactor applying the condensed distillers solubles as a microbial nutrient and its recovery by reduction - Duy Tho Tran; Ngoc Tu Trinh Tran; Xiaoyu Lin; Jong-won Choi; Minhee Han; Myung-Hee Song; Yeoung-Sang Yun (Journal of Environmental Management, 2025)

Mechanisms of arsenic oxidation and immobilization by structural and surface iron-modified nontronite - Ji-Hyun Park; Dong Yun Shin; Dong-Hee Lim; Jin Young Kim; Young Heon Kim; Eun-Ji Bae; Young-Soo Han (Chemical Engineering Journal, 2025)

Toxicity of diclofenac sodium salt after two weeks of daily intramuscular administration in cynomolgus monkeys - Sieun Yoo; Jung-Ho Noh; Hong-Soo Lee; Sang-Hee Lee; Eunji Choi; Dong-Il Kim; Seung Eui Min; Kang-Hyun Han; Sang Kyum Kim (Toxicological Research, 2025)

Transformation-associated recombination and heterologous expression of noncanonical depsipeptide nonribosomal peptide synthetase derived from marine Streptomyces - Jeong Sang Yi; Jin Won Choi; Ngoc Han Le Thi; Sung Jin Kim; Hyun-Ju Kim; Jung Min Kim; Jun Eui Park; Kyuho Moon; Dong Chan Oh; Sang Hee Shim; Ki Sung Kang; Yeo Joon Yoon (Marine Life Science & Technology, 2025)
Analysis of the secondary metabolite biosynthesis gene cluster (BGC) from marine Streptomyces sp. SNJ102 revealed the presence of a noncanonical nonribosomal peptide synthetase (NRPS), predicted to produce a depsipeptide compound. The NRPS gene cluster was captured by transformation-associated recombination and heterologously expressed in Streptomyces albus . The production of the new compound was confirmed using high-resolution liquid chromatography-mass spectrometry, and its structure was elucidated using nuclear magnetic resonance spectroscopy. The structure of the new depsipeptide was more similar to the monomeric structure of cyclic depsipeptides derived from fungi than to other Streptomyces -derived depsipeptides. In addition, the bacterial depsipeptide, which we named jejumide, showed promising anti-inflammatory activity. These results demonstrate that genome mining and successful heterologous expression of cryptic nonlinear NRPS BGCs from marine bacteria will facilitate the discovery of novel nonribosomal peptides and understanding of the complicated biosynthetic mechanism of nonlinear NRPS.

Erratum to “Species-specific effects of iron on temperate and tropical marine rotifers in reproduction, lipid and ROS metabolisms” [Chemosphere 277 (2021) 130317] - Chengyan Han; Hee-Jin Kim; Jae-Seong Lee; Yoshitaka Sakakura; Atsushi Hagiwara (Chemosphere, 2025)

Sustainable, highly effective selenate removal using electrochlorination facility–obtained magnesium precipitate: An approach to in situ layered double hydroxide formation - Han Gyeol Jeon; Jin-Seok Kim; Seonggyu Choi; Kyung-Hee Lee; Kyoung-Woong Kim; Sang-Ho Lee (Journal of Environmental Management, 2025)

Exploratory investigation of the correlation between microplastics and breast cancer: Polystyrene-derived microplastics promote cell proliferation via estrogenic endocrine disruption - Seoung-Woo Lee; Hee-Yeon Kim; Soyoung Jang; Wansoo Kim; Choonok Kim; Jiyeon Lee; Zae Young Ryoo; Jee Eun Han; Su-Min Baek; Jin-Kyu Park; Jun-Seong Hwang; Sung-Jun Lee; et al. (Journal of Environmental Chemical Engineering, 2025)

Carbon nanotube/metal organic framework hybrid scaffolds for scalable and self-structured OER catalyst coating: From rheology study to MEA fabrication - Suhyeon Lee; Yunseong Ji; Gisu Doo; MinJoong Kim; Jooyoung Shin; Chansol Kim; Man Ho Han; Woong Hee Lee; Jong Hyup Lee; Yeonji Kwak; Eunji Choi; Yonghwi Cho; et al. (Chemical Engineering Journal, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Effect of temperature and seedling cultivation period on the quality of plug seedlings of four medicinal plant - Eun Won Park; Jeong Hun Hwang; Hee Sung Hwang; Ji Hye Yun; So Yeong Hwang; Jin Yu; Hyeong Eun Choi; Jeong Kil Koo; Eun Song Lee; Kyung Sook Han; Young Ho Yoon; Seung Jae Hwang (Horticulture, Environment, and Biotechnology, 2025)

O2-microbubble of iron-porphyrin conjugated polyaspartamide for molecular ultrasound contrast effect - Yoon Na Cho; Jun Woo Lim; Seung Joo Oh; Sa Ra Han; Sungwoo Cho; Jimin Jeong; Byoung Hee Han; Jae Hyun Jeong (Biotechnology Letters, 2025)

Identification of QTL for rice panicle length and grain weight using a doubled haploid population derived from 93–11 and Milyang352 - Jiheon Han; Seung Young Lee; Yeeun Jun; So-Myeong Lee; Gyu-Hyeon Eom; Jong-Hee Lee; Youngjun Mo (Plant Biotechnology Reports, 2025)

Enhancing indigenous plant growth in metal(loid) contaminated soil using biochar - Han Na Kim; Keum Chul Yang; Su Kyeong Shin; Yeong Ju Seok; Ju-Sung Cho; Hyo Kyung Jee; Jeong Yeon Kim; Jin Hee Park (Chemosphere, 2025)

Neurotoxic effects of citronellol induced by the conversion of kynurenine to 3-hydroxykynurenine - Seong Soon Kim; Suhyun Kim; Yeonhwa Kim; Youngran Ha; Hyojin Lee; Hyunji Im; Jung Yoon Yang; Dae-Seop Shin; Kyu-Seok Hwang; Yuji Son; Sung Bum Park; Ki Young Kim; et al. (Journal of Hazardous Materials, 2025)

Recent advances in recovering bioactive compounds from macroalgae and microalgae using subcritical water extraction: Prospective compounds and biological activities - Md Sadek Ali; Monjurul Haq; Sin-Won Park; Ji-Min Han; Jang-Woo Kim; Min-Seo Choi; Sang-Min Lee; Jin-Seok Park; Man-Seog Chun; Hee-Jeong Lee; Byung-Soo Chun (Food Chemistry, 2025)

Performance of weighted genomic BLUP and Bayesian methods for Hanwoo carcass traits - Md Azizul Haque; Eun-Bi Jang; Han-Deul Lee; Dae-Hyun Shin; Ji-Hee Jang; Jong-Joo Kim (Tropical Animal Health and Production, 2025)

Spatial and Temporal Variation of Synechococcus Abundance and Diversity in the Yellow Sea - Jongseok Won; Myungjin Hyun; Wonseok Yang; Howon Lee; Yeonjung Lee; Seok Lee; Kongtae Ra; Hee Cheol Yang; Jae Hoon Noh; Dong Han Choi (Ocean Science Journal, 2025)

Transcriptome-Based Prediction of the Toxicity of the Marine Biotoxin Okadaic Acid in Human Vascular Endothelial Cells - Jong Hee Kim; Jeong-In Park; Yewon Kim; Mira Park; Jang Kyun Kim; Young-Seok Han; Youn-Jung Kim (Ocean Science Journal, 2025)

A Numerical Study for the Self-Propulsion Performance of a Propulsion System Using the Coanda Effect - Jun-Hee Lee; Kwang-Jun Paik; Do-Han Oh (Journal of Marine Science and Engineering, 2025)
This study evaluated the performance of a ship propeller numerically using the Coanda effect. The simulations applied a model based on a 6.5K DWT tanker and conducted self-propulsion assessments for three types of propellers: the original propeller, a normal propeller, and a Coanda propeller. The numerical simulations used the unsteady Reynolds-averaged Navier–Stokes (URANS) equations, incorporating the SST k–ω turbulence model. The influence of the additional thrust generated by the Coanda effect on the hull resistance and self-propulsion factors was analyzed. The key findings showed that the Coanda-based propeller achieved efficient propulsion performance by generating additional lift even at low rotational speeds. A self-propulsion analysis showed that the Coanda propeller required approximately 7.8% less delivered power than the original propeller. These results suggest that propulsion systems utilizing the Coanda effect offer superior efficiency and economic advantages over traditional technologies. This study provides critical baseline data for assessing the feasibility of a Coanda propeller, with further validation planned through full-scale ship simulations.

Corrigendum to ‘Deciphering the toxicity of polyhexamethylene guanidine phosphate in lung carcinogenesis: Mutational profiles and molecular mechanisms’ [Chemosphere Volume 368 (2024) 143785] - Hong Lee; Sang Hoon Jeong; Yong-Wook Baek; Hyejin Lee; Jason K. Sa; Ji Yoon Lee; Yu-Seon Lee; Yoon Jeong Nam; Jaeyoung Kim; Jonghoon Kim; Jin Young Choi; Su A. Park; et al. (Chemosphere, 2025)

Effect of LED spectrum on the vision, appetite, and growth of red seabream (Pagrus major) - Si-Chan Kim; Ji-Sung Moon; Josel Cadangin; Eun-Seo Lee; Bo-Hyun Joo; Han-Sik Kim; Sang-Woo Hur; Youn Hee Choi (Aquaculture, 2025)

The SGLT2 inhibitor remogliflozin induces vasodilation in the femoral artery of rabbits via activation of a Kv channel, the SERCA pump, and the cGMP signaling pathway - Minju Park; Wenwen Zhuang; Junsu Jeong; Hye Ryung Kim; YeEun Jang; Mi Seon Seo; Jin Ryeol An; Hongzoo Park; Eun-Taek Han; Jin-Hee Han; Wanjoo Chun; Won Sun Park (Toxicology and Applied Pharmacology, 2025)

Two new compounds from Apiospora xenocordella culture medium and their inhibitory effects on TNF-α-induced ROS generation and MMP-1 secretion - Haeun Kwon; Hee Woon Ann; Jin Su Lee; Jaeyoung Kwon; Keunwan Park; Yuanqiang Guo; Bang Yeon Hwang; Jae-Jin Kim; Joung Han Yim; Il-Chan Kim; Dae Sik Jang; Sullim Lee; et al. (Phytochemistry Letters, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

Efficient radon removal using a metal–organic framework with high density of unsaturated Co2+ sites - Kwang Hyun Oh; Seungho Yu; Jung Sub Kim; Kijun Kim; Hyug Hee Han; Yujin Choi; Ki Chul Kim; Youn-Sang Bae (Chemical Engineering Journal, 2025)

Facile manufacturing solutions for ultra-durable flexible MXene micro-supercapacitors in 8-inch scale - Eunji Kim; Yunhui Choi; Hyeong Jin Kim; Hyeong Min Jin; Yeon-Wha Oh; Sanghee Jung; Il-Suk Kang; Hee Han; Jaewoo Roh; Il-Kwon Oh; Jinwoo Lee; Chi Won Ahn; et al. (Chemical Engineering Journal, 2025)

5-Fluorouracil induces hair loss by inhibiting β-catenin signaling and angiogenesis - Jung-Il Kang; Youn Kyung Choi; Sang-Chul Han; Jin Won Hyun; Young-Sang Koh; Jaeseong Oh; Hye-Jin Boo; Eun-Sook Yoo; Hee-Kyoung Kang (Chemico-Biological Interactions, 2025)

Reduction of Low-Density Lipoprotein Cholesterol by Mesenchymal Stem Cells in a Mouse Model of Exogenous Cushing’s Syndrome - Yu-Hee Kim; Seonghee Jeong; Kyung-Ah Cho; So-Youn Woo; Seung-Ho Han; Kyung-Ha Ryu (Tissue Engineering and Regenerative Medicine, 2025)

An Efficient Method for Enrichment and In Vitro Propagation of Muscle Stem Cells Derived from Black Sea Bream (Acanthopagrus schlegelii) Skeletal Muscle - Dan Hee Han; Seung Pyo Gong (Marine Biotechnology, 2025)

Impact of Arctic Sea Ice Representation on Extended Medium-Range Forecasting: a Case Study of the 2016 Barents-Kara Sea Warming Event - Jung Hyun Park; Hyun-Joon Sung; Myung-Seo Koo; Junseong Park; Rae-Seol Park; Kwang-Hee Han; Ji-Han Sim; Hyo-Jung Lee; Hayeon Noh; Baek-Min Kim (Asia-Pacific Journal of Atmospheric Sciences, 2025)

Correction: Forecast Accuracy and Physics Sensitivity in High-Resolution Simulations of Precipitation Events in Summer 2022 by the Korean Integrated Model - Eun-Hee Lee; Sujeong Cho; Keon-Hee Cho; Ji-Young Han; Youngsu Lee; Junghan Kim (Asia-Pacific Journal of Atmospheric Sciences, 2025)

Impact of administration routes and dose frequency on the toxicology of SARS-CoV-2 mRNA vaccines in mice model - Jae-Hun Ahn; Jisun Lee; Gahyun Roh; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Kang-Min Han; Ji-Eun Kim; Hyo-Jung Park; Soyeon Yoo; Sung Pil Kwon; Eun-Kyoung Bang; et al. (Archives of Toxicology, 2025)
The increasing use of SARS-CoV-2 mRNA vaccines has raised concerns about their potential toxicological effects, necessitating further investigation to ensure their safety. To address this issue, we aimed to evaluate the toxicological effects of SARS-CoV-2 mRNA vaccine candidates formulated with four different types of lipid nanoparticles in ICR mice, focusing on repeated doses and administration routes. We conducted an extensive analysis in which mice received the mRNA vaccine candidates intramuscularly (50 μg/head) twice at 2-week intervals, followed by necropsy at 2 and 14 dpsi (days post-secondary injection). In addition, we performed a repeated dose toxicity test involving three, four, or five doses and compared the toxicological outcomes between intravenous and intramuscular routes. Our findings revealed that all vaccine candidates significantly induced SARS-CoV-2 spike protein-specific IgG and T cell responses. However, at 2 dpsi, there was a notable temporary decrease in lymphocyte and reticulocyte counts, anemia-related parameters, and significant increases in cardiac damage markers, troponin-I and NT-proBNP. Histopathological analysis revealed severe inflammation and necrosis at the injection site, decreased erythroid cells in bone marrow, cortical atrophy of the thymus, and increased spleen cellularity. While most toxicological changes observed at 2 dpsi had resolved by 14 dpsi, spleen enlargement and injection site damage persisted. Furthermore, repeated doses led to the accumulation of toxicity, and different administration routes resulted in distinct toxicological phenotypes. These findings highlight the potential toxicological risks associated with mRNA vaccines, emphasizing the necessity to carefully consider administration routes and dosage regimens in vaccine safety evaluations, particularly given the presence of bone marrow and immune organ toxicity, which, though eventually reversible, remains a serious concern.

Enhancement of skin longevity through TGF-β/Smad signaling pathway modulation by Rohu fish (Labeo rohita) collagen peptides in chronologically aged hairless mice - Hae Dun Kim; Yeok Boo Chang; Hyung Joo Suh; Sung Hee Han; Eun Yeong Jang; Eun Mi Sun; Hyung Shik Shin; Yejin Ahn (Food Bioscience, 2025)

Anode interface-stabilizing dry process employing a binary binder system for ultra-thick and durable battery electrode fabrication - Juhyun Lee; Chae Yeong Son; Seungmin Han; Subi Yang; Patrick Joohyun Kim; Dongsoo Lee; Jung Woo Lee; Won-Hee Ryu; Junghyun Choi (Chemical Engineering Journal, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Efficacy of Bone Regeneration Cell Therapy Using Mesenchymal Stem Cells Originating from Embryonic Stem Cells in Animal Models; Bone Defects and Osteomyelitis - Jin-Ho Park; Han-Sol Bae; Ingeun Kim; Jiwoon Jung; Yoonho Roh; Dongbin Lee; Tae Sung Hwang; Hee-Chun Lee; June-Ho Byun (Tissue Engineering and Regenerative Medicine, 2025)

Ship-based visual observation underestimates plastic debris in marine surface water - Yu Lee Jang; Soeun Eo; Gi Myung Han; Sung Yong Ha; Sang Hee Hong; Won Joon Shim (Marine Pollution Bulletin, 2024)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

Eco-friendly biocontrol of pine wilt disease: Enhancing tree defense with Bacillus subtilis JCK-1398 for sustainable forest management - Mohamed Mannaa; Ae ran Park; Jungwook Park; Hee Won Jeon; Hyejung Jung; Hyo Seong Jeon; Gil Han; Jin-Cheol Kim; Young-Su Seo (Science of The Total Environment, 2024)

Efficient cryopreservation of pear(Pyrus Spp.) germplasm by droplet-vitrification - Jae-Young Song; Ji-Won Han; Jinjoo Bae; Sung-Hee Nam; Ho-sun Lee; Ye-ji Lee; Ho Cheol Ko; Seok Cheol Kim; Byeong Hyeon Yun; Se Hee Kim (Cryobiology, 2024)

A Study on iPSC-Associated Factors in the Generation of Hepatocytes - Delger Bayarsaikhan; Govigerel Bayarsaikhan; Hyun A Kang; Su Bin Lee; So Hee Han; Teruo Okano; Kyungsook Kim; Bonghee Lee (Tissue Engineering and Regenerative Medicine, 2024)

Dynamics of Carbon Export and Lower Trophic Ecosystems: A Comparative Model Study in the Yellow Sea and Dokdo Waters - Young Shin Kwon; Hyoun-Woo Kang; Dong Han Choi; Ok Hee Seo (Ocean Science Journal, 2024)

Exogenous S1P via S1P receptor 2 induces CTGF expression through Src-RhoA-ROCK-YAP pathway in hepatic stellate cells - Suhyun Park; Jonghwa Kim; Sera Yang; So Hee Kang; Wonseok Kang; Yong-Han Paik (Molecular Biology Reports, 2024)

Comprehensive analysis of somatic mutations and structural variations in domestic pig - Seong Gyu Kwon; Geon Hue Bae; Joo Hee Hong; Jeong-Woo Choi; June Hyug Choi; Nam Seop Lim; CheolMin Jeon; Nanda Maya Mali; Mee Sook Jun; JaeEun Shin; JinSoo Kim; Eun-Seok Cho; et al. (Mammalian Genome, 2024)

Phocaeicola acetigenes sp. nov., producing acetic acid and iso-butyric acid, isolated faeces from a healthy human - Hyo Eun Do; Young Bong Ha; Ji-Sun Kim; Min Kuk Suh; Han Sol Kim; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; et al. (Antonie van Leeuwenhoek, 2024)

Deciphering the toxicity of polyhexamethylene guanidine phosphate in lung carcinogenesis: Mutational profiles and molecular mechanisms - Hong Lee; Sang Hoon Jeong; Yong-Wook Baek; Hyejin Lee; Jason K. Sa; Ji Yoon Lee; Yu-Seon Lee; Yoon Jeong Nam; Jaeyoung Kim; Jonghoon Kim; Jin Young Choi; Su A. Park; et al. (Chemosphere, 2024)

The impact of forest therapy on functional recovery after acute ischemic stroke - Sang-Hwa Lee; Jong-Hee Sohn; Joo Hye Sung; Sang-Won Han; Minwoo Lee; Yerim Kim; Jong Ho Kim; Jin Pyeong Jeon; Jae Jun Lee; Chulho Kim (Urban Forestry & Urban Greening, 2024)

2,7-Phloroglucinol-6,6′-bieckol from Ecklonia cava ameliorates nanoplastics-induced premature endothelial senescence and dysfunction - Hwan-Hee Sim; Saugat Shiwakoti; Ji-Hyeok Lee; In-Young Lee; Yejoo Ok; Han-Kyu Lim; Ju-Young Ko; Min-Ho Oak (Science of The Total Environment, 2024)

Dermal toxicity studies of 1,2-benzisothiazolin-3-one (CAS number: 2634-33-5) in Sprague-Dawley rats - Joon-Goo Lee; Muthuchamy Maruthupandy; ChulBeom Park; Seol-Hee Moon; Soyoung Yang; Misook Jung; Sun Hee Park; Beom Seok Han; Wan-Seob Cho (Food and Chemical Toxicology, 2024)

Daily and seasonal changes of sap flow in Gamhong apple cultivar and estimate the tree-level transpiration using Penman-Monteith reference evapotranspiration - Narayan Bhusal; Louis S. Santiago; Joncheon Lee; Sanghak Jeong; In Hee Park; Byeong-Ho Choi; Hun-Joong Kweon; Su-Gon Han; Tae-Myung Yoon (South African Journal of Botany, 2024)

Mechanistic insights into selenite and selenate immobilization using brucite-rich magnesium precipitate derived from seawater electrochlorination facility - Han Gyeol Jeon; Seonggyu Choi; Jin-Seok Kim; Kyung-Hee Lee; Jaegwan Shin; Kangmin Chon; Kyoung-Woong Kim; Sang-Ho Lee (Journal of Environmental Chemical Engineering, 2024)

The impact of sexual reproduction-induced vertical migration on the complexity of harmful algal blooms in Heterosigma akashiwo - Joo-Hwan Kim; Jin Ho Kim; Sae-Hee Kim; Yoon-Ho Kang; Jaeyoon Lee; Jae-Hyoung Joo; Myung-Soo Han; Bum Soo Park (Environmental Research, 2024)

Chemical optimization and derivatization of micrococcin p2 to target multiple bacterial infections: new antibiotics from thiopeptides - Jiyun Park; Dahyun Kim; Young-Jin Son; Marco A. Ciufolini; Shyaka Clovis; Minwoo Han; Lee-Han Kim; Sung Jae Shin; Hee-Jong Hwang (World Journal of Microbiology and Biotechnology, 2024)

Multi-archive record of late Quaternary paleoseismicity along the surface projection of the 2017 Pohang earthquake seismogenic fault, SE Korea - Seongjun Lee; Jong-Won Han; Sangmin Ha; Jeong-Heon Choi; Yeong Bae Seong; Tae-Ho Lee; Hee-Cheol Kang; Moon Son (Geosciences Journal, 2024)

Ambivalent effects of mass cultivation of biodiesel producible green alga Tetraselmis striata on a microbial ecosystem: Evidence from mesocosm experiments - Sae-Hee Kim; Jin Ho Kim; Joo-Hwan Kim; Pengbin Wang; Tae Gyu Park; Sangsuk Park; Yoon-Ho Kang; Myung-Soo Han; Bum Soo Park (Algal Research, 2024)

Variation of volatile compounds and sensory profile for Protaetia brevitarsis larvae fermented with lactic acid bacteria and yeast - Ji Yoon Cha; Jaejoon Han; JeongAe Heo; Hwan Hee Yu; Yea-Ji Kim; Hae Won Jang; Mi-Ran Kim; Yun-Sang Choi (Food Chemistry, 2024)

Sub-minute carbonization of polymer/carbon nanotube films by microwave induction heating for ultrafast preparation of hard carbon anodes for sodium-ion batteries - Gyeongbeom Ryoo; Jiwon Shin; Byeong Guk Kim; Do Geun Lee; Joong Tark Han; Byeongho Park; Youngseok Oh; Seung Yol Jeong; Se-Hee Lee; Dong Yun Lee; Daeho Kim; Jong Hwan Park (Chemical Engineering Journal, 2024)

Exosomal miR-196b secreted from bronchial epithelial cells chronically exposed to low-dose PM2.5 promotes invasiveness of adjacent and lung cancer cells - Seong-Lan Yu; Han Koo; Yujin Kang; Hye Jin Jeon; Minho Kang; Dong Hee Choi; Su Yel Lee; Ji Woong Son; Dong Chul Lee (Toxicology Letters, 2024)

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

Protective effects of Y-27632 against cisplatin-induced ototoxicity: A zebrafish model Y-27632 and cisplatin-induced ototoxicity - Kang Hyeon Lim; Saemi Park; Eunjung Han; Hee Soo Yoon; Yunkyoung Lee; Sumin Hong; Kyungtae Hyun; Seung Hwa Baek; Hyun woo Baek; Yoon Chan Rah; June Choi (Food and Chemical Toxicology, 2024)

Green process for Polyurethane: From CO2 to isocyanate - Jung Ae Lim; Young-Woo You; Seung Kwon Kang; Jongseon Rho; Suyeon Yeo; Seulgi Han; Mintaek Im; Un Young Kim; Min-Chul Kim; Tae-Sun Chang; Ji Hoon Park; Jinjoo An; et al. (Chemical Engineering Journal, 2024)

High-Resolution Melting (HRM) analysis of DNA methylation using semiconductor chip-based digital PCR - Jinuk Jeong; Yongsu Yang; Min-Sik Song; Hee-Young Won; Andrew T. Han; Songmi Kim (Genes & Genomics, 2024)

Forecast accuracy and physics sensitivity in high-resolution simulations of precipitation events in summer 2022 by the Korean Integrated Model - Eun-Hee Lee; Sujeong Cho; Keon-Hee Cho; Ji-Young Han; Youngsu Lee; Junghan Kim (Asia-Pacific Journal of Atmospheric Sciences, 2024)
The precipitation prediction of the Korean Integrated Model (KIM) is evaluated over South Korea for the summer season of July–August 2022, and key factors for accurate predictions are examined using various approaches, including case studies under distinct synoptic patterns and physics sensitivity experiments. In this study, a five-day prediction experiment was conducted using the latest version of KIM in a near real-time full cycle configuration with 8-km grid spacing, while additional case simulations and prediction tests were conducted on low-resolution or cold-run testbeds. For verification, a newly designed synoptic pattern verification was introduced to assist to the conventional dichotomous verification for daily precipitation. It was found that heavy rainfall events over South Korea are determined by two dominant patterns: frontal and cyclonic. KIM can successfully discriminate between synoptic patterns with a detection rate of approximately 85% for these two types within a short-range prediction. However, it is evident that the precise prediction of precipitation requires an accurate location of the precipitation system within a specified timeframe, wherein KIM shows weakness in delaying the movement of extratropical cyclones with forecast lead times. The significance of moist physics is also highlighted by sensitivity experiments that control convective trigger conditions. This demonstrates that large-scale precipitation from a microphysics scheme must be enhanced to properly represent the strong development of inland rain systems over South Korea, which are highly sensitive to convective precipitation activity in the numerical model, especially in upwind ocean regions.

Covalent organic polymer/chitosan multifunctional granular aerogels for diclofenac sodium removal from water - Seenu Ravi; Hyug Hee Han; Yujin Choi; Haryeong Choi; Hyung-Ho Park; Youn-Sang Bae (Chemical Engineering Journal, 2024)

Transcriptome sequencing of the endangered land snail Karaftohelix adamsi from the Island Ulleung: De novo assembly, annotation, valuation of fitness genes and SSR markers - Jie Eun Park; Bharat Bhusan Patnaik; Min Kyu Sang; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hongray Howrelia Patnaik; Hee Ju Hwang; So Young Park; et al. (Genes & Genomics, 2024)

MicroRNA 429 regulates MMPs expression by modulating TIMP2 expression in colon cancer cells and inflammatory colitis - Seol-Hee Han; Ji-Su Mo; Ki-Jung Yun; Soo-Cheon Chae (Genes & Genomics, 2024)

DNA repair-retarded isothermal CRISPR amplification for rapid, sensitive base excision repair enzyme assay - Hyogu Han; Se Hee Jang; Jun Ki Ahn; Chang Yeol Lee (Analytica Chimica Acta, 2024)

Fabrication of smart film based on fish gelatin incorporating phycoerythrin and cellulose nanofibrils to monitor fish freshness - Md Sadek Ali; Truc Cong Ho; Jin-Seok Park; Ji-Min Han; Duraiarasan Surendhiran; Hee-Jeong Lee; Wei Zhang; Byung-Soo Chun (Food Bioscience, 2024)

Corrigendum to “Physicochemical and in-vitro release characteristics of vitamin C-loaded antioxidant orally disintegrating films with different catechin levels” [Food Bioscience 53 (2023) /102733] - Hejeong Shin; Jin-Hee Chang; Jung-Ah Han (Food Bioscience, 2024)

Preliminary Estimation of Protist Predation Potential on Picoplankton in Summer of the Yellow Sea - Young-Ok Kim; Mutsuo Ichinomiya; Jungmin Choi; Dong Han Choi; Wonseok Yang; Kyung-Hee Oh; Kongtae Ra; Howon Lee (Ocean Science Journal, 2024)

New insights on seismic activity in the southeastern Korean Peninsula from the Gyeongju Hi-density Broadband Seismic Network (GHBSN) - Dabeen Heo; Tae-Seob Kang; Minook Kim; Byeong Seok Ahn; Hobin Lim; Jaeseoung Han; Kwang-Hee Kim; Junkee Rhie; YoungHee Kim; Jin-Han Ree (Geosciences Journal, 2024)

Benzyl-methylbenzyl-benzene: Improving hydrogen storage and release performance of dibenzyltoluene based liquid organic hydrogen carrier - Kwanyong Jeong; Hyunwoo Yook; So Hyeon Lee; Hwa Jin Han; Yunkyeong Jung; Seulgi Han; So Yeon Shin; Myungho Choi; Sunil Kwon; Jin Hee Lee; Sang-Joon Kim; Soo Min Kim; et al. (Chemical Engineering Journal, 2024)

An electro-ferroptotic nanoammunition enables image-guided, spatiotemporally controlled cancer ferroptosis induction via irreversible electroporation - Jun-Hyeok Han; Hee Seung Seo; Jiyoung Lee; Zheng Chen; Qiyue Wang; Yun Young Lee; Na Kyeong Lee; Jeon Min Kang; Song Hee Kim; Hwichan Hong; Jung-Hoon Park; Yuanzhe Piao; et al. (Chemical Engineering Journal, 2024)

Validation of a new risk stratification system-based management for methicillin-resistant Staphylococcus aureus bacteraemia: analysis of a multicentre prospective study - Taeeun Kim; Sang-Rok Lee; Seong Yeon Park; Song Mi Moon; Jiwon Jung; Min Jae Kim; Heungsup Sung; Mi-Na Kim; Sung-Han Kim; Sang-Ho Choi; Sang-Oh Lee; Yang Soo Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Does more information mean better choices? A study on calorie display and consumer behavior in restaurants - Dae Hee Chung; Doo Bong Han; Rodolfo M. Nayga Jr.; Sang Hyeon Lee (Food Quality and Preference, 2024)

Occurrence and health risk assessment of tropane alkaloids in cereal foods consumed in Korea - Songyi Han; Sukyeong Jang; Sujin Oh; Jian Lee; Hwa-Jeong Lee; Yong Eui Koo; Byung Hee Kim (Food and Chemical Toxicology, 2024)

Morphology and phylogenetic relationships of two Antarctic strains within the genera Carolibrandtia and Chlorella (Chlorellaceae, Trebouxiophyceae) - Hyunsik Chae; Eun Jae Kim; Han Soon Kim; Han-Gu Choi; Sanghee Kim; Ji Hee Kim (Algae, 2024)

In vitro callus induction and growth for medicinal use of an endangered Korean native plant, Glochidion chodoense C. S. Lee & H. T. Im - Jin-Ho Kim; Hae Lim Kim; Sea-Hee Han; Hwa Lee; Jong-Eun Han; Tea-Su Kim; Su Hui Seong; Bo-Ram Kim; Ha-Nul Lee; Chan Seo; Jung Eun Kim; Sua Im; et al. (Rhizosphere, 2024)

Angular dihydropyranocoumarins from the flowers of Peucedanum japonicum and their aldo-keto reductase inhibitory activities - Jisu Park; Trung Huy Ngo; Sunil Babu Paudel; Yun-Seo Kil; Ga-Hee Ryoo; Chang Hyun Jin; Hong-Il Choi; Chan-Hun Jung; MinKyun Na; Joo-Won Nam; Ah-Reum Han (Phytochemistry, 2024)

High-performance interfacial water evaporation of black TiO2-x with high-concentration bulk oxygen vacancies - Myeongjun Ji; Jeong Hyun Kim; Hee Yeon Jeon; Seungheon Han; Dong Hoon Lee; Young-In Lee (Chemical Engineering Journal, 2024)

Rigid amine-incorporated silica aerogel for highly efficient CO2 capture and heavy metal removal - Haryeong Choi; Hyug Hee Han; Vinayak G. Parale; Taehee Kim; Wanje Park; Younghun Kim; Jiseung Kim; Yujin Choi; Youn-Sang Bae; Hyung-Ho Park (Chemical Engineering Journal, 2024)

Gordonibacter faecis sp. nov., producing urolithin C from ellagic acid, isolated from feces of healthy Korean subjects - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Hyo Eun Do; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2024)

The effect of weathering on cohesion in granitic fault rocks: A case study from the Yeongdeok Fault, South Korea - Jae Hoon Kim; Jin-Han Ree; Wataru Tanikawa; Hee-Cheol Kang (Journal of Structural Geology, 2024)

Hazardous chemical additives within marine plastic debris and fishing gear: Occurrence and implications - Mi Jang; Won Joon Shim; Youna Cho; Gi Myung Han; Sung Yong Ha; Sang Hee Hong (Journal of Cleaner Production, 2024)

Diisobutyl phthalate (DiBP)-induced male germ cell toxicity and its alleviation approach - Seok-Man Kim; Yong-Hee Kim; Gil Un Han; Seul Gi Kim; Dong Ha Bhang; Byung-Gak Kim; Sung-Hwan Moon; Seung Hee Shin; Buom-Yong Ryu (Food and Chemical Toxicology, 2024)

High C2H6/C2H4 selectivity via incorporation of dense methyl groups into a stable Zr-based MOF with cavity-like pores - Wanje Park; Tea-Hoon Kim; Kwang Hyun Oh; Hyug Hee Han; Yujin Choi; Kijun Kim; Youn-Sang Bae (Chemical Engineering Journal, 2024)

Establishment and Characterization of a Skeletal Muscle-Derived Myogenic Cell Line from Black Sea Bream (Acanthopagrus schlegelii) - Dan Hee Han; Seung Pyo Gong (Journal of Marine Science and Engineering, 2024)
Establishing muscle lineage cell lines from fish will provide a great opportunity to study muscle development, which can eventually contribute to the improvement of the fish quality in the aquaculture industry. However, there has been a lack of the development of proper fish muscle lineage cell lines so far. Here, we report the establishment of a skeletal muscle-derived myogenic cell line from black sea bream (Acanthopagrus schlegelii). For this, we first attempted to find the optimal conditions for the primary explant culture of A. schlegelii muscle tissues and then established muscle-derived cell lines. After that, cell lines were characterized for their muscle-specific gene expression, growth, and myogenic differentiation. We found that the primary explant culture was effective when the tissue fragments were cultured in Dulbecco’s Modified Eagle Medium supplemented with fetal bovine serum and antibiotics on gelatin-coated dishes. Additionally, we confirmed that the addition of basic fibroblast growth factor was necessary to establish the cell lines. One of three cell lines established was capable of long-term culture, expressed three major myogenic regulatory genes including Pax7, MyoD, and Myog, and differentiated to myotubes in the condition using low concentration of horse serum, demonstrating that this cell line was a skeletal muscle-derived myogenic cell line.

Isolation of a quorum quenching bacterium effective to various acyl-homoserine lactones: Its quorum quenching mechanism and application to a membrane bioreactor - Soyoung Ham; Hwa-Soo Ryoo; Yongsun Jang; Sang-Hoon Lee; Ji-Yoon Lee; Han-Shin Kim; Jeong-Hoon Lee; Hee-Deung Park (Chemosphere, 2024)

Synergistic effect of climate change and water management: Historical and future soil salinity in the Kur-Araz lowland, Azerbaijan - Junho Han; Minhee Kim; Zaman Mammadov; Seoyeon Lee; Evert J. Elzinga; Garib Mammadov; Wonjae Hwang; Hee-Myong Ro (Science of The Total Environment, 2024)

Environmental forensics approach to source investigation in a mercury contaminated river: Insights from mercury stable isotopes - Young Gwang Kim; Sae Yun Kwon; Spencer J. Washburn; Yongseok Hong; Seung Hee Han; Mikyung Lee; Ji Hyoung Park (Journal of Hazardous Materials, 2024)

Kaempferol induces apoptosis through the MAPK pathway and regulates JNK-mediated autophagy in MC-3 cells - Su-Ji Jeon; Gi-Hwan Jung; Eun-Young Choi; Eun-Ji Han; Jae-Han Lee; So-Hee Han; Joong-Seok Woo; Soo-Hyun Jung; Ji-Youn Jung (Toxicological Research, 2024)

Morphology and phylogenetic relationships of two Antarctic strains within the genera Carolibrandtia and Chlorella (Chlorellaceae, Trebouxiophyceae) - Hyunsik Chae; Eun Jae Kim; Han Soon Kim; Han-Gu Choi; Sanghee Kim; Ji Hee Kim (Algae, 2023)
The genera Carolibrandtia and Chlorella have been described as small green algae with spherical cell shapes that inhabit various environments. Species of these genera are often difficult to identify because of their simple morphology and high phenotypic plasticity. We investigated two small coccoid strains from Antarctica based on morphology, molecular phylogeny by two alignment methods which have been applied to previous phylogenetic studies of the genus Chlorella, and comparison of the secondary structures of nuclear small subunit (SSU) and internal transcribed spacer (ITS) rDNA sequences. Light microscopy of two strains revealed spherical cells containing chloroplasts with pyrenoids, and the morphological characteristics of the strains were nearly identical to those of other Chlorella species. However, based on the phylogenetic analyses of nuclear SSU and ITS rDNA sequences, it was determined that the Antarctic microalgal strains belonged to two genera, as the Chlorella and Carolibrandtia. In addition, the secondary structures of the SSU and ITS2 sequences were analyzed to detect compensatory base changes (CBCs) that were used to identify and describe the two strains. A unique CBC in the SSU rDNA gene was decisive for distinguishing strain CCAP 211/45. The ITS2 rDNA sequences for each strain were compared to those obtained previously from other closely related species. Following the comparison of morphological and molecular characteristics, we propose KSF0092 as a new species, Chlorella terrestris sp. nov., and the reassignment of the strain Chlorella antarctica CCAP 211/45 into Carolibrandtia antarctica comb. nov.

Micro-grinding–based production for sulforaphene-enriched radish seeds extract via facilitating glucosinolates-myrosinase reaction, and evaluation of its anti-adipogenic effects - Tae Kyung Lee; Gihyun Hur; Jong Hun Kim; Jung Han Yoon Park; Hee Yang; Ki Won Lee (Food Chemistry, 2023)

Investigating the different transformations of tetracycline using birnessite under different reaction conditions and various humic acids - Hang Vo-Minh Nguyen; Doo-Hee Lee; Han-Saem Lee; Hyun-Sang Shin (Environmental Pollution, 2023)

Cell death induction and intracellular vesicle formation in human colorectal cancer cells treated with Δ9-Tetrahydrocannabinol - Yu-Na Hwang; In-Seo Kwon; Ju-Hee Park; Han-Heom Na; Tae-Hyung Kwon; Jin-Sung Park; Keun-Cheol Kim (Genes & Genomics, 2023)
Background Δ 9 -Tetrahydrocannabinol (Δ 9 -THC) is a principal psychoactive extract of Cannabis sativa and has been traditionally used as palliative medicine for neuropathic pain. Cannabidiol (CBD), an extract of hemp species, has recently attracted increased attention as a cancer treatment, but Δ 9 -THC is also requiring explored pharmacological application. Objective This study evaluated the pharmacological effects of Δ 9 -THC in two human colorectal cancer cell lines. We investigated whether Δ 9 -THC treatment induces cell death in human colorectal cancer cells. Methods We performed an MTT assay to determine the pharmacological concentration of Δ 9 -THC. Annxein V and Western blot analysis confirmed that Δ 9 -THC induced apoptosis in colorectal cancer cells. Metabolic activity was evaluated using MitoTracker staining and ATP determination. We investigated vesicle formation by Δ 9 -THC treatment using GW9662, known as a PPARγ inhibitor. Results The MTT assay showed that treatment with 40 μM Δ 9 -THC and above inhibited the proliferation of colorectal cancer cells. Multiple intracytoplasmic vesicles were detected upon microscopic observation, and fluorescence-activated cell sorting analysis showed cell death via G1 arrest. Δ 9 -THC treatment increased the expression of cell death marker proteins, including p53, cleaved PARP-1, RIP1, and RIP3, suggesting that Δ 9 -THC induced the death of colorectal cancer cells. Δ 9 -THC treatment also reduced ATP production via changes in Bax and Bcl-2. Δ 9 -THC regulated intracytoplasmic vesicle formation by modulating the expression of PPARγ and clathrin, adding that antiproliferative activity of Δ 9 -THC was also affected. Conclusion In conclusion, Δ 9 -THC regulated two functional mechanisms, intracellular vesicle formation and cell death. These findings can help to determine how cannabinoids can be used most effectively to improve the efficacy of cancer treatment.

Biofloc Application Using Aquaponics and Vertical Aquaculture Technology in Aquaculture: Review - Young-Bin Yu; Jae-Ho Choi; Ju-Hyeong Lee; A-Hyun Jo; Sung Won Han; Song-Hun Han; Hee Jae Choi; Cheol Young Choi; Ju-Chan Kang; EunYoung Min; Jun-Hwan Kim (Fishes, 2023)
Some aspects of traditional aquaculture have negative impacts on the aquatic environment, leading to pollution and disease outbreaks in farmed organisms. Biofloc technology (BFT) is a closed aquaculture system that utilizes specific microbial communities to remove ammonia emitted from aquaculture organisms or adds carbon to the aquaculture system to improve water quality. BFT has benefits, such as increasing production and improving water quality, and reducing disease spread and pollution, without the need for water exchange. However, there are disadvantages, such as rapid changes in water quality due to accumulation of dissolved nutrients and total suspended soils (TSS) and the requirement for expensive aeration equipment to maintain dissolved oxygen. BFT can be enhanced in value and efficiency by combining it with other aquaculture technologies, such as aquaponics and vertical aquaculture to overcome the disadvantages. The integration of biofloc with technologies from the fourth industrial revolution holds potential for further development, while aquaponics and vertical farming can eliminate geographical limitations and accelerate the urbanization of aquaculture. The integration of aquaponics and vertical aquaculture with BFT has potential for development, accelerating the urbanization of aquaculture and removing geographic limitations.

Behavior of lightweight-foamed soil reinforced by waste fishing net and its design guideline - Jinung Do; Sun-Bin Kim; Taek-Hee Han; Gil-Lim Yoon (Marine Georesources & Geotechnology, 2023)

Airborne hyperspectral imaging for early diagnosis of kimchi cabbage downy mildew using 3D-ResNet and leaf segmentation - Lukas Wiku Kuswidiyanto; Pingan Wang; Hyun-Ho Noh; Hee-Young Jung; Dae-Hyun Jung; Xiongzhe Han (Computers and Electronics in Agriculture, 2023)

Intra-annual variation in microplastics in mussels (Mytilus galloprovincialis) inhabiting an urbanized bay of South Korea - Jongwook Jeong; Won Joon Shim; Youna Cho; Gi Myung Han; Mi Jang; Sang Hee Hong (Marine Pollution Bulletin, 2023)

In situ electrolyte replenishment with atmospheric pressure-chemical/electrochemical vapour deposition for molten carbonate fuel cells - Kab In Kim; Jae Kwan Bae; Emilio Audasso; Albert Won Cho; Young Bae Jun; Hyun Seo Park; Seong-Cheol Jang; Yong Soo Cho; Han Sung Kim; Sun-Hee Choi; Sung Pil Yoon (Chemical Engineering Journal, 2023)

Corrigendum to “Physicochemical and in-vitro release characteristics of vitamin C-loaded antioxidant orally disintegrating films with different catechin levels” [Food Biosci. 53 (2023) 102733] - Hye-Jung Shin; Jin-Hee Chang; Jung-Ah Han (Food Bioscience, 2023)

Thermal performance design and analysis method for energy cast-in-place piles (E-CIPs) installed in diaphragm walls - Seokjae Lee; Taek Hee Han; Sangwoo Park; Chaemin Hwang; Hangseok Choi (Energy and Buildings, 2023)

Two weeks dose range-finding and four weeks repeated dose oral toxicity study of a novel reversible monoamine oxidase B inhibitor KDS2010 in cynomolgus monkeys - Kyung-Tai Kim; Doo-Wan Cho; Jae-woo Cho; Wan-Jung Im; Da-Hee Kim; Jong-Hyun Park; Ki Duk Park; Young-Su Yang; Su-Cheol Han (Toxicological Research, 2023)

Field application of biologically derived substances (BDSs: Naphthoquinone derivative) for eco-friendly mitigation of harmful cyanobacterial blooms - Jae-Hyoung Joo; Yoon-Ho Kang; Zhun Li; Sae-Hee Kim; Bum Soo Park; Myung-Soo Han (Journal of Applied Phycology, 2023)

The effects of environmental Microplastic on wharf roach (Ligia exotica): A Multi-Omics approach - Youmi Choi; Dongju Shin; Chang Pyo Hong; Dong-Min Shin; Sung-Hee Cho; Seong Soon Kim; Myung Ae Bae; Sang Hee Hong; Mi Jang; Youna Cho; Gi Myung Han; Won Joon Shim; et al. (Chemosphere, 2023)

Spatial distribution and historical trend of microplastic pollution in sediments from enclosed bays of South Korea - Soeun Eo; Sang Hee Hong; Youna Cho; Young Kyoung Song; Gi Myung Han; Won Joon Shim (Marine Pollution Bulletin, 2023)

Directed charge boosting by polyelectrolyte nanorods on a graphene oxide membrane for High-Performance blue energy harvesting - Ki Hyun Lee; Hyeonhoo Lee; Woojae Jeong; Tae Hee Han (Chemical Engineering Journal, 2023)

A review of the endangered mollusks transcriptome under the threatened species initiative of Korea - Hongray Howrelia Patnaik; Min Kyu Sang; Jie Eun Park; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hee Ju Hwang; So Young Park; Se Won Kang; et al. (Genes & Genomics, 2023)

Competitive formation of NO, NO2, and O3 in an air-flowing plasma reactor: A central role of the flow rate - Jinwoo Kim; Hyungyu Lee; Seong-Cheol Huh; Jin Hee Bae; Wonho Choe; Duksun Han; Seungil Park; Seungmin Ryu; Sanghoo Park (Chemical Engineering Journal, 2023)

Breast Tissue Reconstruction Using Polycaprolactone Ball Scaffolds in a Partial Mastectomy Pig Model - Kyu-Sik Shim; Da Hye Ryu; Han-Saem Jo; Ki-Bum Kim; Do-Hyun Kim; Yong-Kyu Park; Min Heo; Hee-Eun Cho; Eul-Sik Yoon; Won Jai Lee; Tai Suk Roh; Seung Yong Song; et al. (Tissue Engineering and Regenerative Medicine, 2023)

A comparative study on the implementation of deep learning algorithms for detection of hepatic necrosis in toxicity studies - Ji-Hee Hwang; Minyoung Lim; Gyeongjin Han; Heejin Park; Yong-Bum Kim; Jinseok Park; Sang-Yeop Jun; Jaeku Lee; Jae-Woo Cho (Toxicological Research, 2023)
Deep learning has recently become one of the most popular methods of image analysis. In non-clinical studies, several tissue slides are generated to investigate the toxicity of a test compound. These are converted into digital image data using a slide scanner, which is then studied by researchers to investigate abnormalities, and the deep learning method has been started to adopt in this study. However, comparative studies evaluating different deep learning algorithms for analyzing abnormal lesions are scarce. In this study, we applied three algorithms, SSD, Mask R-CNN, and DeepLabV3 + , to detect hepatic necrosis in slide images and determine the best deep learning algorithm for analyzing abnormal lesions. We trained each algorithm on 5750 images and 5835 annotations of hepatic necrosis including validation and test, augmented with 500 image tiles of 448 × 448 pixels. Precision, recall, and accuracy were calculated for each algorithm based on the prediction results of 60 test images of 2688 × 2688 pixels. The two segmentation algorithms, DeepLabV3 + and Mask R-CNN, showed over 90% of accuracy (0.94 and 0.92, respectively), whereas SSD, an object detection algorithm, showed lower accuracy. The trained DeepLabV3 + outperformed all others in recall while also successfully separating hepatic necrosis from other features in the test images. It is important to localize and separate the abnormal lesion of interest from other features to investigate it on a slide level. Therefore, we suggest that segmentation algorithms are more appropriate than object detection algorithms for use in the pathological analysis of images in non-clinical studies.

Morpho-physiological and genetic characteristics of a salt-tolerant mutant line in soybean (Glycine max L.) - Chang Yeok Moon; Byeong Hee Kang; Woon Ji Kim; Sreeparna Chowdhury; Sehee Kang; Jeong-Dong Lee; Soon-Jae Kwon; Han-Yong Kim; Hyeon-Seok Lee; Bo-Keun Ha (Theoretical and Applied Genetics, 2023)

Hongjam prevents hepatic damage against ethanol-induced fatty liver disease in rats - Da-Young Lee; Moon-Young Song; Young-Min Han; Eun-Hee Kim (Journal of Asia-Pacific Entomology, 2023)

Physicochemical and in-vitro release characteristics of vitamin C-loaded antioxidant orally disintegrating films with different catechin levels - Hye-Jung Shin; Jin-Hee Chang; Jung-Ah Han (Food Bioscience, 2023)

Stevia extract enhances the fermentation and functional properties of fermented milk in human colon epithelial cells - Do Hyun Kim; Chang Hee Jeong; Seo Gu Han; Hyun Su Jung; Sung Gu Han (Food Bioscience, 2023)

Analysis of volatile compounds of several rice varieties according to endosperm type using an electronic nose - Chae-Min Han; Jong-Hee Shin; Sang-Kuk Kim; Jung-Gi Ryu (Journal of Crop Science and Biotechnology, 2023)

Anti-oviposition and repellence of Cordyceps fumosorosea against Spodoptera exigua - Roland Bocco; Hye Ju Jeong; Ji Hee Han; Dayeon Kim; Seongho Ahn; Sang Yeob Lee (International Journal of Tropical Insect Science, 2023)
Anti-oviposition induced by Cordyceps fumosorosea FG340 to Spodoptera exigua and its persistence had been assessed on the Chinese cabbage seedlings sprayed with 0, 10 6 , 10 7 and 10 8 conidia per mL in greenhouse and laboratory. In a randomized complete block, four couples (males and females) of moths were released in each cage. In the laboratory, the percentage of egg laid varied significantly between treatments with 59.8, 14.8, 11.9, and 13.5% on 0, 10 6 , 10 7 and 10 8 conidia per mL; respectively. Similarly, in the greenhouse, the percentage of eggs laid differed significantly between suspensions with 88.18, 8.7, 0, and 3.13% on 0, 10 6 , 10 7 , and 10 8 conidia per mL; respectively. Repellence study showed that there is a major difference between suspensions with average 34.55, 35.21 and 40.02% for 10 6 , 10 7 and 10 8 conidia per mL; respectively. Endophytic C. fumosorosea and its culture fluid affect the behavior of armyworm larvae. The concentration of 10 8 conidia per mL can affect the oviposition of the armyworm.

Systematic tracing of nitrate sources in a complex river catchment: An integrated approach using stable isotopes and hydrological models - Seung-Hee Kim; Dong-Hun Lee; Min-Seob Kim; Han-Pil Rhee; Jin Hur; Kyung-Hoon Shin (Water Research, 2023)

Inhibiting bacterial biofilm formation by stimulating c-di-GMP regulation using citrus peel extract from Jeju Island - Han-Shin Kim; So-Young Ham; Hwa-Soo Ryoo; Do-Hyung Kim; Eun-Tae Yun; Hee-Deung Park; Jeong-Hoon Park (Science of The Total Environment, 2023)

Corrigendum to “Blue light irradiation exerts anti-viral and anti-inflammatory properties against herpes simplex virus type 1 infection” [Journal of Photochemistry and Photobiology B: Biology Volume 239 (2023) 112632] - Phil-Sun Oh; Yeon-Hee Han; SeokTae Lim; Hwan-Jeong Jeong (Journal of Photochemistry and Photobiology B: Biology, 2023)

Modified viologen-assisted reversible bromine capture and release in flowless zinc–bromine batteries - Seung Hee Han; Seoyoung Kim; Hyeong Yong Lim; Sewon Park; Kyungjae Shin; Seungwon Kim; Hee-Tak Kim; Sang Kyu Kwak; Changduk Yang; Nam-Soon Choi (Chemical Engineering Journal, 2023)

Development of a long-acting tablet with ticagrelor high-loaded nanostructured lipid carriers - Minwoo Jung; Minki Jin; Woo-Jin Jeon; HaeSoo Lee; Haeun Kim; Jong-Hee Won; Hyelim Yoo; Hyoung-Woo Bai; Su-Cheol Han; Hearan Suh; Kyoung Un Kang; Hong-Ki Lee; et al. (Drug Delivery and Translational Research, 2023)

Inverse opal-structured all-in-one water purification filter designed for the effective removal of multi-pollutants - Hee Jung Kim; Gill Sang Han; Jaesung Kim; Young Ju Kim; Jin Hyuk Choi; Jae Myeong Lee; Geon Woo Yoon; Hongshin Lee; In Sun Cho; Jaesang Lee; Hyun Suk Jung (Journal of Water Process Engineering, 2023)

Fermentative features of Bacillus velezensis and Leuconostoc mesenteroides in doenjang-meju, a Korean traditional fermented soybean brick - Dong Min Han; Ju Hye Baek; Byung Hee Chun; Che Ok Jeon (Food Microbiology, 2023)

Correction to: TGFβ1-Induced Transglutaminase-2 Triggers Catabolic Response in Osteoarthritic Chondrocytes by Modulating MMP-13 - Jae-Young Park; Hyun Cheol Bae; Sung Hee Pyo; Myung Chul Lee; Hyuk-Soo Han (Tissue Engineering and Regenerative Medicine, 2023)

Matrix Metalloproteinase 1 as a Marker of Tonsil-Derived Mesenchymal Stem Cells to Assess Bone Marrow Cell Migration - Hee-Yeon Kim; Hee-Soo Yoon; Younghay Lee; Yu-Hee Kim; Kyung-Ah Cho; So-Youn Woo; Han Su Kim; Kyung-Ha Ryu; Joo-Won Park (Tissue Engineering and Regenerative Medicine, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

Microplastic emission characteristics of stormwater runoff in an urban area: Intra-event variability and influencing factors - Youna Cho; Won Joon Shim; Sung Yong Ha; Gi Myung Han; Mi Jang; Sang Hee Hong (Science of The Total Environment, 2023)

Exploring the nexus between food and veg*n lifestyle via text mining-based online community analytics - Ra Yoo; Seo-Young Kim; Do-Hee Kim; Jiyoung Kim; Ye Ji Jeon; Jung Han Yoon Park; Ki Won Lee; Hee Yang (Food Quality and Preference, 2023)

A Biological Indication of Vertical Mixing of the Yellow Sea Bottom Cold Water - Young Ok Kim; Jungmin Choi; Dong Han Choi; Kyung-Hee Oh (Ocean Science Journal, 2023)

Complete genome of Nakamurella sp. PAMC28650: genomic insights into its environmental adaptation and biotechnological potential - Lakshan Paudel; Nisha Ghimire; So-Ra Han; Hyun Park; Sang-Hee Jung; Tae-Jin Oh (Functional & Integrative Genomics, 2023)
The mechanisms underlying the survival of bacteria in low temperature and high radiation are not yet fully understood. Nakamurella sp. PAMC28650 was isolated from a glacier of Rwenzori Mountain, Uganda, which species belonged to Nakamurella genus based on 16S rRNA phylogeny, ANI (average nucleotide identity), and BLAST Ring Image Generator (BRIG) analysis among Frankineae suborder. We conducted the whole genome sequencing and comparative genomics of Nakamurella sp. PAMC28650, to understand the genomic features pertaining to survival in cold environment, along with high UV (ultraviolet) radiation. This study highlights the role of polysaccharide in cold adaptation, mining of the UV protection-related secondary metabolites and other related to cold adaptation mechanism through different bioinformatics tools, and providing a brief overview of the genes present in DNA repair systems. Nakamurella sp. PAMC28650 contained glycogen and cellulose metabolism pathways, mycosporine-like amino acids and isorenieratene-synthesizing gene cluster, and a number of DNA repair systems. Also, the genome analysis showed osmoregulation-related genes and cold shock proteins. We infer these genomic features are linked to bacterial survival in cold and UV radiation.

“Coastal Dynamics, Hazards, and Numerical Modelling” in Memory of Prof. Byung Ho Choi - Han Soo Lee; Kyeong Ok Kim; Jin-Hee Yuk; Seung-Buhm Woo; Youngjin Choi (Journal of Marine Science and Engineering, 2023)
This Special Issue is dedicated to Prof Byung Ho Choi at SungKyunKwan University, South Korea [...]

Differential modes of response to zinc chloride in the marine rotifers Brachionus plicatilis and Brachionus rotundiformis: Reproductive flexibility and stress-defensive activity - Chengyan Han; Hee-Jin Kim; Jae-Seong Lee; Yoshitaka Sakakura; Atsushi Hagiwara (Aquaculture, 2023)

Blue light irradiation exerts anti-viral and anti-inflammatory properties against herpes simplex virus type 1 infection - Phil-Sun Oh; Yeon-Hee Han; SeokTae Lim; Hwan-Jeong Jeong (Journal of Photochemistry and Photobiology B: Biology, 2023)

Bed configurations in CO vacuum pressure swing adsorption process for basic oxygen furnace gas utilization: Experiment, simulation, and techno-economic analysis - Hyunmin Oh; Hee Tae Beum; Suh-Young Lee; Jinsu Kim; Jungil Kim; Yongju Yun; Sang Sup Han (Chemical Engineering Journal, 2023)

Attached Macroinvertebrates Inhabiting Marine Plastic Debris from the Beach and Port Areas of the Southern Sea of Korea - Gwan Hee Han; Sang Lyeol Kim; Su Min Kang; Hyung-Gon Lee; Ok Hwan Yu (Journal of Marine Science and Engineering, 2023)
The increasing amount of marine plastic debris (MPD) poses risks of ingestion, entanglement, and transport of alien species. A new ecosystem called the “plastisphere” is currently being studied, but relevant research on it is limited. In this study, we analyzed the frequency of appearance of macroinvertebrate species on MPD. Macroinvertebrates attached to MPD were collected once every three months from March to December 2021 in eight regions. MPD in the form of aquaculture and fishing gear was detected most frequently during the study. In total, two phyla, 14 orders, 19 families, and 41 species of attached macroinvertebrates were detected during the study. There were more attached macroinvertebrate species, and they were more frequent, on fishing/aquaculture MPD (sea origin) than packaging MPD (land origin). Most fishing/aquaculture MPD is made of softer or rougher materials than packaging MPD and has a longer exposure time in the sea. In particular, the alien species Mytilus galloprovincialis was found on all longer-exposure MPD. These findings suggest that the macroinvertebrates attached to MPD are affected by the duration of exposure to the water and the characteristics of the MPD material. Therefore, in the future, fishing/aquaculture MPD could be used as an indicator for monitoring MPD-attached organisms.

Species Diversity and Community Structure of Macrobenthos in the Ulleung Basin, East Sea, Republic of Korea - Sang Lyeol Kim; Su Min Kang; Hyung Gon Lee; Gwan Hee Han; Ok Hwan Yu (Journal of Marine Science and Engineering, 2023)
The Ulleung Basin of the East Sea is a biological hotspot, but studies on the macrobenthos therein are lacking. To evaluate the macrobenthos species diversity and community structure in the Ulleung Basin, we conducted a survey from 2017 to 2021. A total of 262 species of macrobenthos was detected by the survey, and the average habitat density was 243 individuals/m2. The average biomass of macrobenthos was 43.7 g/m2, and the average Shannon and Wiener’s diversity index was 2.3 (0.69–3.61). The dominant species were the polychaetes Terebellides horikoshii, Chaetozone setosa, Scalibregma inflatum, and Aglaophamus sp. and the bivalvia Axinopsida subquadrata. The community structure of macrobenthos differed according to water depth, and a correlation analysis using environmental variables showed that the community was affected by water temperature, salinity, and dissolved oxygen. The macrobenthic fauna in the Ulleung Basin was greatly influenced by water depth, the sedimentary environment was different, and the dominant species were also different. In addition, there was little seasonal change compared to the East Sea coast. Our findings will facilitate further investigation of benthic ecosystems throughout the East Sea.

E2F4 regulates cell cycle to mediate embryonic development in pigs - Wen-Jie Jiang; Ming-Hong Sun; Xiao-Han Li; Song-Hee Lee; Geun Heo; Dongjie Zhou; Xiang-Shun Cui (Theriogenology, 2023)

Plastic debris as a mobile source of additive chemicals in marine environments: In-situ evidence - Mi Jang; Won Joon Shim; Gi Myung Han; Youna Cho; Sang Hee Hong (Science of The Total Environment, 2023)

Association of long-term exposure to PM2.5 and survival following ischemic heart disease - Jongmin Oh; Sangbum Choi; Changwoo Han; Dong-Wook Lee; Eunhee Ha; Soontae Kim; Hyun-Joo Bae; Wook Bum Pyun; Yun-Chul Hong; Youn-Hee Lim (Environmental Research, 2023)

Protective effect of 7-hydroxyl-1-methylindole-3-acetonitrile on the intestinal mucosal damage response to inflammation in mice with DSS-induced colitis - Kyung-Sook Chung; Sang-Eun Park; Jung-Hun Lee; Su-Yeon Kim; Hee-Soo Han; Yong Sup Lee; Seang-Hwan Jung; Eungyeong Jang; Sangmin Lee; Kyung-Tae Lee (Chemico-Biological Interactions, 2023)

Evaluating the comparative MT1B, MT1F, MT1G, and MT1H expression in human pulmonary alveolar epithelial cells treated with polyhexamethylene guanidine-phosphate, chloromethylisothiazolinone/methylisothiazolinone, oligo(2-(2-ethoxy)ethoxyethyl guanidinium chloride, benzalkonium chloride, and sodium dichloroisocyanurate - Jaeyoung Kim; Yong-Wook Baek; Cherry Kim; Yoon Jeong Nam; Yu-Seon Lee; Hong Lee; Ja Young Kang; Hyejin Lee; Jin Young Choi; Yoon Hee Park; Su A. Park; Eun-Kee Park; et al. (Molecular & Cellular Toxicology, 2023)

Gene expression related to lung cancer altered by PHMG-p treatment in PBTE cells - Yoon Hee Park; Sang Hoon Jeong; Hyejin Lee; Cherry Kim; Yoon Jeong Nam; Ja Young Kang; Jin Young Choi; Yu-Seon Lee; Su A. Park; Jaeyoung Kim; Eun-Kee Park; Yong-Wook Baek; et al. (Molecular & Cellular Toxicology, 2023)

A mechanism-based understanding of altered drug pharmacokinetics by gut microbiota - Aneela Gulnaz; Ji-Eun Chang; Han-Joo Maeng; Kwang-Hee Shin; Kyeong-Ryoon Lee; Yoon-Jee Chae (Journal of Pharmaceutical Investigation, 2023)

Sensitive electrochemical sensing platform based on Au nanoflower-integrated carbon fiber for detecting interleukin-6 in human serum - Sekar Madhu; Jang Hee Han; Chang Wook Jeong; Jungil Choi (Analytica Chimica Acta, 2023)

Estimation of Snow Cover over Mountain Region based on the Surface Wet-bulb Temperature Measurements - Ji-Han Sim; Baek-Min Kim; Jai-Ho Oh; Mo-Rang Huh; Namkyu Noh; Kwang-Hee Han (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Estimation of the Benthic Habitat Zonation by Photo-Quadrat Image Analysis along the Fringing Reef of Weno Island, Chuuk, Micronesia - Taihun Kim; Dae-Won Lee; Han-Jun Kim; Yun-Hwan Jung; Young-Ung Choi; Jung-Hee Oh; Tae-Hoon Kim; Do-Hyung Kang; Heung-Sik Park (Journal of Marine Science and Engineering, 2022)
Benthic habitat zonation is described from in situ observations and seabed photographs taken from the coastal area of Weno Island, Chuuk, Micronesia. Habitat groups, types, and boundaries are defined by visible substratum characteristics (i.e., in situ and by digital imaging of photo-quadrats along transect lines), and by cluster and ordination analyses using relative coverage percentage of identified classification categories. The statistical similarity between habitat groups is determined by Analysis of similarity (ANOSIM). Benthic habitat groups with significant influence on the determination of habitat type are isolated by the similarity percentage (SIMPER) test. In addition to the standard practices of using transect lines and collecting data in accordance with the already well-implemented and thoroughly-tested benthic habitat classification scheme for tropical reef monitoring, we applied simple statistics that enable comparative data interpretation. Our simple, repeatable methods provide a framework for benthic habitat-related monitoring research that allows the comparison of results across regions.

Factors governing seawater carbonate dynamics in a macroalgal habitat - Ja-Myung Kim; Kitack Lee; In-Seong Han; Miok Kim; Ju-Hyoung Kim; Tae-Hoon Kim; HyunKyum Kim; Byung Hee Jeon; Kyoungsoon Shin (Frontiers in Marine Science, 2022)
Photosynthetic organisms shift the dynamics of surface pCO 2 driven by the sea surface temperature change (thermodynamic driver) by assimilating inorganic C from seawater. Here we measured net C uptake in a macroalgal habitat of coastal Korea for two years (2019-2020) and found that the macroalgal habitat contributed 5.8 g C m −2 month −1 of the net C uptake during the growing period (the cooling period, September−May). This massive C uptake changed the thermodynamics-driven seasonal dynamics such that the air−sea equilibrium of pCO 2 was pushed into disequilibrium. The surface pCO 2 dynamics during the cooling period was mostly influenced by the seasonal decrease in temperature and the proliferation of macroalgae, while the dynamics during the warming period (the stagnant period, June−August) closely followed that predicted based solely on the change in sea surface temperature (thermodynamic driver). In contrast to the phytoplankton-dominated off-shore waters (where phytoplankton populations are large in spring and summer), the impact of coastal macroalgae on surface pCO 2 dynamics was most pronounced during the cooling period, when the magnitude of pCO 2 change was as much as twice that resulting from temperature change. Our study shows that the distinctive features of the macroalgal habitat—in particular the seasonal temperature extremes (~18°C difference), the active macroalgal metabolism, and anthropogenic nutrient inputs—collectively influenced the seasonal decoupling of seawater and air pCO 2 dynamics.

Neotectonics at the SE Continental Margin of the Korean Peninsula: Implications for the Back-Arc Region Behind the SW Japan Arc - Han-Joon Kim; Seonghoon Moon; Chungho Kim; Kwang-Hee Kim; Wooseok Seo; Kwang-Hyun Cho; Hye-Jin Moon; Gwang Hoon Lee (Pure and Applied Geophysics, 2022)

Impact of buffer concentration on the thermal stability of immunoglobulin G - Soo Hyun Kim; Han Ju Yoo; Eun Ji Park; Wonhwa Lee; Dong Hee Na (Journal of Pharmaceutical Investigation, 2022)

Concurrent sorption of antimony and lead by iron phosphate and its possible application for multi-oxyanion contaminated soil - Han Na Kim; Jin Hee Park (Environmental Science and Pollution Research, 2022)

Comparison of pollution tolerance in sunflowers as a case study to establish risk assessment criteria for transgenic plants for environmental remediation - Sung Min Han; Kyong-Hee Nam (Plant Biotechnology Reports, 2022)

Effect of 3-caffeoyl, 4-dihydrocaffeoylquinic acid from Salicornia herbacea on endothelial nitric oxide synthase activation via calcium signaling pathway - Gi Ho Lee; Seung Yeon Lee; Chuanfeng Zheng; Hoa Thi Pham; Chae Yeon Kim; Mi Yeon Kim; Eun Hee Han; Yong Pil Hwang; Hye Gwang Jeong (Toxicological Research, 2022)

Bacteroides humanifaecis sp. nov., isolated from faeces of healthy Korean - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2022)

Fat Graft with Allograft Adipose Matrix and Magnesium Hydroxide-Incorporated PLGA Microspheres for Effective Soft Tissue Reconstruction - Dae-Hee Kim; Da-Seul Kim; Hyun-Jeong Ha; Ji-Won Jung; Seung-Woon Baek; Seung Hwa Baek; Tae-Hyung Kim; Jung Chan Lee; Euna Hwang; Dong Keun Han (Tissue Engineering and Regenerative Medicine, 2022)

Isolation of High Purity Mouse Mesenchymal Stem Cells through Depleting Macrophages Using Liposomal Clodronate - Ju Han Song; Jung-Woo Kim; Mi Nam Lee; Sin-Hye Oh; Xianyu Piao; Zhao Wang; Seung-Hee Kwon; Ok-Su Kim; Jeong-Tae Koh (Tissue Engineering and Regenerative Medicine, 2022)
BACKGROUND : The use of mouse bone marrow mesenchymal stem cells (mBMSCs) represents a promising strategy for performing preclinical studies in the field of cell-based regenerative medicine; however, mBMSCs obtained via conventional isolation methods have two drawbacks, i.e., (i) they are heterogeneous due to frequent macrophage contamination, and (ii) they require long-term culturing for expansion. METHODS : In the present study, we report a novel strategy to generate highly pure mBMSCs using liposomal clodronate. This approach is based on the properties of the two cell populations, i.e., BMSCs (to adhere to the plasticware in culture dishes) and macrophages (to phagocytose liposomes). RESULTS : Liposomal clodronate added during the first passage of whole bone marrow culture was selectively engulfed by macrophages in the heterogeneous cell population, resulting in their effective elimination without affecting the MSCs. This method allowed the generation of numerous high-purity Sca-1 + CD44 + F4/80 − mBMSCs (> 95%) with just one passaging. Comparative studies with mBMSCs obtained using conventional methods revealed that the mBMSCs obtained in the present study had remarkably improved experimental utilities, as demonstrated by in vitro multilineage differentiation and in vivo ectopic bone formation assays. CONCLUSION : Our newly developed method, which enables the isolation of mBMSCs using simple and convenient protocol, will aid preclinical studies based on the use of MSCs.

Correlation of seismicity with geologic structures at the middle eastern Korean margin in the East Sea (Japan Sea) and seismic hazard assessment - Seonghoon Moon; Han-Joon Kim; Kwang-Hee Kim; Dong-Geun Yoo; Sang-Hoon Lee; Woo-Hyun Son; Bo Yeon Yi (Marine Geophysical Research, 2022)

Next-Generation Sequencing Results Vary Between Cultured and Uncultured Microbes - Hee Sang You; Song Hee Lee; Young Ju Lee; Han Lee; Sang Sun Kang; Sung Hee Hyun (Current Microbiology, 2022)

Measurement of seismometer misorientation based on P-wave polarization: application to dense temporary broadband seismic array in the epicentral region of 2016 Gyeongju earthquake, South Korea - Min-Seong Seo; Young Oh Son; YoungHee Kim; Tae-Seob Kang; Junkee Rhie; Kwang-Hee Kim; Jin-Han Ree (Geosciences Journal, 2022)

Update on CD164 and LMX1A genes to strengthen their causative role in autosomal dominant hearing loss - Dominika Oziębło; Sang‐Yeon Lee; Marcin Ludwik Leja; Anna Sarosiak; Natalia Bałdyga; Henryk Skarżyński; Yehree Kim; Jin Hee Han; Hyo Soon Yoo; Min Hyun Park; Byung Yoon Choi; Monika Ołdak (Human Genetics, 2022)

Potential of a Tintinnid Species, Tintinnidium primitivum, as a Biological Indicator in the Yellow Sea Bottom Cold Water - Young Ok Kim; Jungmin Choi; Kyung-Hee Oh; Dong Han Choi; Jae Hoon Noh; Wonseok Yang; Myung Jin Hyun (Ocean Science Journal, 2022)

Utility of plasma cell-free DNA detection using homobifunctional imidoesters using a microfluidic system for diagnosing active tuberculosis - Joung Ha Park; Bonhan Koo; Min Jae Kim; Hyo Joo Lee; Hye-Hee Cha; Ji Yeun Kim; Sei Won Lee; Yong Shin; Sung-Han Kim (Infectious Diseases, 2022)

Arsenic removal characteristics of natural Mn-Fe binary coating on waste filter sand from a water treatment facility - Young-Soo Han; Seol-Hee Kim; Jeong-Yun Jang; Sangwoo Ji (Environmental Science and Pollution Research, 2022)

JAK2 regulates paclitaxel resistance in triple negative breast cancers - Jongmin Han; Jihui Yun; Mingji Quan; Wonyoung Kang; Ji-Gwang Jung; Woohang Heo; Songbin Li; Kyu Jin Lee; Hye-Youn Son; Ju Hee Kim; Jaeyong Choi; Dong-Young Noh; et al. (Journal of Molecular Medicine, 2021)

Identification of QTLs for cold tolerance at the booting and flowering stages in rice (Oryza sativa L.) - Lina Zhang; Jianghong Tang; Di Cui; Cuifeng Tang; Xiaoding Ma; Xinxiang A; Bing Han; Guilan Cao; Zhengwu Zhao; Hee-Jong Koh; Longzhi Han (Euphytica, 2021)

Diagnostic evaluation of qRT-PCR-based kit and dPCR-based kit for COVID-19 - Cherl-Joon Lee; Wonseok Shin; Seyoung Mun; Minjae Yu; Young-Bong Choi; Dong Hee Kim; Kyudong Han (Genes & Genomics, 2021)

Multilayered Cell Sheets of Cardiac Reprogrammed Cells for the Evaluation of Drug Cytotoxicity - Sung Pil Kwon; Seuk Young Song; Jin Yoo; Han Young Kim; Ju-Ro Lee; Mikyung Kang; Hee Su Sohn; Seokhyoung Go; Mungyo Jung; Jihye Hong; Songhyun Lim; Cheesue Kim; et al. (Tissue Engineering and Regenerative Medicine, 2021)

TGFβ1-Induced Transglutaminase-2 Triggers Catabolic Response in Osteoarthritic Chondrocytes by Modulating MMP-13 - Jae-Young Park; Hyun Cheol Bae; Sung Hee Pyo; Myung Chul Lee; Hyuk-Soo Han (Tissue Engineering and Regenerative Medicine, 2021)

Short-term exposure to air pollution and hospital admission for heart failure among older adults in metropolitan cities: a time-series study - Dong-Wook Lee; Chang-Woo Han; Yun-Chul Hong; Jong-Min Oh; Hyun-Joo Bae; Soontae Kim; Youn-Hee Lim (International Archives of Occupational and Environmental Health, 2021)

Collinsella acetigenes sp. nov., an Anaerobic Actinobacterium Isolated from Human Feces, and Emended Description of the Genus Collinsella and Collinsella aerofaciens - Kook-Il Han; Ji-Sun Kim; Mi Kyung Eom; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Seung-Hwan Park; Ju Huck Lee; Se Won Kang; Jam-Eon Park; Byeong Seob Oh; Seoung Woo Ryu; et al. (Current Microbiology, 2021)

Tiller Outgrowth in Rice (Oryza sativa L.) is Controlled by OsGT1, Which Acts Downstream of FC1 in a PhyB-Independent Manner - Vikranth Kumar; Sung Hoon Kim; Moch Rosyadi Adnan; Jung Heo; Jin Hee Jeong; Ryza A. Priatama; Jeung Joo Lee; Chul Min Kim; Byoung Il Je; Soon Ju Park; Yuan Hu Xuan; Chang-deok Han (Journal of Plant Biology, 2021)

Hymenobacter taeanensis sp. nov., radiation resistant bacterium isolated from coastal sand dune - Ji Hee Lee; Jong-Hyun Jung; Min-Kyu Kim; Han Na Choe; Sangyong Lim (Antonie van Leeuwenhoek, 2021)

Liposoluble portion of the red alga Pyropia yezoensis protects alcohol induced liver injury in mice - Ji-Hyeok Lee; Ginne Ahn; Ju-Young Ko; Nalae Kang; Kyungsook Jung; Eui-Jeong Han; Gwang-Hoon Kim; Hee Jeong Kim; Cheol Soo Choi; You-Jin Jeon (Algae, 2021)
The hepatoprotective effect of liposoluble portion of Pyropia yezoensis (PYLP) was investigated against alcohol-induced liver injury in mice. Fatty acids were predominant in PYLP obtained from hexane fraction of 70% EtOH extract after ultrasonication. In particular, polyunsaturated fatty acids such as eicosapentaenoic acid and linoleic acid accounted for 56.91% of the total lipids. PYLP significantly reduced liver damage induced by the alcohol treatment in mice. PYLP treatment increased the activity of antioxidant enzymes including superoxide dismutase, catalase, and glutathion peroxidase by reducing thiobarbituric acid reactive substances. Histological observations showed that PYLP minimizes damage to living tissue induced by alcohol treatment by modulating the expression level of proteins involved in the anti-apoptotic signaling pathway. Our results suggest that PYLP, rich in polyunsaturated fatty acids extracted from the red alga P. yezoensis, will be useful as a potential liver protectant in the hangover industry.

Frequency of putative enteric zoster diagnosed using saliva samples in patients with abdominal pain: a prospective study - Sang Hyun Ra; Ji-Soo Kwon; Ji Yeun Kim; Hye-Hee Cha; Hyun-Jung Lee; Jiwon Jung; Min Jae Kim; Yong Pil Chong; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Won Young Kim; et al. (Infectious Diseases, 2021)

Ursodeoxycholic acid shows antineoplastic effects in bile duct cancer cells via apoptosis induction; p53 activation; and EGFR-ERK, COX-2, and PI3K-AKT pathway inhibition - Jin Lee; Eun Mi Hong; Jung Han Kim; Jung Hee Kim; Jang Han Jung; Se Woo Park; Dong Hee Koh; Hyun Joo Jang (Molecular Biology Reports, 2021)

Effect of ingestion methods of jellies for oral administration on drug absorption in beagle dogs - Kyung Hee Han; Joong-Won Jeon; Yoon-Jee Chae; Mi-Kyung Lee (Journal of Pharmaceutical Investigation, 2021)

Investigation of high correlation with carcass traits of SNPs of the PLCB1, C/EBPα, and TDRKH genes and the combinations of SNPs using the MDR method in the Hanwoo - Songmi Kim; Yong-Moon Lee; Dong Hee Kim; Jae Jung Ha; Jun Koo Yi; Dae Hyun Kim; Dongyep Oh; Kyudong Han (Genes & Genomics, 2021)

Flow cytometric evaluation of the potential of metal oxide nanoparticles for skin sensitization using 5-Bromo-2-deoxyuridine - Dong Han Lee; Sung-Hyun Kim; Jin Hee Lee; Jun-Young Yang; Ji-Hyun Seok; Kikyung Jung; Jong Kwon Lee (Toxicological Research, 2021)

RNA-sequencing identification and validation of genes differentially expressed in high-risk adenoma, advanced colorectal cancer, and normal controls - Namjoo Kim; Jeong-An Gim; Beom Jae Lee; Byung il Choi; Seung Bin Park; Hee Sook Yoon; Sang Hee Kang; Seung Han Kim; Moon Kyung Joo; Jong-Jae Park; Chungyeul Kim; Han-Kyeom Kim (Functional & Integrative Genomics, 2021)

Complete genome sequencing and comparative CAZyme analysis of Rhodococcus sp. PAMC28705 and PAMC28707 provide insight into their biotechnological and phytopathogenic potential - Nisha Ghimire; So-Ra Han; Byeollee Kim; Sang-Hee Jung; Hyun Park; Jun Hyuck Lee; Tae-Jin Oh (Archives of Microbiology, 2021)

Generation of Hepatic Progenitor Cells from the Primary Hepatocytes of Nonhuman Primates Using Small Molecules - Da Hee Hong; Changhee Lee; Yohan Kim; Seung Bum Lee; Su-Cheol Han; Sung Joo Kim; Heung-Mo Yang; Dongho Choi; Jaemin Jeong; Kiyoung Ryu (Tissue Engineering and Regenerative Medicine, 2021)

Correction to: A Novel Method to Differentiate Tonsil-Derived Mesenchymal Stem Cells In Vitro into Estrogen-Secreting Cells - Hee-Yeon Kim; Younghay Lee; Hee-Soo Yoon; Yu-Hee Kim; Kyung-Ah Cho; So-Youn Woo; Han Su Kim; Bo Young Park; Sung-Chul Jung; Inho Jo; Woo-Jae Park; Joo-Won Park; et al. (Tissue Engineering and Regenerative Medicine, 2021)

A Novel Method to Differentiate Tonsil-Derived Mesenchymal Stem Cells In Vitro into Estrogen-Secreting Cells - Hee-Yeon Kim; Younghay Lee; Hee-Soo Yoon; Yu-Hee Kim; Kyong-A Cho; So-Youn Woo; Han Sun Kim; Bo-Young Park; Sung-Chul Jung; Inho Jo; Woo-Jae Park; Joo-Won Park; et al. (Tissue Engineering and Regenerative Medicine, 2021)

A novel apoptosis probe, cyclic ApoPep-1, for in vivo imaging with multimodal applications in chronic inflammatory arthritis - In-Seop So; Jin Hee Kang; Jung Wan Hong; Shijin Sung; Al Faruque Hasan; Keum Hee Sa; Seung Woo Han; In San Kim; Young Mo Kang (Apoptosis, 2021)

Spring Distribution of Ciliate Plankton in the Southeastern Yellow Sea in 2019 - Young Ok Kim; Jungmin Choi; Hyung-Ku Kang; Jae Hoon Noh; Dong Han Choi; Kyung-Hee Oh (Ocean Science Journal, 2021)

Spatial distribution of salinity and heavy metals in surface soils on the Mugan Plain, the Republic of Azerbaijan - Junho Han; Zaman Mammadov; Minhee Kim; Elton Mammadov; Seoyeon Lee; Jisuk Park; Garib Mammadov; Guliyev Elovsat; Hee-Myong Ro (Environmental Monitoring and Assessment, 2021)

Monitoring a short-lived earthquake swarm during April–May 2020 in Haenam, Korea, and its preliminary results - Jongwon Han; Wooseok Seo; Han-Joon Kim; Won-Young Kim; Deokhee Won; Ji-In Chung; Kwang-Hee Kim (Geosciences Journal, 2021)

Spirosoma taeanense sp. nov., a radiation resistant bacterium isolated from a coastal sand dune - Ji Hee Lee; Jong-Hyun Jung; Min-Kyu Kim; Han Na Choe; Chi Nam Seong; Sangyong Lim (Antonie van Leeuwenhoek, 2021)

Corrigendum: Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2021)

Predicting Functional Outcome Based on Linked Data After Acute Ischemic Stroke: S-SMART Score - Tae Jung Kim; Ji Sung Lee; Mi-Sun Oh; Ji-Woo Kim; Jae Sun Yoon; Jae-Sung Lim; Chan-Hyuk Lee; Heejung Mo; Han-Yeong Jeong; Yerim Kim; Sang-Hwa Lee; Keun-Hwa Jung; et al. (Translational Stroke Research, 2020)

Hymenobacter baengnokdamensis sp. nov., Isolated from the Soil of a Crater Lake in Korea - Ji Hee Lee; Min-Kyu Kim; Jong-Hyun Jung; Ho Seong Seo; Jing Zhang; Han Na Choe; Seon Choi; Chi Nam Seong; Sangyong Lim (Current Microbiology, 2020)

Comparative transcriptome profiling of two sweetpotato cultivars with contrasting flooding stress tolerance levels - Sul-U Park; Yun-Hee Kim; Chan-Ju Lee; So-Eun Kim; Ye-Hoon Lim; Ung-Han Yoon; Ho Soo Kim; Sang-Soo Kwak (Plant Biotechnology Reports, 2020)

Spirosoma aureum sp. nov., and Hymenobacter russus sp. nov., radiation-resistant bacteria in Cytophagales order isolated from soil - Soohyun Maeng; Yuna Park; Joo Hyun Han; Sang Eun Lee; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Rhodocytophaga rosea sp. nov. and Nibribacter ruber sp. nov., two radiation-resistant bacteria isolated from soil - Yuna Park; Soohyun Maeng; Joo Hyun Han; Sang Eun Lee; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Multi-directional Morphological Assessment of Single Bacterial Colonies Through Non-invasive Optical Imaging - Junsoo Lee; Seung-Yeol Lee; Sangyeob Han; Daewoon Seong; Ruchire Eranga Wijesinghe; Pilun Kim; Mansik Jeon; Hee-Young Jung; Jeehyun Kim (Annals of Biomedical Engineering, 2020)

Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2020)
Shark populations are constantly decreasing owing to environmental destruction and overfishing; thus, sharks are now at a risk of extinction, with 27.9% of shark species classified as endangered on the International Union for Conservation of Nature’s Red List. Sharks are apex predators and a keystone species in balancing the marine food chain; their extinction will create an imbalance of the entire marine ecosystem. Assisted reproductive technology is the last resort for protecting animals facing severe extinction. Here, as a proactive effort toward building a hormone-induced artificial insemination protocol for endangered wild sharks, we identified the possibility of germ cell maturation by administration of Ovaprim ® , a commercially produced synthetic salmon gonadotropin-releasing hormone, and calculated its optimum dosage and injection timing. The experiment was conducted on two shark species— Triakis scyllium and Triaenodon obesus . We found that intramuscular injections of 0.2 mL/kg of Ovaprim ® for male T. scyllium and T. obesus , 0.2 mL/kg + 0.5 mL/kg at a 24 h interval for female T. scyllium , and 0.2 mL/kg + 0.2 mL/kg or 0.2 mL/kg + 0.3 mL/kg at a 24 h interval for female T. obesus were optimal dose protocols. These doses effectively induced the maturation and ovulation of oocytes and the release of semen. Our results confirm that Ovaprim ® is a suitable tool for shark hormone-induced artificial insemination and indicate that this method may enable the conservation of the endangered shark species.

Clinical characteristics and prognostic factors of extraintestinal infection caused by Clostridioides difficile: analysis of 60 consecutive cases - Hyemin Chung; Jiwon Jung; Min Jae Kim; Heungsup Sung; Mi-Na Kim; Yong Pil Chong; Sung-Han Kim; Sang-Oh Lee; Yang Soo Kim; Jun Hee Woo; Sang-Ho Choi (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Management and outcomes of Burkholderia cepacia complex bacteremia in patients without cystic fibrosis: a retrospective observational study - Yu-Mi Lee; Ki-Ho Park; Chisook Moon; Dong Youn Kim; Mi Suk Lee; Tark Kim; Eun Ju Choo; Yong Pil Chong; Sung-Han Kim; Yang Soo Kim; Jun Hee Woo; Mee Soo Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

Clinical characteristics and outcomes of Staphylococcus aureus bacteremia from a biliary source - Eunmi Yang; Jeongsoo Lee; Hyeonji Seo; Hyemin Chung; Sang Hyun Ra; Heungsup Sung; Mi-Na Kim; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

NH4+ Suppresses NO3–-Dependent Lateral Root Growth and Alters Gene Expression and Gravity Response in OsAMT1 RNAi Mutants of Rice (Oryza sativa) - Vikranth Kumar; Sung Hoon Kim; Ryza A. Priatama; Jin Hee Jeong; Moch Rosyadi Adnan; Bernet Agung Saputra; Chul Min Kim; Byoung Il Je; Soon Ju Park; Ki Hong Jung; Kyung Min Kim; Yuan Hu Xuan; et al. (Journal of Plant Biology, 2020)

A comprehensive analysis of chimpanzee (Pan Troglodytes)-specific AluYb8 element - Songmi Kim; Dong Hee Kim; Hiroo Imai; Yong-Moon Lee; Kyudong Han (Genes & Genomics, 2020)

Analysis of KAP1 expression patterns and human endogenous retrovirus Env proteins in ovarian cancer - Kyung-Yoon Jeon; Eun-Ji Ko; Young Lim Oh; Hongbae Kim; Wan Kyu Eo; Ari Kim; Han Gyu Sun; Mee Sun Ock; Ki Hyung Kim; Hee-Jae Cha (Genes & Genomics, 2020)

Complete genome sequence of Sphingobium sp. strain PAMC 28499 reveals a potential for degrading pectin with comparative genomics approach - So-Ra Han; Sung-Min Jang; Young Min Chi; Byeollee Kim; Sang-Hee Jung; Yung Mi Lee; Jun Uetake; Jun Hyuck Lee; Hyun Park; Tae-Jin Oh (Genes & Genomics, 2020)

Pontibacter pudoricolor sp. nov., and Pontibacter russatus sp. nov. radiation-resistant bacteria isolated from soil - Soohyun Maeng; Yuna Park; Sang Eun Lee; Joo Hyun Han; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Human Leukocyte Antigen Class I Pseudo-Homozygous Mesenchymal Stem Cells Derived from Human Induced Pluripotent Stem Cells - Daekee Kwon; Hee-Jin Ahn; Mi-Jung Han; Minjun Ji; Jongchan Ahn; Kwang-Won Seo; Kyung-Sun Kang (Stem Cell Reviews and Reports, 2020)

Neural Tract Degeneration Correlates with Functional Impairment in Patients with Anoxic Brain Injury: A Tract-based Spatial Statistics Study - Ji-Yun Park; Sung Ho Park; Jeong-Hee Yang; Han Do Lee; Jiho Lee; Ki-Hyun Byeon; Seo Young Park; Dongseok Yang (Neuroscience Bulletin, 2020)

A new approach to the restoration of seaweed beds using Sargassum fulvellum - Sang Mok Jung; Ji Hyun Lee; Seung Hee Han; Won Bin Jeon; Ga Yeon Kim; Sinyang Kim; Seongju Kim; Hwa-Rim Lee; Dong Soo Hwang; Sungjune Jung; Jongdae Lee; Hyun Woung Shin (Journal of Applied Phycology, 2020)

Waterlogging tolerance in apple trees grafted on rootstocks from G, CG, and M series - Byeong-Ho Choi; Narayan Bhusal; Woo-Tae Jeong; In-Hee Park; Su-Gon Han; Tae-Myung Yoon (Horticulture, Environment, and Biotechnology, 2020)

Characterization of genetic variation and antioxidant properties in strawberry (Fragaria × ananassa Duch.) mutant genotypes - Jaihyunk Ryu; Woon Ji Kim; Sang Hun Kim; Kang-Seop Lee; Han-Jig Jo; Ee-Youb Kim; Sang Hoon Kim; Si-Yong Kang; Jeong-Hee Lee; Bo-Keun Ha (Genetic Resources and Crop Evolution, 2020)

Adsorptive removal of cationic tricyclic antidepressants using cation-exchange resin - Jong-Won Choi; John Kwame Bediako; Yufeng Zhao; Shuo Lin; Amit Kumar Sarkar; Minhee Han; Myung-Hee Song; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Science and Pollution Research, 2020)

Impact of neutropenia on the clinical outcomes of Staphylococcus aureus bacteremia in patients with hematologic malignancies: a 10-year experience in a tertiary care hospital - Byung-Han Ryu; Seung Cheol Lee; Minjeong Kim; Yewon Eom; Jiwon Jung; Min Jae Kim; Heungsup Sung; Mi-Na Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jun Hee Woo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Factors modifying the structural configuration of oxyanions and organic acids adsorbed on iron (hydr)oxides in soils. A review - Junho Han; Minhee Kim; Hee-Myong Ro (Environmental Chemistry Letters, 2020)
Oxyanions are ubiquitous in soils, organisms and the environment. Due to their unique chemical structure, oxyanions can be easily transferred into other systems. Carbonate (CO 3 2− ), nitrate (NO 3 − ), phosphate (PO 4 3− ), silicate (SiO 4 2− ) and sulfate (SO 4 2− ) are the major oxyanions in organisms and the soil environment, whereas arsenate (AsO 4 3− ), antimonate (SbO 4 3− ), borate (BO 3 3− ), selenate (SeO 4 2− ), and tellurate (TeO 4 2− ) are generally reported as toxic chemicals found at trace levels. Excessive oxyanions leached from soils into water have caused severe environmental problems. Here, we review the factors affecting the structural configuration of oxyanions and organic acids adsorbed on iron oxides and hydroxides. The configuration of oxyanions on iron (hydr)oxides is controlled by surface loading, pH, sample phase, competing ions and organic acids. Under conditions of low surface loading and low pH at the interface in the absence of competing ions, oxyanions with high affinity possibly form a complex with higher denticity. But an increase in pH decreases the number of sorption sites; thus, a transition from a tri- or bidentate complex to monodentate and outer-sphere complexes occurs.

Acinetobacter pullicarnis sp. nov. isolated from chicken meat - Rae-Hee Han; Ju-Eun Lee; Sung-Hee Yoon; Geun-Bae Kim (Archives of Microbiology, 2020)

Flexural behaviour prediction for RC beams in consideration of compressive stress distribution of concrete with electric arc furnace oxidising slag aggregates - Yong-Jun Lee; Hyeong-Gook Kim; Jung-Han Park; Kang-Seok Lee; Kil-Hee Kim (European Journal of Environmental and Civil Engineering, 2020)

A comparison of histomorphologic diagnosis with culture- and immunohistochemistry-based diagnosis of invasive aspergillosis and mucormycosis - Hyo-Ju Son; Joon Seon Song; Sungim Choi; Jiwon Jung; Min Jae Kim; Yong Pil Chong; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Jun Hee Woo; Sung-Han Kim (Infectious Diseases, 2020)

Optimal Condition of Isolation from an Adipose Tissue-Derived Stromal Vascular Fraction for the Development of Automated Systems - Su Jin Lee; Chae Rim Lee; Ki Joo Kim; Yeon Hee Ryu; Eunjin Kim; Yu Na Han; Suk-Ho Moon; Jong-Won Rhie (Tissue Engineering and Regenerative Medicine, 2020)

Sequence-characterized amplified region markers and multiplex-polymerase chain reaction assays for kiwifruit cultivar identification - Kang Hee Cho; Yong-Bum Kwack; Seo Jun Park; Se Hee Kim; Han Chan Lee; Kyeong Ho Chung; Ji Hae Jun (Horticulture, Environment, and Biotechnology, 2020)

Long-term methicillin-resistant Staphylococcus aureus bacteremia persisting for more than 2 weeks: risk factors and outcomes - Yu-Mi Lee; Yong Pil Chong; Minjeong Kim; Yewon Eom; Eun Sil Kim; Miyoung Kim; Ki-Ho Park; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jun Hee Woo; Yang Soo Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Clinical significance of follow-up blood culture in patients with a single Staphylococcus aureus -positive blood culture - Taeeun Kim; Seung Cheol Lee; Min Jae Kim; Jiwon Jung; Heungsup Sung; Mi-Na Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jun Hee Woo; Yang Soo Kim; Yong Pil Chong (Infectious Diseases, 2020)

Diverse Gene Expressions in the Prediction of Cuprizone-Induced Demyelination - Seung Ro Han; Yun Hee Kang; Seung-Min Yoo; Myung-Shin Lee; Seung-Hoon Lee (Neurotoxicity Research, 2020)

A multidisciplinary assessment of the impact of spilled acids on geoecosystems: an overview - Sung Pil Hyun; Doyun Shin; Hee Sun Moon; Young-Soo Han; Seonjin Ha; Yoonho Lee; Eunhee Lee; Hyun Jung; Yu Sik Hwang (Environmental Science and Pollution Research, 2020)

Effect of probiotics on obesity-related markers per enterotype: a double-blind, placebo-controlled, randomized clinical trial - Eun-Ji Song; Kyungsun Han; Tae-Joong Lim; Sanghyun Lim; Myung-Jun Chung; Myung Hee Nam; Hojun Kim; Young-Do Nam (EPMA Journal, 2020)

Effects of aging and exercise training on mitochondrial function and apoptosis in the rat heart - Mi-Hyun No; Jun-Won Heo; Su-Zi Yoo; Chang-Ju Kim; Dong-Ho Park; Ju-Hee Kang; Dae-Yun Seo; Jin Han; Hyo-Bum Kwak (Pflügers Archiv - European Journal of Physiology, 2020)

Circadian modulation of the cardiac proteome underpins differential adaptation to morning and evening exercise training: an LC-MS/MS analysis - Dae Yun Seo; Chang Shin Yoon; Louise Anne Dizon; Sung Ryul Lee; Jae Boum Youm; Won Suk Yang; Hyo-Bum Kwak; Tae Hee Ko; Hyoung Kyu Kim; Jin Han; Robin A McGregor (Pflügers Archiv - European Journal of Physiology, 2020)

Acute and 13-week subchronic toxicity studies of hot-water extract of Cynanchi wilfordii Radix in Sprague-Dawley rats - Chung-Tack Han; Du-Yeol Kim; Chunja Nam; Seol-Hee Moon; Sun-Hee Park; Kyoung-Goo Han; Hye-Yeong Lee; Heung-Mo Bae; Cheol-Beom Park; Jai-Hyun So; Sukmo Kang; Jong-Koo Kang (Toxicological Research, 2020)

Morphology and phylogenetic relationships of Micractinium (Chlorellaceae, Trebouxiophyceae) taxa, including three new species from Antarctica - Hyunsik Chae; Sooyeon Lim; Han Soon Kim; Han-Gu Choi; Ji Hee Kim (Algae, 2019)

Effects of elevated ozone on physiological, biochemical and morphological characteristics of eggplant - Yang Li; Su Young Woo; Jong Kyu Lee; Myeong Ja Kwak; Inkyin Khaine; Ji Hwi Jang; Hae Naem Kim; Ji Eun Kim; Sang Hee Park; Han Dong Kim; Yea Ji Lim (Horticulture, Environment, and Biotechnology, 2019)

Incidence, clinical characteristics, and outcomes of Streptococcus dysgalactiae subspecies equisimilis bacteremia in a tertiary hospital: comparison with S. agalactiae bacteremia - Joung Ha Park; Jiwon Jung; Min Jae Kim; Heungsup Sung; Mi-Na Kim; Yong Pil Chong; Sung-Han Kim; Sang-Oh Lee; Yang Soo Kim; Jun Hee Woo; Sang-Ho Choi (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

A comparative evaluation of BACT/ALERT FA PLUS and FN PLUS blood culture bottles and BD BACTEC Plus Aerobic and Anaerobic blood culture bottles for antimicrobial neutralization - Yousun Chung; In-Hee Kim; Minje Han; Hyun Soo Kim; Han-Sung Kim; Wonkeun Song; Jae-Seok Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Future Directions of Pharmacovigilance Studies Using Electronic Medical Recording and Human Genetic Databases - Young Hee Choi; Chang Yeob Han; Kwi Suk Kim; Sang Geon Kim (Toxicological Research, 2019)

Pharmacokinetic and Pharmacodynamic Modeling and Simulation Analysis of CTB-001, a Recently Developed Generic of Bivalirudin - Sungpil Han; Yo-Han Kim; Hee Youn Choi; Mi-Jo Kim; Wan Joo Kim; Hyunjung Park; Kyun-Seop Bae; Hyeong-Seok Lim (Pharmaceutical Research, 2019)

Phenotypic and molecular spectrum of Korean patients with Lesch-Nyhan syndrome and attenuated clinical variants - Ja Hyang Cho; Jin-Ho Choi; Sun Hee Heo; Gu-Hwan Kim; Mi-Sun Yum; Beom Hee Lee; Han-Wook Yoo (Metabolic Brain Disease, 2019)

Comparison of library construction kits for mRNA sequencing in the Illumina platform - Yong-Soo Park; Songmi Kim; Dong-Guk Park; Dong Hee Kim; Kyeong-Wook Yoon; Wonseok Shin; Kyudong Han (Genes & Genomics, 2019)

Sternoclavicular septic arthritis caused by Staphylococcus aureus : excellent results from medical treatment and limited surgery - Young-Rock Jang; Taeeun Kim; Min-Chul Kim; Heung Sup Sung; Mi-Na Kim; Min Jae Kim; Sung Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jun Hee Woo; Yang Soo Kim; Yong Pil Chong (Infectious Diseases, 2019)

Clinical characteristics and treatment outcomes of Enterococcus durans bacteremia: a 20-year experience in a tertiary care hospital - Byung-Han Ryu; Jeongmin Hong; Jiwon Jung; Min Jae Kim; Heungsup Sung; Mi-Na Kim; Yong Pil Chong; Sung-Han Kim; Sang-Oh Lee; Yang Soo Kim; Jun Hee Woo; Sang-Ho Choi (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Complete genome sequence and phylogenetic analysis of nosocomial pathogen Acinetobacter nosocomialis strain NCTC 8102 - Bindu Subhadra; Surya Surendran; Bo Ra Lim; Jong-Sung Yim; Dong Ho Kim; Kyungho Woo; Kyudong Han; Man Hwan Oh; Chul Hee Choi (Genes & Genomics, 2019)

Cinnamomum camphora Leaves Alleviate Allergic Skin Inflammatory Responses In Vitro and In Vivo - Na-Jin Kang; Sang-Chul Han; Seok-Hyun Yoon; Jae-Yeop Sim; Young Hee Maeng; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2019)

Chrysophanol, an anthraquinone from AST2017-01, possesses the anti-proliferative effect through increasing p53 protein levels in human mast cells - Na-Ra Han; Hee-Yun Kim; Soonsik Kang; Mi Hye Kim; Kyoung Wan Yoon; Phil-Dong Moon; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2019)

A comprehensive analysis of the Baboon-specific full-length LINE-1 retrotransposons - Wooseok Lee; Minhoon Choi; Songmi Kim; Wanxiangfu Tang; Dong Hee Kim; Heui-Soo Kim; Ping Liang; Kyudong Han (Genes & Genomics, 2019)

Are Probiotics Effective in Targeting Alcoholic Liver Diseases? - Meegun Hong; Dae Hee Han; Jitaek Hong; Dong Joon Kim; Ki Tae Suk (Probiotics and Antimicrobial Proteins, 2019)

Genetic diversity and population structure of Kichulchoia multifasciata in South Korea - Han-Gyu Bae; Casey Nightingale; Duck Hee Jeoung; Sunho Cha; Hyung-Bae Jeon; Hangkyo Lim; Ho Young Suk (Conservation Genetics, 2019)

Correlation of fungal cultures from non-sterile sites and Galactomannan assay with the diagnosis of aspergillosis and mucormycosis based on sterile culture results and histopathologic findings - Taeeun Kim; Jiwon Jung; Joon Seon Song; Heungsup Sung; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Jun Hee Woo; Sung-Han Kim; Kyung Ja Cho (Infectious Diseases, 2019)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

Repositioning of the antipsychotic drug TFP for sepsis treatment - Jung Hwa Park; Hyun Jin Park; Sung Eun Lee; Young Seob Kim; Gun-Young Jang; Hee Dong Han; In Duk Jung; Kyung Chul Shin; Young Min Bae; Tae Heung Kang; Yeong-Min Park (Journal of Molecular Medicine, 2019)

TSPYL5-mediated inhibition of p53 promotes human endothelial cell function - Hee-Jun Na; Chung Eun Yeum; Han-Seop Kim; Jungwoon Lee; Jae Yun Kim; Yee Sook Cho (Angiogenesis, 2019)

Conditioned Medium from Tonsil-Derived Mesenchymal Stem Cells Relieves CCl4-Induced Liver Fibrosis in Mice - Yu-Hee Kim; Kyung-Ah Cho; Minhwa Park; Han Su Kim; Joo-Won Park; So-Youn Woo; Kyung-Ha Ryu (Tissue Engineering and Regenerative Medicine, 2019)

In Vivo Safety and Regeneration of Long-Term Transported Amniotic Fluid Stem Cells for Renal Regeneration - Na-hee Yu; So Young Chun; Yun-Sok Ha; Hyun Tae Kim; Eugene Lih; Dae Hwan Kim; Jeongshik Kim; Jae-Wook Chung; Phil Hyun Song; Eun Sang Yoo; Sung Kwang Chung; Dong Keun Han; et al. (Tissue Engineering and Regenerative Medicine, 2019)

Improvement of blood culture contamination rate, blood volume, and true positive rate after introducing a dedicated phlebotomy team - Moonsuk Bae; Hae In Kim; Joung Ha Park; Byung-Han Ryu; Jeonghyun Chang; Heungsup Sung; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Transgenic Arabidopsis plants expressing CsBCATs affect seed germination under abiotic stress conditions - Jeong Hwan Lee; Ji Hoon Han; Young-Cheon Kim; Young Hee Lee; Jeum Kyu Hong; Sanghyeob Lee (Plant Biotechnology Reports, 2019)

Correction to: Nanomedicines: current status and future perspectives in aspect of drug delivery and pharmacokinetics - Young Hee Choi; Hyo-Kyung Han (Journal of Pharmaceutical Investigation, 2019)
The article “Nanomedicines: current status and future perspectives in aspect of drug delivery and pharmacokinetics”, written by Young Hee Choi and Hyo‑Kyung Han, was originally published electronically on the publisher’s internet portal (currently SpringerLink) on 28 November 2017 without open access.

Correction to: Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2019)

Multiplex PCR using YeaD and 16S rRNA gene to identify major pathogens in vibriosis of Litopenaeus vannamei - Yeong-Jong Han; Ara Jo; So-Won Kim; Hee-Eun Lee; Young Chul Kim; Hyun Do Jeong; Yung Hyun Choi; Suhkmann Kim; Hee-Jae Cha; Heui-Soo Kim (Genes & Genomics, 2019)

Simulation of the 1953 storm surge in the North Sea - Byung Ho Choi; Kyeong Ok Kim; Jin-Hee Yuk; Han Soo Lee (Ocean Dynamics, 2018)

MicroRNA 429 regulates the expression of CHMP5 in the inflammatory colitis and colorectal cancer cells - Ji-Su Mo; Seol-Hee Han; Ki-Jung Yun; Soo-Cheon Chae (Inflammation Research, 2018)

Flavobacterium knui sp. nov., a novel member of the family Flavobacteriaceae - Seo-Yeong Kim; Leonid N. Ten; Seung-Yeol Lee; Seung-Han Kim; In-Kyu Kang; Hee-Young Jung (Antonie van Leeuwenhoek, 2018)

Electrophysiological Signatures of Intrinsic Functional Connectivity Related to rTMS Treatment for Mal de Debarquement Syndrome - Yoon-Hee Cha; Guofa Shou; Diamond Gleghorn; Benjamin C. Doudican; Han Yuan; Lei Ding (Brain Topography, 2018)

Nocardia seriolae infection in the cultured eel Anguilla japonica in Korea - Jin Do Kim; Nam‐Sil Lee; Jeung Wan Do; Myoung Sug Kim; Han Gill Seo; Miyoung Cho; Sung Hee Jung; Hyun‐Ja Han (Journal of Fish Diseases, 2018)
Mass mortality occurred at an Anguilla japonica eel farm equipped with a recirculating aquaculture system in Gimcheon, Korea, from late spring to early summer 2015. The cumulative 3‐month mortality was 16% (approximately 24,300–150,000 fish). The majority of affected fish displayed ulcerative lesions that progressed to petechial haemorrhages and small white granulomas in the major organs. A Gram‐positive, acid‐fast, nonmotile bacterium was isolated from internal organ lesions. Phylogenetic analysis of 16S rRNA identified the species as Nocardia seriolae and the strain was designated EM 150506. Afterwards, naïve eels were injected with 1.8 × 10 7 colony‐forming units per fish to confirm the strain's pathogenicity, which resulted in a 20% mortality rate within 4 weeks. However, surviving fish still exhibited white N. seriolae colonies in internal organs. To our knowledge, this is the first report of a N. seriolae infection in cultured eel.

Interpreting competitive adsorption of arsenate and phosphate on nanosized iron (hydr)oxides: effects of pH and surface loading - Junho Han; Hee-Myong Ro (Environmental Science and Pollution Research, 2018)

Hymenobacter agri sp. nov., a novel bacterium isolated from soil - Jigon Han; Leonid N. Ten; Dong Hoon Lee; In-Kyu Kang; Hee-Young Jung (Antonie van Leeuwenhoek, 2018)

Diagnostic usefulness of bronchoalveolar lavage fluid xpert MTB/RIF in pauci-bacillary pulmonary tuberculosis - Jeongmin Hong; Seung Hyun Lee; Byung-Han Ryu; Min Jae Kim; Kyung-Wook Jo; Yong Pil Chong; Sang-Oh Lee; Sang-Ho Choi; Tae Sun Shim; Yang Soo Kim; Jun Hee Woo; Sung-Han Kim (Infectious Diseases, 2018)

Piperlongumine Improves Lipopolysaccharide-Induced Amyloidogenesis by Suppressing NF-KappaB Pathway - Sun Mi Gu; Hee Pom Lee; Young Wan Ham; Dong Ju Son; Hoi Yeong Kim; Ki Wan Oh; Sang-Bae Han; Jaesuk Yun; Jin Tae Hong (NeuroMolecular Medicine, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Comparison of resting egg gene expression with different hatchability related to salinity variations in the marine rotifer Brachionus manjavacas - Chengyan Han; Hee-Jin Kim; Koushirou Suga; Mingyou Li; Atsushi Hagiwara (Fisheries Science, 2018)

Correction to: Targeted next-generation sequencing for identifying genes related to horse temperament - Soyoung Song; Dong‑Yep Oh; Gil‑Jae Cho; Dong Hee Kim; Yong‑Soo Park; Kyudong Han (Genes & Genomics, 2018)

Virulence properties of uropathogenic Escherichia coli isolated from children with urinary tract infection in Korea - Dong Ho Kim; Bindu Subhadra; Hee Young Kang; Kyungho Woo; Jaeseok Kim; Yeo-Jin Son; Kyung Mok Sohn; Hwa-Jung Kim; Kyudong Han; Man Hwan Oh; Chul Hee Choi (Genes & Genomics, 2018)

Complete genome sequence of uropathogenic Escherichia coli isolate UPEC 26-1 - Bindu Subhadra; Dong Ho Kim; Jaeseok Kim; Kyungho Woo; Kyung Mok Sohn; Hwa-Jung Kim; Kyudong Han; Man Hwan Oh; Chul Hee Choi (Genes & Genomics, 2018)

Diagnostic usefulness of the QuantiFERON-TB gold in-tube test (QFT-GIT) for tuberculous vertebral osteomyelitis - Sungim Choi; Kyung Hwa Jung; Hyo-Ju Son; Seung Hyun Lee; Jung Min Hong; Min Chul Kim; Min Jae Kim; Yong Pil Chong; Heungsup Sung; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (Infectious Diseases, 2018)

BPH1, a novel substrate receptor of CRL3, plays a repressive role in ABA signal transduction - Og-Geum Woo; Soon-Hee Kim; Seok Keun Cho; Sang-Hoon Kim; Han Nim Lee; Taijoon Chung; Seong Wook Yang; Jae-Hoon Lee (Plant Molecular Biology, 2018)

Transcriptome analysis of the threatened snail Ellobium chinense reveals candidate genes for adaptation and identifies SSRs for conservation genetics - Se Won Kang; Bharat Bhusan Patnaik; So Young Park; Hee-Ju Hwang; Jong Min Chung; Min Kyu Sang; Hye Rin Min; Jie Eun Park; Jiyeon Seong; Yong Hun Jo; Mi Young Noh; Jong Dae Lee; et al. (Genes & Genomics, 2018)

Effect of cerebral embolus size on the timing of cardiac surgery for infective endocarditis in patients with neurological complications - Yong Kyun Kim; Choong Gon Choi; Jiwon Jung; Shi Nae Yu; Ju Young Lee; Yong Pil Chong; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jun Hee Woo; Yang Soo Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2018)
Photodynamic therapy (PDT) is performed using a photosensitizer and light of specific wavelength in the presence of oxygen to generate singlet oxygen and reactive oxygen species(ROS) in the cancer cells. The accumulated photosensitizers in target sites induce ROS generation upon light activation, then the generated cytotoxic reactive oxygen species lead to tumor cell death via apoptosis or necrosis, and damages the target sites which results tumor destruction. As a consequence, the PDT-mediated cell death is associated with anti-tumor immune response. In this paper, the effects of PDT and immune response on tumors are reviewed. Activation of an immune response regarding the innate and adaptive immune response, interaction with immune cells and tumor cells that associated with antitumor efficacy of PDT are also discussed.

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Effects of 1-methylcyclopropene (1-MCP) and polyethylene (PE) film liner treatments on the fruit quality of cold-stored ‘Gamhong’ apples - Kyoung-ook Kim; Jingi Yoo; Jinwook Lee; Nay Myo Win; Seulgi Ryu; Jeung-Sul Han; Hee-Young Jung; Myoung-Gun Choung; Yong-Deuk Kwon; Dong Hoon Lee; In-Kyu Kang (Horticulture, Environment, and Biotechnology, 2018)

Uliginosibacterium sangjuense sp. nov., isolated from sediment of the Nakdong River - Ji-Hye Han; Kiwoon Baek; Young-Hee Ahn; Wook Jae Lee; Mi-Hwa Lee (Antonie van Leeuwenhoek, 2018)

Erratum to "Anti-Inflammatory Effect of 3-Bromo-4,5-Dihydroxybenzaldehyde, a Component of Polysiphonia morrowii, In Vivo and In Vitro " [Toxicol. Res. 33 (2017) 325-332] - Na-Jin Kang; Sang-Chul Han; Hyun-Jae Kang; Geum Ko; Weon-Jong Yoon; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2018)

Endosulfan Plant Uptake Suppression Effect on Char Amendment in Oriental Radish - Geun-Hyoung Choi; Deuk-Yeong Lee; Dong-Cheol Seo; Leesun Kim; Sung-Jin Lim; Song-Hee Ryu; Byung-Jun Park; Jeong-Han Kim; Jin Hyo Kim (Water, Air, & Soil Pollution, 2018)

Nanomedicines: current status and future perspectives in aspect of drug delivery and pharmacokinetics - Young Hee Choi; Hyo-Kyung Han (Journal of Pharmaceutical Investigation, 2018)
Nanomedicines have evolved into various forms including dendrimers, nanocrystals, emulsions, liposomes, solid lipid nanoparticles, micelles, and polymeric nanoparticles since their first launch in the market. Widely highlighted benefits of nanomedicines over conventional medicines include superior efficacy, safety, physicochemical properties, and pharmacokinetic/pharmacodynamic profiles of pharmaceutical ingredients. Especially, various kinetic characteristics of nanomedicines in body are further influenced by their formulations. This review provides an updated understanding of nanomedicines with respect to delivery and pharmacokinetics. It describes the process and advantages of the nanomedicines approved by FDA and EMA. New FDA and EMA guidelines will also be discussed. Based on the analysis of recent guidelines and approved nanomedicines, key issues in the future development of nanomedicines will be addressed.

Current Understanding of Stem Cell and Secretome Therapies in Liver Diseases - Dongkyu Kim; Gun-Sik Cho; Choongseong Han; Dong-Hyuk Park; Hee-Kyung Park; Dong-Hun Woo; Jong-Hoon Kim (Tissue Engineering and Regenerative Medicine, 2017)

Distinct Histone Modifications Modulate DEFB1 Expression in Human Vaginal Keratinocytes in Response to Lactobacillus spp. - Jaehyouk Lee; Ara Jang; Jin Wook Kim; Jun Hyun Han; Byung Hee Chun; Hye Su Jung; Che Ok Jeon; Soon Chul Myung (Probiotics and Antimicrobial Proteins, 2017)

(E)-2-Methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) Phenol Ameliorates LPS-Mediated Memory Impairment by Inhibition of STAT3 Pathway - Ji Yeon Choi; Chul Ju Hwang; Do Yeon Lee; Sun Mi Gu; Hee Pom Lee; Dong Young Choi; Ki Wan Oh; Sang-Bae Han; Jin Tae Hong (NeuroMolecular Medicine, 2017)

Fucoidan inhibits lipopolysaccharide-induced inflammatory responses in RAW 264.7 macrophages and zebrafish larvae - Jin-Woo Jeong; Su Jung Hwang; Min Ho Han; Dae-Sung Lee; Jong Su Yoo; Il-Whan Choi; Hee-Jae Cha; Suhkmann Kim; Heui-Soo Kim; Gi-Young Kim; You-Jin Jeon; Hyo-Jong Lee; et al. (Molecular & Cellular Toxicology, 2017)

Targeted next-generation sequencing for identifying genes related to horse temperament - Soyoung Song; Dong-Yep Oh; Gil-Jae Cho; Dong Hee Kim; Yong-Soo Park; Kyudong Han (Genes & Genomics, 2017)

Multiclass mycotoxin analysis in edible oils using a simple solvent extraction method and liquid chromatography with tandem mass spectrometry - Taeyong Eom; Hyun-Deok Cho; Junghyun Kim; Mihee Park; Jinyoung An; Moosung Kim; Sheen-Hee Kim; Sang Beom Han (Food Additives & Contaminants: Part A, 2017)

Fluorescent Labeling of Protein Using Blue-Emitting 8-Amino-BODIPY Derivatives - Dokyoung Kim; Donghee Ma; Muwoong Kim; Yuna Jung; Na Hee Kim; Chiho Lee; Seo Won Cho; Sungnam Park; Youngbuhm Huh; Junyang Jung; Kyo Han Ahn (Journal of Fluorescence, 2017)

Alzheimer’s disease related genes during primate evolution - Dong Hee Kim; Jeong-An Gim; Kwang Hee Kim; Chang Woo Han; Se Bok Jang; Heui-Soo Kim (Genes & Genomics, 2017)

Lamivudine Therapy Exacerbates Bilirubinemia in Patients Underlying Severely Advanced Hepatitis - Young Hee Choi; Chang Ho Lee; Myong Suk Ko; Hyun Joo Han; Sang Geon Kim (Toxicological Research, 2017)

Anti-Inflammatory Effect of 3-Bromo-4,5-Dihydroxybenzaldehyde, a Component of Polysiphonia morrowii , In Vivo and In Vitro - Na-Jin Kang; Sang-Chul Han; Hyun-Jae Kang; Geum Ko; Weon-Jong Yoon; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2017)

A comparative study on generating simulated Landsat NDVI images using data fusion and regression method—the case of the Korean Peninsula - Mi Hee Lee; Soo Bong Lee; Yang Dam Eo; Sun Woong Kim; Jung-Hun Woo; Soo Hee Han (Environmental Monitoring and Assessment, 2017)

Lipid Emulsion Inhibits Apoptosis Induced by a Toxic Dose of Verapamil via the Delta-Opioid Receptor in H9c2 Rat Cardiomyoblasts - Seong-Ho Ok; Mun Hwan Choi; Il-Woo Shin; Soo Hee Lee; Sebin Kang; Jiah Oh; Jeong Yeol Han; Ju-Tae Sohn (Cardiovascular Toxicology, 2017)

Epidermal Growth Factor (EGF)-Like Repeats and Discoidin I-Like Domains 3 (EDIL3): A Potential New Therapeutic Tool for the Treatment of Keloid Scars - Yeon Hee Ryu; Yoon Jae Lee; Ki-Joo Kim; Su Jin Lee; Yu-Na Han; Jong-Won Rhie (Tissue Engineering and Regenerative Medicine, 2017)

Factors predicting life-threatening infections with respiratory syncytial virus in adult patients - Se Yoon Park; Taeeun Kim; Young Rock Jang; Min-Chul Kim; Yong Pil Chong; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Jun Hee Woo; Sung-Han Kim (Infectious Diseases, 2017)

Spontaneous Peripheral Ameloblastic Odontoma in a Male Sprague-Dawley Rat - Yinghua Li; Han-Ik Bae; Hak-Soo Kim; Min-Soo Kang; Bo-Ho Gong; Won-Hee Jung; Sranna Lee; Jin-Sook Bae; Kap-Ho Kim; Si-Whan Song; Jae-Hyun Lee; Boo-Hyon Kang (Toxicological Research, 2017)

Inhalation Toxicity of Bisphenol A and Its Effect on Estrous Cycle, Spatial Learning, and Memory in Rats upon Whole-Body Exposure - Yong Hyun Chung; Jeong Hee Han; Sung-Bae Lee; Yong-Hoon Lee (Toxicological Research, 2017)

Development of GNSS/WSS/YRS integration algorithm for land vehicle positioning - Joong-hee Han; Jay Hyoun Kwon; Chang-Ki Hong; Yong Lee (Spatial Information Research, 2017)

Molecular marker analysis of Cynanchum wilfordii and C. auriculatum using the simple ARMS-PCR method with mismatched primers - Eun-Heui Han; Soo Jin Lee; Man Bae Kim; Yong-Wook Shin; Yun-Hee Kim; Shin-Woo Lee (Plant Biotechnology Reports, 2017)

Selecting suitable sites for mountain ginseng (Panax ginseng) cultivation by using geographically weighted logistic regression - Hee Han; Kwang-min Jang; Joo-sang Chung (Journal of Mountain Science, 2017)

PsCYP1 of marine red alga Pyropia seriata (Bangiales, Rhodophyta) confers salt and heat tolerance in Chlamydomonas - Ha-Nul Lee; Sun Hee Kim; Yun-Jeong Han; Sungoh Im; Won-Joong Jeong; Eun Jeong Park; Mi Sook Hwang; Dong-Woog Choi (Journal of Applied Phycology, 2017)

Erratum to: A de novo 3p13 deletion induced by a complex chromosomal rearrangement combined with a pericentric inversion of chromosome 3, inv(3)(p13q12), and a translocation between chromosome 3 and 8, t(3;8)(q13.1;q24.2), in a child with developmental delay - Kye Hee Cho; Sung Han Shim; MinYoung Kim (Genes & Genomics, 2017)

A de novo 3p13 deletion induced by a complex chromosomal rearrangement combined with a pericentric inversion of chromosome, inv(3)(p13q12), and a translocation between chromosome 3 and 8, t(3;8)(q13.1;q24.2), in a child with developmental delay - Kye Hee Cho; Sung Han Shim; MinYoung Kim (Genes & Genomics, 2017)

Significance of diazotrophic plant growth-promoting Herbaspirillum sp. GW103 on phytoextraction of Pband Zn by Zea mays L. - Loganathan Praburaman; Sung-Hee Park; Min Cho; Kui-Jae Lee; Jeong-Ae Ko; Sang-Sub Han; Sang-Hyun Lee; Seralathan Kamala-Kannan; Byung-Taek Oh (Environmental Science and Pollution Research, 2017)

Biocatalytic characterization of an endo-β-1,4-mannanase produced by Paenibacillus sp. strain HY-8 - Do Young Kim; Chung Wook Chung; Han-Young Cho; Young Ha Rhee; Dong-Ha Shin; Kwang-Hee Son; Ho-Yong Park (Biotechnology Letters, 2017)

Functional identification of oleate 12-desaturase and ω-3 fatty acid desaturase genes from Perilla frutescens var. frutescens - Kyeong-Ryeol Lee; Yongjik Lee; Eun-Ha Kim; Seul-Bee Lee; Kyung Hee Roh; Jong-Bum Kim; Han-Chul Kang; Hyun Uk Kim (Plant Cell Reports, 2016)

Overexpression of Telomerase Reverse Transcriptase Induces Autism-like Excitatory Phenotypes in Mice - Ki Chan Kim; Jeehae Rhee; Jong-Eun Park; Dong-Keun Lee; Chang Soon Choi; Ji-Woon Kim; Han-Woong Lee; Mi-Ryoung Song; Hee Jeong Yoo; ChiHye Chung; Chan Young Shin (Molecular Neurobiology, 2016)

Expression of exosomal and cellular microRNAs: as biomarkers for toluene, ethylbenzene, xylene (TEX) exposure - Jung-hee Lim; Mi-Kyung Song; Yoon Cho; Woong Kim; Sung Ok Han; Jae-Chun Ryu (Molecular & Cellular Toxicology, 2016)

The 12 September 2016 Gyeongju earthquakes: 2. Temporary seismic network for monitoring aftershocks - Kwang-Hee Kim; Tae-Seob Kang; Junkee Rhie; YoungHee Kim; Yongcheol Park; Su Young Kang; Minhui Han; Jeongmu Kim; Jechan Park; Minook Kim; ChangHwan Kong; Dabeen Heo; et al. (Geosciences Journal, 2016)

Metabolic engineering to produce γ-linolenic acid in Brassica napus using a Δ6-desaturase from pike eel - Sun Hee Kim; Kyung Hee Roh; Kyeong-Ryeol Lee; Han-Chul Kang; Hyun Uk Kim; Jong Bum Kim (Plant Biotechnology Reports, 2016)

Construction of a draft reference transcripts of onion (Allium cepa) using long-read sequencing - Seong-Han Sohn; Yul-Kyun Ahn; Tae-Ho Lee; Jong-Eun Lee; Min-Hee Jeong; Chae-Hwa Seo; Romika Chandra; Young-Seok Kwon; Cheol-Woo Kim; Do-Sun Kim; So-Youn Won; Jung Sun Kim; et al. (Plant Biotechnology Reports, 2016)

Transcriptome sequencing and de novo characterization of Korean endemic land snail, Koreanohadra kurodana for functional transcripts and SSR markers - Se Won Kang; Bharat Bhusan Patnaik; Hee-Ju Hwang; So Young Park; Jong Min Chung; Dae Kwon Song; Hongray Howrelia Patnaik; Jae Bong Lee; Changmu Kim; Soonok Kim; Hong Seog Park; Yeon Soo Han; et al. (Molecular Genetics and Genomics, 2016)

Fluxes of nutrients and trace metals across the sediment-water interface controlled by sediment-capping agents: bentonite and sand - Junho Han; Hee-Myong Ro; Kyung Hwa Cho; Kyoung-Woong Kim (Environmental Monitoring and Assessment, 2016)

A diagnostic algorithm for tuberculous pleurisy using the ELISPOT assay on peripheral blood and pleural effusion - Min-Chul Kim; Sun-Mi Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Jun Hee Woo; Sung-Han Kim (Infectious Diseases, 2016)

Cereblon in health and disease - Hyoung Kyu Kim; Tae Hee Ko; Bayalagmaa Nyamaa; Sung Ryul Lee; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Chul-Seung Park; Bernd Nilius; Jin Han (Pflügers Archiv - European Journal of Physiology, 2016)

Subacute Inhalation Toxicity of 3-Methylpentane - Yong Hyun Chung; Seo-Ho Shin; Jeong Hee Han; Yong-Hoon Lee (Toxicological Research, 2016)

A new secoiridoid glycoside from the fruits of Cornus officinalis (Cornaceae) - Ji-Yeon Park; Ah-Reum Han; Yun-Seo Kil; Unwoo Kang; Se-Hee Kim; Sang-Jip Nam; Eun Kyoung Seo (Natural Product Research, 2016)

Elucidating the triplicated ancestral genome structure of radish based on chromosome-level comparison with the Brassica genomes - Young-Min Jeong; Namshin Kim; Byung Ohg Ahn; Mijin Oh; Won-Hyong Chung; Hee Chung; Seongmun Jeong; Ki-Byung Lim; Yoon-Jung Hwang; Goon-Bo Kim; Seunghoon Baek; Sang-Bong Choi; et al. (Theoretical and Applied Genetics, 2016)

An atypical 12q24.31 microdeletion implicates six genes including a histone demethylase KDM2B and a histone methyltransferase SETD1B in syndromic intellectual disability - Jonathan D. J. Labonne; Kang-Han Lee; Shigeki Iwase; Il-Keun Kong; Michael P. Diamond; Lawrence C. Layman; Cheol-Hee Kim; Hyung-Goo Kim (Human Genetics, 2016)

Performance evaluation of CDN method in V-World web service as spatial information open platform service - Han-sol Jang; Jun-hee Go; Wook-rak Jung; In-sung Jang (Spatial Information Research, 2016)

Development of novel tetra- and trinucleotide microsatellite markers for giant grouper Epinephelus lanceolatus using 454 pyrosequencing - Keun-Sik Kim; Choong Hwan Noh; Shin-Joo Moon; Seung-Hee Han; In-Chul Bang (Molecular Biology Reports, 2016)

LED light for in vitro and ex vitro efficient growth of economically important highbush blueberry (Vaccinium corymbosum L.) - Cao Dinh Hung; Chang-Hee Hong; Seon-Ki Kim; Kyu-Han Lee; Jea-Young Park; Min-Woo Nam; Dae-Ho Choi; Hye-In Lee (Acta Physiologiae Plantarum, 2016)

Effects of Formulation Variables on the Particle Size and Drug Encapsulation of Imatinib-Loaded Solid Lipid Nanoparticles - Biki Gupta; Bijay Kumar Poudel; Shiva Pathak; Jin Wook Tak; Hee Hyun Lee; Jee-Heon Jeong; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (AAPS PharmSciTech, 2016)

External Application of Apo-9'-fucoxanthinone, Isolated from Sargassum muticum, Suppresses Inflammatory Responses in a Mouse Model of Atopic Dermatitis - Sang-Chul Han; Na-Jin Kang; Weon-Jong Yoon; Sejin Kim; Min-Chull Na; Young-Sang Koh; Jin-Won Hyun; Nam-Ho Lee; Mi-Hee Ko; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2016)

Development of molecular markers, based on chloroplast and ribosomal DNA regions, to discriminate three popular medicinal plant species, Cynanchum wilfordii, Cynanchum auriculatum, and Polygonum multiflorum - Eun-Heui Han; KyeMan Cho; YoungMin Goo; ManBae Kim; Young-Wook Shin; Yun-Hee Kim; Shin-Woo Lee (Molecular Biology Reports, 2016)

Isolation of a lignan-enriched fraction from Schisandra chinensis and its effective solubilization via poloxamer 407-based solid dispersion formulation - Young Hee Choi; Young-Won Chin; Seung Jun Yang; Pisey Pel; You-Jin Kim; Eun Young Kim; Hyo-Kyung Han (Journal of Pharmaceutical Investigation, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Mycobacterium avium MAV2052 protein induces apoptosis in murine macrophage cells through Toll-like receptor 4 - Kang-In Lee; Han-Gyu Choi; Yeo-Jin Son; Jake Whang; Kwangwook Kim; Heat Sal Jeon; Hye-Soo Park; Yong Woo Back; Seunga Choi; Seong-Woo Kim; Chul Hee Choi; Hwa-Jung Kim (Apoptosis, 2016)

Development of Solid Self-Emulsifying Formulation for Improving the Oral Bioavailability of Erlotinib - Duy Hieu Truong; Tuan Hiep Tran; Thiruganesh Ramasamy; Ju Yeon Choi; Hee Hyun Lee; Cheol Moon; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (AAPS PharmSciTech, 2016)

Suppression of lytic replication of Kaposi’s sarcoma-associated herpesvirus by autophagy during initial infection in NIH 3T3 fibroblasts - Gun-Hee Jang; Jihui Lee; Na-Yeon Kim; Jae-Hyeon Kim; Jung-Yong Yeh; Minsub Han; Soon Kil Ahn; Hara Kang; Michael Lee (Archives of Virology, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

Matrix Metalloproteinase-8 is a Novel Pathogenetic Factor in Focal Cerebral Ischemia - Jeong Eun Han; Eun-Jung Lee; Eunjung Moon; Jong Hoon Ryu; Ji Woong Choi; Hee-Sun Kim (Molecular Neurobiology, 2016)

Genetic and functional characterization of an extracellular modular GH6 endo-β-1,4-glucanase from an earthworm symbiont, Cellulosimicrobium funkei HY-13 - Do Young Kim; Min Ji Lee; Han-Young Cho; Jong Suk Lee; Mi-Hwa Lee; Chung Wook Chung; Dong-Ha Shin; Young Ha Rhee; Kwang-Hee Son; Ho-Yong Park (Antonie van Leeuwenhoek, 2016)

Transcriptome analysis of the short-term photosynthetic sea slug Placida dendritica - Ji Hee Han; Tatyana A. Klochkova; Jong Won Han; Junbo Shim; Gwang Hoon Kim (Algae, 2015)

Ca2+ clearance by plasmalemmal NCLX, Li+-permeable Na+/Ca2+ exchanger, is required for the sustained exocytosis in rat insulinoma INS-1 cells - Young-Eun Han; Shin-Young Ryu; Sun-Hyun Park; Kyu-Hee Lee; Suk-Ho Lee; Won-Kyung Ho (Pflügers Archiv - European Journal of Physiology, 2015)

Relative paleointensity data from the late Holocene deltaic sediments in Korea - Seungwon Shin; Yong-Hee Park; Jong-Hyun Park; Soojeong Han (Geosciences Journal, 2015)

Erratum to: Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Influence of Flaxseed Oil on Fecal Microbiota, Egg Quality and Fatty Acid Composition of Egg Yolks in Laying Hens - Jun-Yeong Lee; Sang-Kee Kang; Yun-Jeong Heo; Do-Woon Shin; Tae-Eun Park; Geon Goo Han; Gwi-Deuk Jin; Ho-Bin Lee; Eojin Jung; Hee Sung Kim; Yerim Na; Eun Bae Kim; et al. (Current Microbiology, 2015)

Influence of starvation on heart contractility and corticosterone level in rats - Sung Ryul Lee; Tae Hee Ko; Hyoung Kyu Kim; Jubert Marquez; Kyung Soo Ko; Byoung Doo Rhee; Jin Han (Pflügers Archiv - European Journal of Physiology, 2015)

A Novel Compound ITC-3 Activates the Nrf2 Signaling and Provides Neuroprotection in Parkinson’s Disease Models - Ji Ae Lee; Hyo Jin Son; Ki Duk Park; Se Hee Han; Nari Shin; Ji Hyun Kim; Hye Ri Kim; Dong Jin Kim; Onyou Hwang (Neurotoxicity Research, 2015)

Statistical modeling for selecting a superior working dog using microsatellite loci - Hoim Jeong; Kyeongjun Lee; Bong-Hwan Choi; Hee-Eun Lee; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; Youngseuk Cho; Heui-Soo Kim (Genes & Genomics, 2015)

Complete genome sequence and comparative genome analysis of Streptococcus parauberis KCTC11980 - Jung Soo Seo; Mun Gyeong Kwon; Jee Youn Hwang; Sung Hee Jung; Hyun Ja Han; Myoung Sug Kim; Jeong-Wan Do; Myoung Ae Park; Dong-Wook Kim; Wang Sik Cho; Kyungho Lee (Genes & Genomics, 2015)

Endosulfan induces COX-2 expression via NADPH oxidase and the ROS, MAPK, and Akt pathways - Hyung Gyun Kim; Young Ran Kim; Jin Hee Park; Tilak Khanal; Jae Ho Choi; Minh Truong Do; Sun Woo Jin; Eun Hee Han; Young Ho Chung; Hye Gwang Jeong (Archives of Toxicology, 2015)

Role of the MoYAK 1 protein kinase gene in M agnaporthe oryzae development and pathogenicity - Joon‐Hee Han; Hye‐Min Lee; Jong‐Hwan Shin; Yong‐Hwan Lee; Kyoung Su Kim (Environmental Microbiology, 2015)
Summary Conidiation and appressorium differentiation are key processes for polycyclic dissemination and infection in many pathogens. Our previous study using DNA microarray led to the discovery of the MoYAK 1 gene in M agnaporthe oryzae that is orthologous to YAK 1 in S accharomyces cerevisiae . Although the mechanistic roles of YAK 1 in S . cerevisiae have been described, roles of MoYAK 1 in M . oryzae , a phytopathogenic fungus responsible for rice blast, remain uncharacterized. Targeted disruption of MoYAK 1 results in pleiotropic defects in M . oryzae development and pathogenicity. The Δ M oyak1 mutant exhibits a severe reduction in aerial hyphal formation and conidiation. Conidia in the Δ M oyak1 are delayed in germination and demonstrate decreased glycogen content in a conidial age‐dependent manner. The expression of hydrophobin‐coding genes is dramatically changed in the Δ M oyak1 mutant, leading to a loss of surface hydrophobicity. Unlike the complete inability of the Δ M oyak1 mutant to develop appressoria on an inductive surface, the mutant forms appressoria of abnormal morphology in response to exogenous cyclic adenosine‐5′‐monophosphate and host‐driven signals, which are all defective in penetrating host tissues due to abnormalities in glycogen and lipid metabolism, turgor generation and cell wall integrity. These data indicate that MoYAK 1 is a protein kinase important for the development and pathogenicity of M . oryzae .

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Qualitative Analysis of Additives in Plastic Marine Debris and Its New Products - Manviri Rani; Won Joon Shim; Gi Myung Han; Mi Jang; Najat Ahmed Al-Odaini; Young Kyong Song; Sang Hee Hong (Archives of Environmental Contamination and Toxicology, 2015)

Distribution and Size Relationships of Plastic Marine Debris on Beaches in South Korea - Jongmyoung Lee; Jong Su Lee; Yong Chang Jang; Su Yeon Hong; Won Joon Shim; Young Kyung Song; Sang Hee Hong; Mi Jang; Gi Myung Han; Daeseok Kang; Sunwook Hong (Archives of Environmental Contamination and Toxicology, 2015)

Occurrence and Distribution of Microplastics in the Sea Surface Microlayer in Jinhae Bay, South Korea - Young Kyoung Song; Sang Hee Hong; Mi Jang; Gi Myung Han; Won Joon Shim (Archives of Environmental Contamination and Toxicology, 2015)

Toxic response of graphene nanoplatelets in vivo and in vitro - Eun-Jung Park; Gwang-Hee Lee; Beom Seok Han; Byoung-Seok Lee; Somin Lee; Myung-Haing Cho; Jae-Ho Kim; Dong-Wan Kim (Archives of Toxicology, 2015)

Effect of low temperature on Schwann-like cell differentiation of bone marrow mesenchymal stem cells - Hee-Hoon Yoon; Mi-Jung Han; Jung-Keug Park; Jong-Ho Lee; Young-Kwon Seo (Tissue Engineering and Regenerative Medicine, 2015)

Erratum to: Boron availability alters its distribution in plant parts of tomato - Eun-Young Choi; Hae-In Park; Jin-Hee Ju; Yong-Han Yoon (Horticulture, Environment, and Biotechnology, 2015)

Therapeutic dosage assessment based on population pharmacokinetics of a novel single-dose transdermal donepezil patch in healthy volunteers - Hee Youn Choi; Yo Han Kim; Donghyun Hong; Seong Su Kim; Kyun-Seop Bae; Hyeong-Seok Lim (European Journal of Clinical Pharmacology, 2015)

Characterization of a flavin-containing monooxygenase from Corynebacterium glutamicum and its application to production of indigo and indirubin - Sisi Patricia Lolita Ameria; Hye Sook Jung; Hee Sook Kim; Sang Soo Han; Hak Sung Kim; Jin Ho Lee (Biotechnology Letters, 2015)

Trace element analysis of three tissues from Eurasian otters (Lutra lutra) in South Korea - Sukmo Kang; Jung-Hoon Kang; Soohee Kim; Seung Heon Lee; Seungwoo Lee; Hee Jeong Yu; Su-Jun Oh; Jung-Duck Park; Ki-Hoan Nam; Sung Yong Han; Jong-Deock Lim; Doug-Young Ryu (Ecotoxicology, 2015)

Depressive-Like Behaviors in a Rat Model of Chronic Cerebral Hypoperfusion - Sang Rim Lee; Boryoung Choi; Saswati Paul; Ju-Ha Seo; Dong Bin Back; Jung-Soo Han; Dong-Hee Choi; Kyoung Ja Kwon; Chan Young Shin; Jongmin Lee; Seol-Heui Han; Hahn Young Kim (Translational Stroke Research, 2015)

Bioactive injectables based on calcium phosphates for hard tissues: A recent update - Roman A. Perez; Song-Hee Shin; Cheol-Min Han; Hae-Won Kim (Tissue Engineering and Regenerative Medicine, 2015)

The influences of CYP2D6 genotypes and drug interactions on the pharmacokinetics of venlafaxine: exploring predictive biomarkers for treatment outcomes - Fen Jiang; Hae-Deun Kim; Han-Sung Na; Seok-Yong Lee; Doo-Won Seo; Jong-Yeol Choi; Ji-Hye Ha; Hee-Jung Shin; Young-Hoon Kim; Myeon-Woo Chung (Psychopharmacology, 2015)

NNC 55-0396, a T-type Ca2+ channel inhibitor, inhibits angiogenesis via suppression of hypoxia-inducible factor-1α signal transduction - Ki Hyun Kim; Dongyoung Kim; Ju Yeol Park; Hye Jin Jung; Yong-Hee Cho; Hyoung Kyu Kim; Jin Han; Kang-Yell Choi; Ho Jeong Kwon (Journal of Molecular Medicine, 2015)

Boron availability alters its distribution in plant parts of tomato - Eun-Young Choi; Hae-In Park; Jin-Hee Ju; Yong-Han Yoon (Horticulture, Environment, and Biotechnology, 2015)

Population pharmacokinetic and pharmacodynamic model of propofol externally validated in children - Byung-Moon Choi; Hyun-Gu Lee; Hyo-Jin Byon; Soo-Han Lee; Eun-Kyung Lee; Hee-Soo Kim; Gyu-Jeong Noh (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Erratum to: Characterization of a GH family 8 β-1,3-1,4-glucanase with distinctive broad substrate specificity from Paenibacillus sp. X4 - Han Beur Na; Won Kyeong Jung; Yu Seok Jeong; Hee Jung Kim; Sung Kyum Kim; Jungho Kim; Han Dae Yun; Jung-Kul Lee; Hoon Kim (Biotechnology Letters, 2015)

Characterization of a GH family 8 β-1,3-1,4-glucanase with distinctive broad substrate specificity from Paenibacillus sp. X4 - Han Beur Na; Won Kyeong Jung; Yu Seok Jeong; Hee Jung Kim; Sung Kyum Kim; Jungho Kim; Han Dae Yun; Jung-Kul Lee; Hoon Kim (Biotechnology Letters, 2015)

Direct sequencing for comprehensive screening of LDLR genetic polymorphisms among five ethnic populations - Jeong-Hyun Kim; Hyun Sub Cheong; Lyoung Hyo Kim; Hee Jung Shin; Han Sung Na; Myeon Woo Chung; Hyoung Doo Shin (Genes & Genomics, 2015)

Polymorphism analysis of tyrosine hydroxylase gene variable number of tandem repeats in various Korean dogs - Hee-Eun Lee; Bong-Hwan Choi; Dong-Hoon Lee; Yun-Jeong Kwon; Jungwoo Eo; Yuri Choi; Hoim Jeong; Jeong-An Gim; Tae-Hun Kim; Ji-Hong Ha; Kook-Il Han; Heui-Soo Kim (Genes & Genomics, 2015)

FLT3 expression and IL10 promoter polymorphism in acute myeloid leukemia with RUNX1-RUNX1T1 - Myungshin Kim; Jiyeon Kim; Jung Rok Kim; Eunhee Han; Joonhong Park; Jihyang Lim; Yonggoo Kim; Kyungja Han; Hee-Je Kim; Woo-Sung Min; Bin Cho (Molecular Biology Reports, 2015)

Novel mutations and clinical outcomes of copper-histidine therapy in Menkes disease patients - Ja Hye Kim; Beom Hee Lee; Yoo-Mi Kim; Jin-Ho Choi; Gu-Hwan Kim; Chong Kun Cheon; Han-Wook Yoo (Metabolic Brain Disease, 2015)

iNSC suppress macrophage-induced inflammation by repressing COX-2 - Jin Hee Kim; Woong Sun; Dong Wook Han; Hong-Joo Moon; Jangbo Lee (In Vitro Cellular & Developmental Biology - Animal, 2015)

Characterization and chemical control of soft rot disease caused by Pantoea sp. strain PPE7 in Pleurotus eryngii mushroom crops - Min Keun Kim; Song Hee Lee; Young Han Lee; HyeRan Kim; JeongYeo Lee; Il Rae Rho (European Journal of Plant Pathology, 2015)

Sedimentary organic carbon budget of coastal sediments and the importance of benthic-pelagic coupling off Namhae Island in the South Sea of Korea - Jae Seong Lee; Jeong Hee Han; Sung-Uk An; Taehee Na; Jung No Kwon; Eun-Soo Kim (Ocean Science Journal, 2014)

Evolution and expression analysis of the soybean glutamate decarboxylase gene family - Tae Kyung Hyun; Seung Hee Eom; Xiao Han; Ju-Sung Kim (Journal of Biosciences, 2014)

Genome-wide analyses of DNA-binding proteins harboring AT-hook motifs and their functional roles in the rice blast pathogen, Magnaporthe oryzae - Jong-Hwan Shin; Joon-Hee Han; Kyoung Su Kim (Genes & Genomics, 2014)

Statistical analysis and genetic diversity of three dog breeds using simple sequence repeats - Hoim Jeong; Bong-Hwan Choi; Jungwoo Eo; Yun-Jeong Kwon; Hee-Eun Lee; Yuri Choi; Jeong-An Gim; Tae-Hun Kim; Hwan-Hoo Seong; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; et al. (Genes & Genomics, 2014)

Analysis of Cyazofamid and its Metabolite in the Environmental and Crop Samples Using LC–MS/MS - Hyeri Lee; Eunhye Kim; Jong-Hwa Lee; Jeong Hee Sung; Hoon Choi; Jeong-Han Kim (Bulletin of Environmental Contamination and Toxicology, 2014)

Biosynthesis of pinene from glucose using metabolically-engineered Corynebacterium glutamicum - Min-Kyoung Kang; Jin-Hee Eom; Yunje Kim; Youngsoon Um; Han Min Woo (Biotechnology Letters, 2014)

Peroxisome-localized hepatitis Bx protein increases the invasion property of hepatocellular carcinoma cells - Jae-Min Han; Jung-Ah Kang; Min-Hee Han; Kyung-Hun Chung; Cho-Rong Lee; Woo-Keun Song; Youngsoo Jun; Sung-Gyoo Park (Archives of Virology, 2014)

Integrative assessment of sediment quality in terms of chemical contamination in Jinhae Bay, South Korea - Sang Hee Hong; Gi Myung Han; Un Hyuk Yim; Dhong-il Lim; Sung Yong Ha; Nam Sook Kim; Won Joon Shim (Ocean Science Journal, 2014)

Inhibition of lewis lung cancer cell growth and migration by fucoidan - Yong-seok Han; Jun Hee Lee; Hun Soo Chang; Sang Hun Lee (Molecular & Cellular Toxicology, 2014)

Spirosoma radiotolerans sp. nov., a Gamma-Radiation-Resistant Bacterium Isolated from Gamma Ray-Irradiated Soil - Jae-Jin Lee; Sathiyaraj Srinivasan; Sangyong Lim; Minho Joe; Seonghun Im; So Il Bae; Kyoung Ryun Park; Ji-Hee Han; Se-Hee Park; Bo-min Joo; Sol-Ji Park; Myung Kyum Kim (Current Microbiology, 2014)

Coexpression of multiple genes reconstitutes two pathways of very long-chain polyunsaturated fatty acid biosynthesis in Pichia pastoris - Sun Hee Kim; Kyung Hee Roh; Kwang-Soo Kim; Hyun Uk Kim; Kyeong-Ryeol Lee; Han-Chul Kang; Jong-Bum Kim (Biotechnology Letters, 2014)

Large-scale screening of rice accessions to evaluate resistance to bakanae disease - Myung-Hee Kim; Yeon-Jae Hur; Saes Beul Lee; Tackmin Kwon; Un-Ha Hwang; Soo-Kwon Park; Young-Nam Yoon; Jong-Hee Lee; Jun-Hyeon Cho; Dongjin Shin; Tae Heon Kim; Sang-Ik Han; et al. (Journal of General Plant Pathology, 2014)

Isolation and characterization of 26 novel polynucleotide microsatellites from short barbeled grunter (Hapalogenys nitens) for genetic analysis - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Conservation Genetics Resources, 2014)

Population genetic structure of the tongue sole (Cynoglossus semilaevis) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Assessing the potential suitability of forest stands as Kirengeshoma koreana habitat using MaxEnt - Hee Han; Seonhee Cho; Jungeun Song; Ara Seol; Hyejean Chung; Joonsun Kim; Joosang Chung (Landscape and Ecological Engineering, 2014)

Detection of Aichi virus in South Korea - Tae-Hee Han; Sang Hun Park; Eung-Soo Hwang; Gabor Reuter; Ju-Young Chung (Archives of Virology, 2014)

Large genomic rearrangement of BRCA1 and BRCA2 genes in familial breast cancer patients in Korea - Ja Young Cho; Dae-Yeon Cho; Sei Hyun Ahn; Su-Youn Choi; Inkyung Shin; Hyun Gyu Park; Jong Won Lee; Hee Jeong Kim; Jong Han Yu; Beom Seok Ko; Bo Kyung Ku; Byung Ho Son (Familial Cancer, 2014)

Proteomic analysis of the effect of retinoic acids on the human breast cancer cell line MCF-7 - Abu Hena Mostafa Kamal; Baek Soo Han; Jong-Soon Choi; Kun Cho; Sun Young Kim; Won Kon Kim; Sang Chul Lee; Kwang-Hee Bae (Molecular Biology Reports, 2014)

Detection of norovirus genogroup IV, klassevirus, and pepper mild mottle virus in sewage samples in South Korea - Tae-Hee Han; Se-Cheol Kim; Seong-Taek Kim; Chang-Hyun Chung; Ju-Young Chung (Archives of Virology, 2014)

Association between BH3 interacting domain death agonist (BID) gene polymorphism and ossification of the posterior longitudinal ligament in Korean population - Jinmann Chon; Jang-Hyeok Hong; Jinsung Kim; Yoo Jin Han; Byoung Wook Lee; Soo-Cheol Kim; Dong Hwan Kim; Seung Don Yoo; Hee-Sang Kim; Dong Hwan Yun (Molecular Biology Reports, 2014)

Growth and fruit production of asian pear trees grown on Y-, T-, and vase-training systems - Jang-Jeon Choi; Mengmeng Gu; Jin-Ho Choi; Jeom-Hwa Han; Sun-Hee Yim; Yoon-Kyeong Kim; Seok-Kyu Jung; Hyun-Sug Choi (Horticulture, Environment, and Biotechnology, 2014)

Identification and functional characterization of polyunsaturated fatty acid elongase (McELOVL5) gene from pike eel (Muraenesox cinereus) - Sun Hee Kim; So Yun Kim; Eui Ki Kim; Kyung Hee Roh; Jung-Bong Kim; Kwang-Soo Kim; Hyun Uk Kim; Kyeong-Ryeol Lee; Han-Chul Kang; Jong-Sug Park; Kyung Hyun Kim; Jong-Bum Kim (Biotechnology Letters, 2014)

(E)-2,4-Bis(p-hydroxyphenyl)-2-butenal inhibits tumor growth via suppression of NF-κB and induction of death receptor 6 - Jung Ok Ban; Young-Suk Jung; Dae Hwan Kim; Kyung-Ran Park; Hyung-Mun Yun; Nam Jin Lee; Hee Pom Lee; Jeong-Hyun Shim; Heon-Sang Jeong; Yun-Hee Lee; Young Wan Ham; Sang-Bae Han; et al. (Apoptosis, 2014)

Combined effects of an antioxidant and caspase inhibitor on the reversal of hepatic fibrosis in rats - Do Young Kim; Sook In Chung; Simon Weonsang Ro; Yong Han Paik; Jung Il Lee; Man Kil Jung; Min Goo Lee; Young Nyun Park; Kwan Sik Lee; Jung Gyu Park; Hee Dong Park; Kwang-Hyub Han (Apoptosis, 2013)

Oseltamivir-resistant influenza viruses isolated in South Korea from 2005 to 2010 - Han-Gil Cho; Jang-Hoon Choi; Hyun-Kyung Lee; Su-Kyoung Mun; Jong-Bok Lee; Eek-Hoon Jho; Chun Kang; Young-Hee Lim (Archives of Virology, 2013)

Systematic overestimation of Salicaceae seed survival using radicle emergence in response to drying and storage: implications for ex situ seed banking - Elena V. Popova; Du Hyun Kim; Sim Hee Han; Elena Moltchanova; Hugh W. Pritchard; Yong Pyo Hong (Acta Physiologiae Plantarum, 2013)

Congenital MTHFR deficiency causing early-onset cerebral stroke in a case homozygous for MTHFR thermolabile variant - Seung Jin Kim; Beom Hee Lee; Yoo-Mi Kim; Gu-Hwan Kim; Han-Wook Yoo (Metabolic Brain Disease, 2013)

Effects of framing coil shape, orientation, and thickness on intra-aneurysmal flow - Woowon Jeong; Moon Hee Han; Kyehan Rhee (Medical & Biological Engineering & Computing, 2013)

Class 3 inhibition of hERG K+ channel by caffeic acid phenethyl ester (CAPE) and curcumin - Seong Woo Choi; Kyung Su Kim; Dong Hoon Shin; Hae Young Yoo; Han Choe; Tae Hee Ko; Jae Boum Youm; Woo Kyung Kim; Yin Hua Zhang; Sung Joon Kim (Pflügers Archiv - European Journal of Physiology, 2013)

Characteristics of the urban heat island in a high-altitude metropolitan city, Ulaanbaatar, Mongolia - Gantuya Ganbat; Ji-Young Han; Young-Hee Ryu; Jong-Jin Baik (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Distribution of small plastic debris in cross-section and high strandline on Heungnam beach, South Korea - Nak Won Heo; Sang Hee Hong; Gi Myung Han; Sunwook Hong; Jongmyoung Lee; Young Kyung Song; Mi Jang; Won Joon Shim (Ocean Science Journal, 2013)

Inhibition of chrysanthemum axillary buds via transformation with the antisense tomato lateral suppressor gene is season dependent - Yeun Joo Huh; Bong Hee Han; Sang Kun Park; Su Young Lee; Mi Jung Kil; Chun Ho Pak (Horticulture, Environment, and Biotechnology, 2013)

House dust mite allergen Der f 2 induces interleukin-13 expression by activating the PI3K/Akt pathway - Eun Ji Ro; Pu-Hyeon Cha; Hyun-Yi Kim; Yong-Hee Cho; Jung-Won Park; Joong-Soo Han; Kang-Yell Choi (Immunologic Research, 2013)

Right-lateral strike-slip movement of the South Korea Plateau associated with the opening of the East Sea (Sea of Japan) - Dong-Lim Choi; Han-Joon Kim; Hyeong-Tae Jou; Seom-Kyu Jeong; Yong-Kuk Lee; Tae-Hee Lee (Ocean Science Journal, 2013)

Comparative analysis of physicochemicals and antioxidative properties in new red rice (Oryza sativa L. cv. Gunganghongmi) - Woo Duck Seo; Jun Young Kim; You-Chun Song; Jun-Hyun Cho; Ki Chang Jang; Sang-Ik Han; Ji-Eun Ra; Seong-Hwan Oh; Hyeon-Jung Kang; Byung-Joo Kim; Nam-In Baek; Rak-Hun Jeong; et al. (Journal of Crop Science and Biotechnology, 2013)

The role of glutathione in dichloromethane toxicity to Lemna paucicostata - Hyun-Hee Kim; Sae-Rong Kim; Areum Park; Taejun Han; Eun-Mi Choi (Toxicology and Environmental Health Sciences, 2013)

Association of the gene encoding stearoyl-CoA desaturase (SCD) with fatty acid composition in an intercross population between Landrace and Korean native pigs - Dyah Maharani; Hee-Bok Park; Jae-Bong Lee; Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee (Molecular Biology Reports, 2013)

High prevalence of amantadine-resistant influenza A virus isolated in Gyeonggi Province, South Korea, during 2005–2010 - Han-Gil Cho; Jang-Hoon Choi; Woon-Ho Kim; Hae-Kun Hong; Mi-Hye Yoon; Eek-Hoon Jho; Chun Kang; Young-Hee Lim (Archives of Virology, 2013)

The angiotensin receptor blocker and PPAR-γ agonist, telmisartan, delays inactivation of voltage-gated sodium channel in rat heart: novel mechanism of drug action - Hyoung Kyu Kim; Jae Boum Youm; Sung Ryul Lee; Se Eun Lim; Sun-Young Lee; Tae Hee Ko; Le Thanh Long; Bernd Nilius; Du Nam Won; Jung-Hyun Noh; Kyung Soo Ko; Byoung Doo Rhee; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Sulfur deposition simulations over China, Japan, and Korea: a model intercomparison study for abating sulfur emission - Cheol-Hee Kim; Lim-Seok Chang; Fan Meng; Mizuo Kajino; Hiromasa Ueda; Yuanhang Zhang; Hye-Young Son; Jong-Jae Lee; Youjiang He; Jun Xu; Keiichi Sato; Tatsuya Sakurai; et al. (Environmental Science and Pollution Research, 2012)

AMPK activation reduces vascular permeability and airway inflammation by regulating HIF/VEGFA pathway in a murine model of toluene diisocyanate-induced asthma - Seoung Ju Park; Kyung Sun Lee; So Ri Kim; Han Jung Chae; Wan Hee Yoo; Dong Im Kim; Myoung Shin Jeon; Yong Chul Lee (Inflammation Research, 2012)

Biological and cytoselective anticancer properties of copper(II)-polypyridyl complexes modulated by auxiliary methylated glycine ligand - Hoi-Ling Seng; Wai-San Wang; Siew-Ming Kong; Han-Kiat Alan Ong; Yip-Foo Win; Raja Noor Zaliha Raja Abd. Rahman; Makoto Chikira; Weng-Kee Leong; Munirah Ahmad; Alan Soo-Beng Khoo; Chew-Hee Ng (BioMetals, 2012)

The suppression of the glutelin storage protein gene in transgenic rice seeds results in a higher yield of recombinant protein - Young-Mi Kim; Jong-Yeol Lee; Theresa Lee; Yeon-Hee Lee; Se-Hee Kim; Sang-Ho Kang; Ung-Han Yoon; Sun-Hwa Ha; Sun-Hyung Lim (Plant Biotechnology Reports, 2012)

Analysis of residual solvents in poly(lactide-co-glycolide) nanoparticles - Eun-Jung Han; Ae-Hee Chung; In-Joon Oh (Journal of Pharmaceutical Investigation, 2012)

Initial validation of GOCI water products against in situ data collected around Korean peninsula for 2010–2011 - Jeong-Eon Moon; Young-Je Park; Joo-Hyung Ryu; Jong-Kuk Choi; Jae-Hyun Ahn; Jee-Eun Min; Young-Baek Son; Sun-Ju Lee; Hee-Jeong Han; Yu-Hwan Ahn (Ocean Science Journal, 2012)

Overview of geostationary ocean color imager (GOCI) and GOCI data processing system (GDPS) - Joo-Hyung Ryu; Hee-Jeong Han; Seongick Cho; Young-Je Park; Yu-Hwan Ahn (Ocean Science Journal, 2012)

QTL analysis of back fat thickness and carcass pH in an F2 intercross between Landrace and Korean native pigs - Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; Taeyoung Kang; Jun Heon Lee; Hee-Bok Park; In-Cheol Cho (Molecular Biology Reports, 2012)

Synthesis and evaluation of thiopyrano[3,4-c]quinoline-9-carboxamide derivatives as inhibitors of poly(ADP-ribose) polymerase-1 (PARP-1) - Chun-Ho Park; Kwangwoo Chun; Bo-Young Joe; Jong-Hee Choi; Han-Chang Lee; Il-Whea Ku; Hyun Young Kim; Seong-Ho Koh; Goang Won Cho; Seung Hyun Kim; Myung-Hwa Kim (Medicinal Chemistry Research, 2012)

The effect of topography and sea surface temperature on heavy snowfall in the Yeongdong region: A case study with high resolution WRF simulation - Sun-Hee Jung; Eun-Soon Im; Sang-Ok Han (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Particle-Size Distribution of Polycyclic Aromatic Hydrocarbons in Urban Road Dust of Masan, Korea - Sung Yong Ha; Gi Beum Kim; Un Hyuk Yim; Won Joon Shim; Sang Hee Hong; Gi Myung Han (Archives of Environmental Contamination and Toxicology, 2012)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

Prevalence and genetic characterization of respiratory syncytial virus (RSV) in hospitalized children in Korea - Yun Hee Baek; Eun Hye Choi; Min-Suk Song; Philippe Noriel Q. Pascua; Hyeok-il Kwon; Su-Jin Park; Jun Han Lee; Sung-Il Woo; Byung-Hoon Ahn; Heon-Seok Han; Yoon-Soo Hahn; Kyeong-Seob Shin; et al. (Archives of Virology, 2012)

Association of colorectal adenoma with components of metabolic syndrome - Byung Chang Kim; Aesun Shin; Chang Won Hong; Dae Kyung Sohn; Kyung Su Han; Kum Hei Ryu; Bum Joon Park; Ji Hyung Nam; Ji Won Park; Hee Jin Chang; Hyo Seong Choi; Jeongseon Kim; et al. (Cancer Causes & Control, 2012)

Potential role of the rice OsCCS52A gene in endoreduplication - Mukhamad Su’udi; Joon-Yung Cha; Min Hee Jung; Netty Ermawati; Chang-deok Han; Min Gab Kim; Young-Min Woo; Daeyoung Son (Planta, 2012)

Sequence Variation and Comparison of the 5S rRNA Sequences in Allium Species and their Chromosomal Distribution in Four Allium Species - Jae-Han Son; Kyong-Cheul Park; Sung-Il Lee; Eun-Jin Jeon; Hyun-Hee Kim; Nam-Soo Kim (Journal of Plant Biology, 2012)

5-Phenylselenyl- and 5-methylselenyl-methyl-2′-deoxyuridine induce oxidative stress, DNA damage, and caspase-2-dependent apoptosis in cancer cells - Byeong Mo Kim; Ambadas B. Rode; Eun Jong Han; In Seok Hong; Sung Hee Hong (Apoptosis, 2012)

Davallialactone protects against adriamycin-induced cardiotoxicity in vitro and in vivo - Sankarganesh Arunachalam; Sun Young Kim; Sun Hwa Lee; Young Hee Lee; Min Sun Kim; Bong Sik Yun; Ho Keun Yi; Pyoung Han Hwang (Journal of Natural Medicines, 2012)

The MCP-1/CCR2 axis in podocytes is involved in apoptosis induced by diabetic conditions - Bo Young Nam; Jisun Paeng; Seung Hye Kim; Sun Ha Lee; Do Hee Kim; Hye-Young Kang; Jin Ji Li; Seung-Jae Kwak; Jung Tak Park; Tae-Hyun Yoo; Seung Hyeok Han; Dong Ki Kim; et al. (Apoptosis, 2012)

Cationic Liposomal Co-delivery of Small Interfering RNA and a MEK Inhibitor for Enhanced Anticancer Efficacy - Seung Hee Kang; Hee-Jeong Cho; Gayong Shim; Sangbin Lee; Su-Hyeon Kim; Han-Gon Choi; Chan-Wha Kim; Yu-Kyoung Oh (Pharmaceutical Research, 2011)

Effects of carbon black to inflammation and oxidative DNA damages in mouse macrophages - Kyung-Taek Rim; Soo-Jin Kim; Jeong-Hee Han; Min-Gu Kang; Jong-Kyu Kim; Jeong-Sun Yang (Molecular & Cellular Toxicology, 2011)

QTL analysis of fruit length using rRAMP, WRKY, and AFLP markers in chili pepper - Heung-Ryul Lee; Ki-Taek Kim; Hyoun-Joung Kim; Jung-Heon Han; Jeong-Ho Kim; Seon-In Yeom; Hyun Jung Kim; Won-Hee Kang; Jinxia-Shi; Soung-Woo Park; Ik-Hyun Bae; Semin Lee; et al. (Horticulture, Environment, and Biotechnology, 2011)

Long-term measurements of atmospheric PM2.5 and its chemical composition in rural Korea - Young-Ji Han; Seong-Rak Kim; Jin-Hee Jung (Journal of Atmospheric Chemistry, 2011)

Sensitivity of spore germination and germ tube elongation of Saccharina japonica to metal exposure - Taejun Han; Jeong-Ae Kong; Hee-Gyu Kang; Seon-Jin Kim; Gyo-Sun Jin; Hoon Choi; Murray T. Brown (Ecotoxicology, 2011)

Interpreting the temperature-induced response of ammonia oxidizing microorganisms in soil using nitrogen isotope fractionation - Seok-In Yun; Hee-Myong Ro; Woo-Jung Choi; Gwang-Hyun Han (Journal of Soils and Sediments, 2011)

Isolation of an Rx homolog from C. annuum and the evolution of Rx genes in the Solanaceae family - Jinxia Shi; Seon-In Yeom; Won-Hee Kang; Min-Kyu Park; Doil Choi; Jin-Kyung Kwon; Jung-Heon Han; Heung-Ryul Lee; Byung-Dong Kim; Byoung-Cheorl Kang (Plant Biotechnology Reports, 2011)

Human chorionic-plate-derived mesenchymal stem cells and Wharton’s jelly-derived mesenchymal stem cells: a comparative analysis of their potential as placenta-derived stem cells - Mi Jeong Kim; Kyung Seon Shin; Jin Hee Jeon; Dong Ryul Lee; Sung Han Shim; Jin Kyeoung Kim; Dong-Hyun Cha; Tae Ki Yoon; Gi Jin Kim (Cell and Tissue Research, 2011)

Natural 15N abundance of paddy rice (Oryza sativa L.) grown with synthetic fertilizer, livestock manure compost, and hairy vetch - Soek-In Yun; Sang-Sun Lim; Gwang-Sung Lee; Sang-Mo Lee; Han-Yong Kim; Hee-Myong Ro; Woo-Jung Choi (Biology and Fertility of Soils, 2011)

Long-term simulations of the sulfur concentrations over the China, Japan and Korea: A model comparison study - Cheol-Hee Kim; Lim-Seok Chang; Jeong-Soo Kim; Fan Meng; Mizuo Kajino; Hiromasa Ueda; Yuanhang Zhang; Hye-Young Son; Youjiang He; Jun Xu; Keiichi Sato; Chang-Keun Song; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Detection of human parechoviruses in children with gastroenteritis in South Korea - Tae-Hee Han; Cheol-Hwan Kim; Sang-Hun Park; Ju-Young Chung; Eung-Soo Hwang (Archives of Virology, 2011)

The sCMV IE enhancer/promoter system for high-level expression and efficient functional studies of target genes in mammalian cells and zebrafish - Goo-Young Kim; Jeong-Mi Moon; Ji-Hye Han; Kyung-Hee Kim; Hyangshuk Rhim (Biotechnology Letters, 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Fine mapping and candidate gene analysis of dense and erect panicle 3, DEP3, which confers high grain yield in rice (Oryza sativa L.) - Yongli Qiao; Rihua Piao; Jinxia Shi; Song-I Lee; Wenzhu Jiang; Baek-Ki Kim; Joohyun Lee; Longzhi Han; Wenbo Ma; Hee-Jong Koh (Theoretical and Applied Genetics, 2011)

Dry matter and nitrogen accumulation and partitioning in rice (Oryza sativa L.) exposed to experimental warming with elevated CO2 - Han-Yong Kim; Sang-Sun Lim; Jin-Hyeob Kwak; Dong-Suk Lee; Sang-Mo Lee; Hee-Myong Ro; Woo-Jung Choi (Plant and Soil, 2011)

Local kallikrein–kinin system is involved in podocyte apoptosis under diabetic conditions - Seung-Jae Kwak; Jisun Paeng; Do Hee Kim; Sun Ha Lee; Bo-Young Nam; Hye Young Kang; Jin Ji Li; Dong-Sub Jung; Seung Hyeok Han; Dong-Ryeol Ryu; Jung Tak Park; Tae Ik Chang; et al. (Apoptosis, 2011)

Trichome density of main stem is tightly linked to PepMoV resistance in chili pepper (Capsicum annuum L.) - Hyun Jung Kim; Jung-Heon Han; Seungill Kim; Heung Ryul Lee; Jun-Sung Shin; Jeong-Ho Kim; Juok Cho; Young Ho Kim; Hee Jae Lee; Byung-Dong Kim; Doil Choi (Theoretical and Applied Genetics, 2011)

Identification of S-allele genotypes of Korean apple cultivars by using allele-specific polymerase chain reaction - Seong Heo; Sang Eun Han; Soon Il Kwon; Ji Hae Jun; Mok Jong Kim; Hee Jae Lee (Horticulture, Environment, and Biotechnology, 2011)

Cephalosporin-induced recurrent aplastic anemia - Jimin Han; Hyojeong Lee; Yoon Su Lee; Yun-Jeong Bae; You Sook Cho; Hee-Bom Moon; Tae-Bum Kim (European Journal of Clinical Pharmacology, 2011)

Mutation analysis of the APC gene in unrelated Korean patients with FAP: four novel mutations with unusual phenotype - Sung-Hee Han; Jae-Song Ryu; Young-Jin Kim; Han-Ik Cho; Young-Ho Yang; Kyoung-Ryul Lee (Familial Cancer, 2011)

Constant slip rate during the late Quaternary along the Sulu He segment of the Altyn Tagh Fault near Changma, Gansu, China - Yeong Bae Seong; Hee Cheol Kang; Jin‐Han Ree; Chaolu Yi; Hyeon Yoon (Island Arc, 2011)
The question of whether millennial‐scale geological slip rates are consistent with decade‐scale geodetic slip rates is of great importance in evaluating the nature of continental deformation within the Tibetan Plateau. We determined the time‐averaged slip rate of the Sulu He segment of the Altyn Tagh Fault, near Changma in Gansu Province, China, based on geomorphic analysis, remote sensing data, and cosmogenic 10 Be surface‐exposure age dating. Quaternary alluvial fan deposits in the study area (Qf1, Qf2, Qf3) are displaced by left‐lateral movement along the Altyn Tagh Fault. Because of the large accumulated displacement of these fans, some of them have become disconnected from the fan apexes that are directly linked to the debris‐source areas in the piedmont of the Qilian Shan to the south. The total minimum offsets are estimated to be about 429 ± 41 m for Qf1, about 130 ± 10 m for Qf2, and 32 ± 1 m for Qf3. The 10 Be surface‐exposure ages obtained for Qf1 and Qf2 are 100–112 ka and 31–43 ka, respectively. Accordingly, the slip rate since the period of Qf1 and Qf2 depositions is calculated to have been about 3.7 mm/yr.

TEA-Sensitive Currents Contribute to Membrane Potential of Organ Surface Primo-node Cells in Rats - Jae-Hong Choi; Chae Jeong Lim; Tae Hee Han; Seul Ki Lee; So Yeong Lee; Pan Dong Ryu (The Journal of Membrane Biology, 2011)

Emergence of norovirus GII-4/2008 variant and recombinant strains in Seoul, Korea - Tae-Hee Han; Cheol-Hwan Kim; Ju-Young Chung; Sang-Hun Park; Eung-Soo Hwang (Archives of Virology, 2011)

Blue LED and succinic acid enhance the growth of Rhodobacter sphaeroides - Hyun Jeong Lee; Ju-Yong Park; Chul-Hee Han; Suk-Tai Chang; Yang-Hoon Kim; Jiho Min (World Journal of Microbiology and Biotechnology, 2011)

Evaluation of the inorganic compound leakage and carbohydrates as indicator of physiological potential of Ulmus parvifolia seeds - Du Hyun Kim; Sim Hee Han; Jeong Ho Song (New Forests, 2011)

Apoptosis of human fibrosarcoma HT-1080 cells by epigallocatechin-3-O-gallate via induction of p53 and caspases as well as suppression of Bcl-2 and phosphorylated nuclear factor-κB - Mi Hee Lee; Dong-Wook Han; Suong-Hyu Hyon; Jong-Chul Park (Apoptosis, 2011)

Comparative global transcription analysis of Aconitum koreanum Raymond, Typhonium gigantum Engl., and Helianthus tuberosis Linne - Ki Suk Kim; Jin Tae; Jung Bum Han; Kwang Seok Ahn; Beom-Joon Lee; Seok-Geun Lee; Jun-Hee Lee; Sung-Hoon Kim; Ho young Choi; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2010)

Proteome analysis of Arabidopsis seedlings exposed to bacterial volatiles - Young Sang Kwon; Choong-Min Ryu; Soohyun Lee; Hyo Bee Park; Ki Soo Han; Jung Han Lee; Kyunghee Lee; Woo Sik Chung; Mi-Jeong Jeong; Hee Kyu Kim; Dong-Won Bae (Planta, 2010)

Biodegradation of bisphenol A and its halogenated analogues by Cunninghamella elegans ATCC36112 - Young Soo Keum; Hye Ri Lee; Hee Won Park; Jeong-Han Kim (Biodegradation, 2010)

Genetic characterization of rotavirus in children in South Korea from 2007 to 2009 - Tae-Hee Han; Cheol-Hwan Kim; Ju-Young Chung; Sang-Hun Park; Eung-Soo Hwang (Archives of Virology, 2010)

Evaluation of mutagenic activity in the Nakdong river and advanced drinking water treatment processes - Shun-Hwa Lee; Se-Han Lee; Weon-Hwa Jheong; Tae-Seung Kim; Yun-Hee Kim (Molecular & Cellular Toxicology, 2010)

Antitumor and antimetastatic effects of licochalcone A in mouse models - Jin-Kyung Kim; Eun Kyung Shin; Jun Hong Park; Yoon Hee Kim; Jung Han Yoon Park (Journal of Molecular Medicine, 2010)

Function analysis of mesenchymal Bcor in tooth development by using RNA interference - Jinglei Cai; Sungwook Kwak; Jong-Min Lee; Eun-Jung Kim; Min-Jung Lee; Gi-Hee Park; Sung-Won Cho; Han-Sung Jung (Cell and Tissue Research, 2010)

Simultaneous gene expression signature of heart and peripheral blood mononuclear cells in astemizole-treated rats - Eun-Hee Lee; Jung-Hwa Oh; Han-Jin Park; Do-Geun Kim; Jong-Hwa Lee; Choong-Yong Kim; Myung-Sang Kwon; Seokjoo Yoon (Archives of Toxicology, 2010)

Glutathione peroxidase 1 protects mitochondria against hypoxia/reoxygenation damage in mouse hearts - Vu Thi Thu; Hyoung Kyu Kim; Seung Hee Ha; Ji-Young Yoo; Won Sun Park; Nari Kim; Goo Taeg Oh; Jin Han (Pflügers Archiv - European Journal of Physiology, 2010)

c-myb has a character of oxidative stress resistance in aged human diploid fibroblasts: regulates SAPK/JNK and Hsp60 pathway consequently - Young-Hee Lee; Nan-Hee Lee; Govinda Bhattarai; Pyong-Han Hwang; Tae-Il Kim; Eun-Chung Jhee; Ho-Keun Yi (Biogerontology, 2010)

Rapid detection of virulence stx2 gene of Enterohemorrhagic Escherichia coli using two-step ultra-rapid real-time PCR - Il-Wook Kim; Min-Hee Kang; Soon-Hwan Kwon; Seung-Hak Cho; Byung-Sun Yoo; Sang-Hoon Han; Byoung-Su Yoon (Biotechnology Letters, 2010)

Amelioration of hyperglycemia by intestinal overexpression of glucagon-like peptide-1 in mice - Meng-Ju Liu; Jaeseok Han; Young-Sun Lee; Mi-Sung Park; Seungjin Shin; Hee-Sook Jun (Journal of Molecular Medicine, 2010)

Growth response of Acacia mangium Willd. seedlings to arbuscular mycorrhizal fungi and four isolates of the ectomycorrhizal fungus Pisolithus tinctorius (Pers.) Coker and Couch - Nelly Siababa Aggangan; Heung Kyu Moon; Sim Hee Han (New Forests, 2010)

Toxicoproteomic analysis of phalloidin-induced cholestasis in mouse liver - Sun Hee Heo; Jung-Hwa Oh; Han-Jin Park; Myung-Sang Kwon; Suresh V. S. Rana; Seokjoo Yoon (Molecular & Cellular Toxicology, 2010)

Endogenous Zinc Mediates Apoptotic Programmed Cell Death in the Developing Brain - Eunsil Cho; Jung-Jin Hwang; Seung-Hee Han; Sun Ju Chung; Jae-Young Koh; Joo-Yong Lee (Neurotoxicity Research, 2010)

Active reassortment of H9 influenza viruses between wild birds and live-poultry markets in Korea - Ho Jin Moon; Min Suk Song; Deu John M. Cruz; Kuk Jin Park; Philippe Noriel Q. Pascua; Jun Han Lee; Yun Hee Baek; Dong Ho Choi; Young Ki Choi; Chul Joong Kim (Archives of Virology, 2010)

Hypothyroidism Induced by Polychlorinated Biphenyls and Up-Regulation of Transthyretin - Dae-Yong Han; Sang-Rim Kang; Oh-Sung Park; Jae-Hyeon Cho; Chung-Kil Won; Hyeon-Soo Park; Kwang-Il Park; Eun-Hee Kim; Gon-Sup Kim (Bulletin of Environmental Contamination and Toxicology, 2010)

Application of SSR markers and real-time PCR for variety identification in azuki-bean [Vigna angularis (Willd.) Ohwi and Ohashi] - Sang-Ik Han; Deuk-Yong Suh; Tae Joung Ha; Myong-Hee Lee; Woo-Duck Seo; Seong-Hwan Oh; Ki-Chang Jang; Je-Bong Lee; Keum-Yong Park; Hang-Won Kang (Journal of Crop Science and Biotechnology, 2009)

Detection of Human Bocavirus-2 in children with acute Gastroenteritis in South Korea - Tae-Hee Han; Cheol-Hwan Kim; Sang-Hun Park; En-Jung Kim; Ju-Young Chung; Eung-Soo Hwang (Archives of Virology, 2009)

Promoter hypermethylation and Up-regulation of thyroid-stimulating-hormone-alpha (TSH-α) in thyroid cancer - Kyung Hee Han; Keun Su Son; Jun Euy Hong; Sun Jung Kim (Genes & Genomics, 2009)

Antioxidant and Antimicrobial Activity of Zostera marina L. Extract - Han-Gil Choi; Ji-Hee Lee; Hyang-Ha Park; Fotoon A.Q. Sayegh (Algae, 2009)

Molecular characterization and physico-chemical analysis of a new giant embryo mutant allele (ge t) in rice (Oryza sativa L.) - Dong-Soo Park; Soo-Kwon Park; Bong-Chun Lee; Song-Yi Song; Nam-Soo Jun; Norvie L. Manigbas; Jun-Hyun Cho; Min-Hee Nam; Jong-Seong Jeon; Chang-Deok Han; Kyung-Jin Choi; Doh-Hoon Kim; et al. (Genes & Genomics, 2009)

Benzene activates caspase-4 and -12 at the transcription level, without an association with apoptosis, in mouse bone marrow cells lacking the p53 gene - Jung-Yeon Yi; Yoko Hirabayashi; Yang-Kyu Choi; Yukio Kodama; Jun Kanno; Jeong-Hee Han; Tohru Inoue; Byung-Il Yoon (Archives of Toxicology, 2009)

Changes in anthocyanin and isoflavone concentrations in black seed-coated soybean at different planting locations - Tae Joung Ha; Jin Hwan Lee; Sang-Ouk Shin; Seong-Hyu Shin; Sang-Ik Han; Hyun-Tae Kim; Jong-Min Ko; Myong-Hee Lee; Keum-Yong Park (Journal of Crop Science and Biotechnology, 2009)

Y-STR genetic structure of the most common surnames in Korea - Soon Hee Kim; Jongwoo Jung; Nam Soo Cho; Jung Ho Hwang; Seong Yeon Yoo; Ki Min Seong; Myun Soo Han; Won Kim (Genes & Genomics, 2009)

Detection of human rhinovirus C in children with acute lower respiratory tract infections in South Korea - Tae-Hee Han; Ju-Young Chung; Eung-Soo Hwang; Ja-Wook Koo (Archives of Virology, 2009)

Relating Tree Ring Chemistry of Pinus densiflora to Precipitation Acidity in an Industrial Area of South Korea - Jin-Hyeob Kwak; Sang-Sun Lim; Hyun-Jung Park; Sun-Il Lee; Kye-Han Lee; Han-Yong Kim; Scott X. Chang; Sang-Mo Lee; Hee-Myong Ro; Woo-Jung Choi (Water, Air, & Soil Pollution, 2009)

Chitosan hydrogel containing GMCSF and a cancer drug exerts synergistic anti-tumor effects via the induction of CD8+ T cell-mediated anti-tumor immunity - Soo Hong Seo; Hee Dong Han; Kyung Hee Noh; Tae Woo Kim; Sang Wook Son (Clinical & Experimental Metastasis, 2009)

Introducing pulsed low-intensity ultrasound to culturing human umbilical cord-derived mesenchymal stem cells - Jong Hyun Yoon; Eun Youn Roh; Sue Shin; Nam Hee Jung; Eun Young Song; Dong Soon Lee; Kyou Sup Han; Joung Sung Kim; Byoung Jae Kim; Hye Won Jeon; Kang Sup Yoon (Biotechnology Letters, 2009)

Transgenic peppers that are highly tolerant to a new CMV pathotype - Yun Hee Lee; Min Jung; Sun Hee Shin; Ji Hee Lee; Soon Ho Choi; Nam Han Her; Jang Ha Lee; Ki Hyun Ryu; Kee Yoeup Paek; Chee Hark Harn (Plant Cell Reports, 2009)

Effect of mild hypothermia on blood brain barrier disruption induced by oleic acid in rats - Kyung Min Lee; Jae Hee Jang; Jae Sik Park; Dong Sun Kim; Hyung Soo Han (Genes & Genomics, 2009)

BAC-derived markers converted from RFLP linked to Phytophthora capsici resistance in pepper (Capsicum annuum L.) - Hyoun-Joung Kim; Seok-Hyeon Nahm; Heung-Ryul Lee; Gi-Bo Yoon; Ki-Taek Kim; Byoung-Cheorl Kang; Doil Choi; Oh Yeol Kweon; Myeong-Cheoul Cho; Jin-Kyung Kwon; Jung-Heon Han; Jeong-Ho Kim; et al. (Theoretical and Applied Genetics, 2008)

Licochalcone A isolated from licorice suppresses lipopolysaccharide-stimulated inflammatory reactions in RAW264.7 cells and endotoxin shock in mice - Hyuck-Se Kwon; Jun Hong Park; Dae Hwan Kim; Yoon Hee Kim; Jung Han Yoon Park; Hyun-Kyung Shin; Jin-Kyung Kim (Journal of Molecular Medicine, 2008)

Identification of Softness Syndrome-Associated Candidate Genes and DNA Sequence Variation in the Sea Squirt, Halocynthia roretzi - Hyun Kook Cho; Bo-Hye Nam; Hee Jeong Kong; Hyon Sob Han; Young Baek Hur; Tae Jin Choi; Yung Hyun Choi; Woo Jin Kim; JaeHun Cheong (Marine Biotechnology, 2008)

Screening Enantioselective Epoxide Hydrolase Activities from Marine Microorganisms: Detection of Activities in Erythrobacter spp. - Young-Ok Hwang; Sung Gyun Kang; Jung-Hee Woo; Kye Kyung Kwon; Takako Sato; Eun Yeol Lee; Myong Soo Han; Sang-Jin Kim (Marine Biotechnology, 2008)

Fine mapping and candidate gene analysis of hwh1 and hwh2, a set of complementary genes controlling hybrid breakdown in rice - Wenzhu Jiang; Sang-Ho Chu; Rihua Piao; Joong-Hyoun Chin; Yong-Mei Jin; Joohyun Lee; Yongli Qiao; Longzhi Han; Zongze Piao; Hee-Jong Koh (Theoretical and Applied Genetics, 2008)

Perfluorooctanoic acid-induced hepatic toxicity following 21-day oral exposure in mice - Hee-Young Son; Sang-Hyun Kim; Hong-In Shin; Han Ik Bae; Jae-Ho Yang (Archives of Toxicology, 2008)

Sequence analysis of the ORF 7 region of transmissible gastroenteritis viruses isolated in Korea - Jeong Ho Park; Jeong Hee Han; Hyuk Moo Kwon (Virus Genes, 2008)

Acetylcholine inhibits long-term hypoxia-induced apoptosis by suppressing the oxidative stress-mediated MAPKs activation as well as regulation of Bcl-2, c-IAPs, and caspase-3 in mouse embryonic stem cells - Min Hee Kim; Mi Ok Kim; Jung Sun Heo; Jin Sang Kim; Ho Jae Han (Apoptosis, 2008)

Tobacco cultivars vary in induction of systemic resistance against Cucumber mosaic virus and growth promotion by Pseudomonas chlororaphis O6 and its gacS mutant - Choong-Min Ryu; Beom Ryong Kang; Song Hee Han; Song Mi Cho; Joseph W. Kloepper; Anne J. Anderson; Young Cheol Kim (European Journal of Plant Pathology, 2007)

Analysis of gene-trap Ds rice populations in Korea - Sung Han Park; Nam Soo Jun; Chul Min Kim; Tae Yong Oh; Jin Huang; Yuan-hu Xuan; Soon Ju Park; Byoung Il Je; Hai Long Piao; Soo Hyun Park; Young Soon Cha; Byung Ohg Ahn; et al. (Plant Molecular Biology, 2007)

Identification of the ADP-glucose pyrophosphorylase isoforms essential for starch synthesis in the leaf and seed endosperm of rice (Oryza sativa L.) - Sang-Kyu Lee; Seon-Kap Hwang; Muho Han; Joon-Seob Eom; Hong-Gyu Kang; Yulyi Han; Sang-Bong Choi; Man-Ho Cho; Seong Hee Bhoo; Gynheung An; Tae-Ryong Hahn; Thomas W. Okita; et al. (Plant Molecular Biology, 2007)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

3D gravity modelling for Anyongbok Seamount in the East Sea - Moo Hee Kang; Hyun-Chul Han; Hyesu Yun; Gee Soo Kong; Kyong O. Kim; Youn Soo Lee (Marine Geophysical Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Microarray analysis of apple gene expression engaged in early fruit development - Young-Pyo Lee; Gyung-Hee Yu; Young Sam Seo; Sang Eun Han; Yeon-Ok Choi; Daeil Kim; Il-Gin Mok; Woo Taek Kim; Soon-Kee Sung (Plant Cell Reports, 2007)

Vegetation of Barton Peninsula in the neighbourhood of King Sejong Station (King George Island, maritime Antarctic) - Ji Hee Kim; In-Young Ahn; Kyu Song Lee; Hosung Chung; Han-Gu Choi (Polar Biology, 2007)

Construction of the bifunctional enzyme cellulase-β-glucosidase from the hyperthermophilic bacterium Thermotoga maritima - Su-Young Hong; Jin-Suk Lee; Kye-Man Cho; Renukaradhya K. Math; Yong-Hee Kim; Sun-Joo Hong; Yong-Un Cho; Soo-Jeong Cho; Hoon Kim; Han-Dae Yun (Biotechnology Letters, 2007)

The occurrence time estimation of oil contaminated source considering hydro-geological features - Yang-Kyoo Lee; Hee-Wook Ryu; Jai-Young Lee; Jung-Geun Han; Kyong-Ho Chang; Jae-Ho Lee (Geosciences Journal, 2007)

A phosphate starvation-induced acid phosphatase from Oryza sativa: phosphate regulation and transgenic expression - Yeon Jae Hur; Han Gil Lee; Eun Ji Jeon; Yun Young Lee; Min Hee Nam; Gihwan Yi; Moo Young Eun; Jaesung Nam; Jai Heon Lee; Doh Hoon Kim (Biotechnology Letters, 2007)

Alpha-tocopheryl succinate sensitizes human colon cancer cells to exisulind-induced apoptosis - Soo-Jeong Lim; Young-Ju Lee; Dae-Hun Park; Eunmyong Lee; Moon-Kyung Choi; Wanseo Park; Kyung-Hee Chun; Han-Gon Choi; Jung Sik Cho (Apoptosis, 2007)

Assembling a novel bifunctional cellulase–xylanase from Thermotoga maritima by end-to-end fusion - Su Young Hong; Jin Suk Lee; Kye Man Cho; Renukaradhya K Math; Yong Hee Kim; Sun Joo Hong; Yong Un Cho; Hoon Kim; Han Dae Yun (Biotechnology Letters, 2006)

Differential Involvement of Mitochondrial Permeability Transition in Cytotoxicity of 1-Methyl-4-Phenylpyridinium and 6-Hydroxydopamine - Chung Soo Lee; Woo Jae Park; Hyun Hee Ko; Eun Sook Han (Molecular and Cellular Biochemistry, 2006)

A comprehensive expression analysis of the WRKY gene superfamily in rice plants during defense response - Hak-Seung Ryu; Muho Han; Sang-Kyu Lee; Jung-Il Cho; Nayeon Ryoo; Sunggi Heu; Youn-Hyung Lee; Seong Hee Bhoo; Guo-Liang Wang; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Cell Reports, 2006)

Biflavonoids inhibited phosphatase of regenerating liver-3 (PRL-3) - Sung-Kyu Choi; Hyun-Mi Oh; Su-Kyung Lee; Dae Gwin Jeong; Seong Eon Ryu; Kwang-Hee Son; Dong Cho Han; Nack-Do Sung; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Cretaceous thermal event around the Gongsuwon thrust in the northeastern Okcheon belt: evidence from Rb−Sr geochronology of Paleozoic sedimentary rocks - Hee Sagong; Sung-Tack Kwon; Raehee Han; Jin-Han Ree (Geosciences Journal, 2006)

The use of Silver-coated Ceramic Beads for Sterilization of Sphingomonas sp. in Drinking Mineral Water - Dong-Wook Han; Min Sub Lee; Mi Hee Lee; Masakazu Uzawa; Jong-Chul Park (World Journal of Microbiology and Biotechnology, 2005)

Agrobacterium-mediated transformation of Perilla (Perilla frutescens) - Byoung-Kyu Lee; Seung-Hee Yu; Yul-Ho Kim; Byung-Ohg Ahn; Han-Sun Hur; Sang-Chul Lee; Zhanyuan Zhang; Jang-Yong Lee (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Large-scale identification and characterization of genetic variants in asthma candidate genes - Jae-Jung Kim; Hyun-Hee Kim; Joo-Hyun Park; Ha-Jung Ryu; JuYoung Kim; Songmean Moon; Haeok Gu; Hung-Tae Kim; Jong-Young Lee; Bok-Ghee Han; Chan Park; Kuchan Kimm; et al. (Immunogenetics, 2005)

Protection of osteoblastic cells from freeze/thaw cycle-induced oxidative stress by green tea polyphenol - Dong-Wook Han; Hak Hee Kim; Mi Hee Lee; Hyun Sook Baek; Kwon-Yong Lee; Suong-Hyu Hyon; Jong-Chul Park (Biotechnology Letters, 2005)

Tsc-22 enhances TGF-? signaling by associating with Smad4 and induces erythroid cell differentiation - So-Jung Choi; Jae-Hoon Moon; Young-Wook Ahn; Jin-Hyun Ahn; Dong-Uk Kim; Tae-Hee Han (Molecular and Cellular Biochemistry, 2005)

Exposure to air pollution and pulmonary function in university students - Yun-Chul Hong; Jong-Han Leem; Kwan-Hee Lee; Dong-Hyun Park; Jae-Yeon Jang; Sun-Tae Kim; Eun-Hee Ha (International Archives of Occupational and Environmental Health, 2005)

Development and characterization of a recombinant chicken single-chain Fv antibody detecting Eimeria acervulina sporozoite antigen - Kyung Je Park; Dong Woon Park; Chun Hee Kim; Beom Ku Han; Tae Sub Park; Jae Yong Han; Hyun Soon Lillehoj; Jin-Kyoo Kim (Biotechnology Letters, 2005)

Overexpression of human erythropoietin (EPO) affects plant morphologies: retarded vegetative growth in tobacco and male sterility in tobacco and Arabidopsis - Ban Yoon Cheon; Hae Jin Kim; Kyung Hee Oh; Sung Chul Bahn; Ji Hoon Ahn; Jang Won Choi; Sung Han Ok; Jung Myung Bae; Jeong Sheop Shin (Transgenic Research, 2004)

Composted sewage sludge can improve the physiological properties ofBetula schmidtii grown in tailings - Sim-Hee Han; Jae-Cheon Lee; Suk-Seong Jang; Pan-Gi Kim (Journal of Plant Biology, 2004)

Genotyping Possible Polymorphic Variants of Human Mismatch Repair Genes in Healthy Korean Individuals and Sporadic Colorectal Cancer Patients - Jin C. Kim; Seon A. Roh; Kum H. Koo; In H. Ka; Hee C. Kim; Chang S. Yu; Kang H. Lee; Jung S. Kim; Han I. Lee; Walter F. Bodmer (Familial Cancer, 2004)

Differential effect of nitrogen species on changes in mitochondrial membrane permeability due to mitomycin c in lung epithelial cells - Hyun Hee Ko; Se Young Park; Chung Soo Lee; Jin Ho Song; Eun Sook Han (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Urea-nitrogen transformation and compost-nitrogen mineralization in three different soils as affected by the interaction between both nitrogen inputs - Kyung-Hwa Han; Woo-Jung Choi; Gwang-Hyun Han; Seok-In Yun; Sun-Ho Yoo; Hee-Myong Ro (Biology and Fertility of Soils, 2004)

Cloning and Expression of Pyrroloquinoline Quinone (PQQ) Genes from a Phosphate-Solubilizing Bacterium Enterobacter intermedium - Chul Hong Kim; Song Hee Han; Kil Yong Kim; Baik Ho Cho; Yong Hwan Kim; Bon Sung Koo; Young Cheol Kim (Current Microbiology, 2003)

Isolation and characterization of a novel rice Ca2 +-regulated protein kinase gene involved in responses to diverse signals including cold, light, cytokinins, sugars and salts - Kyung-Nam Kim; Jung-Sook Lee; Hee Han; Seung Ah Choi; Seung Joo Go; In Sun Yoon (Plant Molecular Biology, 2003)

Molecular cloning of vitellogenin cDNA in rockfish (Sebastes schlegeli) and effects of estrogenic substances on its gene expression - Jee-Hyun Jung; Yong-Chang Sohn; Jae-Yong Lee; Dae-Jung Kim; Ji-Seon Lee; Joong-Kyon Jeon; Chang-Hee Han (Fish Physiology and Biochemistry, 2003)

Determination of UDP-N-acetylglucosamine:β-D-mannoside-1,4-N-acetylglucosaminyltransferase-III in patients sera with chronic hepatitis and liver cirrhosis using a monoclonal antibody - Eun-Young Song; Kyung-Sook Kim; Kyoung-A. Kim; Yung-Dai Kim; Dur-Han Kwon; Si-Myung Byun; Hee-Jung Kim; Tae-Wook Chung; Yong-Kyung Choe; Tai -Wha Chung; Cheorl-Ho Kim (Glycoconjugate Journal, 2002)

Changes of Flow Characteristics by Stenting in Aneurysm Models: Influence of Aneurysm Geometry and Stent Porosity - Kyehan Rhee; Moon Hee Han; Sang Hoon Cha (Annals of Biomedical Engineering, 2002)

The Potential use of a Viral Coat Protein Gene as a Transgene Screening Marker and Multiple Virus Resistance of Pepper Plants Coexpressing Coat Proteins of Cucumber Mosaic Virus and Tomato Mosaic Virus - Ryoung Shin; Jung-Heon Han; Gil-Je Lee; Kyung-Hee Peak (Transgenic Research, 2002)

Evaluation of nitrate contamination sources of unconfined groundwater in the North Han River basin of Korea using nitrogen isotope ratios - Woo-Jung Choi; Gwang-Hyun Han; Hee-Myong Ro; Sun-Ho Yoo; Sang-Mo Lee (Geosciences Journal, 2002)

Expression and purification of Listeria innocua Sv6b p60 invasion associated protein - Yong-Hee Choi; Sang-Hoon Han; Yong-Soon Lee; Yoon-Kyu Lim; In-Gyu Kim; Byoung-Su Yoon (Biotechnology Letters, 2001)

Geothermal gradient of the upper mantle beneath Jeju Island, Korea: Evidence from mantle xenoliths - Seong Hee Choi; Yong-Joo Jwa; Han Yeang Lee (Island Arc, 2001)

Geothermal gradient of the upper mantle beneath Jeju Island, Korea: Evidence from mantle xenoliths - Seong Hee Choi; Yong‐Joo Jwa; Han Yeang Lee (Island Arc, 2001)
Ultramafic xenoliths found in alkali basalts from Jeju Island, Korea are mostly spinel lherzolites accompanied by subordinate amount of spinel harzburgites and pyroxenites. The combination of results from a two‐pyroxene geothermometer and Ca‐in‐olivine geobarometer yields temperature–pressure (T–P) estimates for spinel peridotites that fall in experimentally determined spinel lherzolite field in CaO‐Fe‐MgO‐Al 2 O 3 ‐SiO 2 ‐Cr 2 O 3 (CFMASCr) system. These T–P data sets have been used to construct the Quaternary Jeju Island geotherm, which defines a locus from about 13 kbar at 880°C to 26 kbar at 1040°C. The geothermal gradient of Jeju Island is greater than that of the conventional conductive models, and may be as a result of a thermal perturbation by the heat input into the lithospheric mantle via the passage and emplacement of magma. Spinel–lherzolite is the main constituent rock‐type of the lithospheric mantle beneath Jeju Island. Pyroxenites may be intercalated in peridotites at similar depth and temperature as re‐equilibrated veins or lenses.

Intramitochondrial pyruvate attenuates hydrogen peroxide-induced apoptosis in bovine pulmonary artery endothelium - Young-Hee Kang; Se-Jin Chung; Il-Jun Kang; Jung Han Yoon Park; Rolf Bunger (Molecular and Cellular Biochemistry, 2001)

Activities of sulfhydryl-related and phenylpropanoid-synthesizing enzymes during the germination ofArabidopsis thaliana seeds - Keum -Nam Park; Jae -Hoon Sa; Byung -Don Han; Eun -Hee Park; Chang -Jin Lim (Journal of Plant Biology, 1998)

A Rapid DNA Extraction Method for RFLP and PCR Analysis from a Single Dry Seed - Hee Wan Kang; Yong Gu Cho; Ung Han Yoon; Moo Young Eun (Plant Molecular Biology Reporter, 1998)